Nanofiltration-assisted electro-Fenton treatment of pharmaceuticals in real surface water: Matrix conditioning for energy-efficient concentrate treatment - Alexandre Giacobbo; Louidi L. Albornoz; Raíssa E. Guimarães; Marco A.S. Rodrigues; Andréa M. Bernardes; Salatiel W. da Silva (Desalination, 2026)

An exploratory traffic impact analysis in a knowledge-based urban development area: the HIDS/UNICAMP case study - Vitor Eduardo Molina Junior; William Machado Emiliano; Vivian Silveira dos Santos Bardini; Marcela Noronha Pinto de Oliveira e Sousa; Silvia Regina Stuchi Cruz; Bruno Noronha Rodrigues; Ana Laura Fragoso Favoreti; José Telhada; Felippe Benavente Canteras (Clean Technologies and Environmental Policy, 2026)

Coordinated regulation of water relations and leaf succulence in beet (Beta vulgaris L.) under interacting salinity and soil moisture stress - Lucas Yago de Carvalho Leal; Martha Katharinne Silva Souza Paulino; Ênio Farias de França e Silva; Bruce Schaffer; Edivan Rodrigues de Souza (Acta Physiologiae Plantarum, 2026)
Salinity and soil water limitation frequently co-occur in semi-arid environments, yet their combined effects on plant water regulation remain insufficiently understood. In this study, we examined how soil moisture influences the physiological responses of beet ( Beta vulgaris L.) to increasing salinity, focusing on water relations, osmotic adjustment, and leaf succulence. Beet ( B. vulgaris L.) plants were grown in a controlled soil system under a 5 × 3 factorial arrangement with four replicates, combining five irrigation water salinity levels (0–8 dS m⁻¹) and three soil moisture conditions (100%, 90%, and 80% of field capacity). Soil electrical conductivity and osmotic potential were monitored, and plant responses were assessed through biomass production, relative water content, leaf succulence, electrolyte leakage, plant water potential, and osmotic adjustment. Salinity increased osmotic adjustment and leaf succulence while progressively reducing relative water content and plant water potential. However, these responses depended on soil moisture level, indicating an interaction between osmotic and matric constraints. Moderate salinity (4 dS m⁻¹) combined with 90% field capacity promoted the highest biomass accumulation and was associated with enhanced osmotic adjustment and succulence. These findings indicate that osmotic adjustment and leaf succulence function as complementary mechanisms contributing to the maintenance of plant water status under interacting salinity and soil moisture stress.

High virulence of Cordyceps javanica to eggs and all nymphal stages of cashew whitefly Aleurodicus cocois in a screenhouse - Pedro Vitor Moura Silva; Nivia da Silva Dias; Sandra Maria Morais Rodrigues; Marcela Camily Rodrigues Gomes; Gabriela Priscila Sousa Maciel; Heloiza Alves Boaventura; Jose Francisco Arruda e Silva; Celli Rodrigues Muniz; Eliane Dias Quintela (Crop Protection, 2026)

Comprehensive characterization of walnut oil processing by-products: biochemical composition, bioactive properties, and polyphenol in vitro bioaccessibility and bioavailability - Rafael Mascoloti Spréa; Daniele Bobrowski Rodrigues; Tânia C.S. Pires; Ricardo C. Calhelha; María E. Brassesco; Manuela Pintado; Susana Santoyo; Elena Arranz; Miguel A. Prieto; Lillian Barros; Joana S. Amaral (Food Chemistry, 2026)

Toxicity and repellency of the monoterpenoids carvone and eucalyptol on Sitophilus zeamais: contact and fumigation-based interactions - Daniele Muniz dos Reis; Solange Maria de França; Davila Esmelinda Oliveira Silva; Mariano Oscar Aníbal Ibañez Rojas; Giovana Lopes da Silva; Leonardo Baltazar Cantanhede; Herus Pablo Firmino Martins; Guilherme Santos de Sousa; Ana Patrícia Rodrigues Teixeira dos Reis; Gutierres Nelson Silva; Paulo Roberto Ramalho Silva; Lúcia da Silva Fontes; et al. (Journal of Plant Diseases and Protection, 2026)
Corn is a globally important crop; however, pest infestations during storage represent a major challenge. The maize weevil, Sitophilus zeamais (Coleoptera: Curculionidae), is a primary pest of stored maize, commonly controlled through phosphine fumigation. Nevertheless, extensive reliance on this insecticide has led to the emergence of resistant populations. Thus, the objective of this study was to evaluate the contact and fumigant toxicity of the monoterpenoids carvone and eucalyptol against S. zeamais , addressing the previously unexplored contact toxicity and repellency of these compounds following impregnation into maize grains, as well as their effects on population growth, insect fresh weight, and grain mass consumption. Experiments were conducted under laboratory conditions (28 ± 2 °C, 60 ± 10% relative humidity and a 12 h photoperiod) using a completely randomized design. Lethal concentrations (LC₅₀ and LC₉₅) were determined for contact and fumigation bioassays, and the LC₅₀ values obtained in the contact tests were used in repellency assays. Carvone exhibited higher toxicity than eucalyptol in both bioassays. In the contact toxicity test, LC₅₀ values were 3.48 µL/20 g for carvone and 14.35 µL/20 g for eucalyptol, while in fumigation assays the LC₅₀ values were 7.68 µL/L and 59.56 µL/L, respectively. Both compounds showed strong repellent activity against S. zeamais , with LC₅₀ treatments attracting only 0.2 and 0.8 insects to eucalyptol- and carvone-treated grains, respectively, corresponding to repellency levels above 90%. The treatments significantly reduced adult emergence and resulted in negative instantaneous population growth rates (r i ranging from − 0.0255 to − 0.0512), indicating population decline. Grain weight loss was reduced to 1.6% for carvone and 0.9% for eucalyptol when LC₅₀ concentrations were applied. These results demonstrate that carvone and eucalyptol exhibit insecticidal and repellent properties and may represent promising alternative agents for the management of S. zeamais in stored maize.

Seed desiccation tolerance and conservation of sapucaia, an emerging functional Brazil nut tree from the Atlantic and Amazon forest biomes - Caroline Palacio de Araujo; Ingridh Medeiros Simões; Joana Silva Costa; Taísa de Fátima Rodrigues de Almeida; Débora Pellanda Fagundes; Eduardo Santos Cade; Emanuel Bizareli de Moraes; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; José Eduardo Macedo Pezzopane; José Carlos Lopes; Heloisa Oliveira dos Santos; et al. (Journal of Stored Products Research, 2026)

A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.

Abscisic Acid Modulates Physiological and Proteomic Changes During Histodifferentiation and Germination of Somatic Embryos in Euterpe edulis - Débora Pellanda Fagundes; Joana Silva Costa; Jociel Nascimento de Noronha; Mateus Santana Rodrigues; Caroline Palacio de Araujo; Simone Wellita Simão de Carvalho; Ingridh Medeiros Simões; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; Elias Terra Werner; Marcia Flores da Silva Ferreira; Amir Ali Khoddamzadeh; et al. (Journal of Plant Growth Regulation, 2026)
Euterpe edulis Martius (juçara palm) is an endangered species of high ecological and economic importance. Its propagation via reproduction is limited by the recalcitrance of its seeds, which hinders conservation and genetic improvement. Somatic embryogenesis represents an efficient alternative for large-scale clonal propagation and conservation. The present study evaluated the effect of abscisic acid (ABA) on histodifferentiation and germination of somatic embryos, to optimize in vitro regeneration of E. edulis . High rates of histodifferentiation (~ 98%) and germination (~ 95%) were achieved with 5 µM ABA, resulting in vigorous embryos with well-developed haustoria. Higher ABA concentrations (10–15 µM) were associated with reduced germination and delayed developmental progression, whereas the absence of ABA impaired histodifferentiation and embryo vigor. Proteomic profiling revealed increased accumulation of structural proteins (β-TUB7, TUBB1, TUBB5), chaperones (HSP83), proteasome components (PSMA2-like), energy metabolism enzymes (GAPDH2, PFK, PFP-α), tricarboxylic acid/glyoxysomal enzymes (SDH5, MDH-glyox), and nitrogen/methylation enzymes (GS, AHCY) in embryos treated with 5 µM ABA, suggesting associations with cytoskeletal remodeling, mitochondrial stability, epigenetic adjustments, and selective translation. In contrast, a decrease in defense proteins such as PR1 reflected a typical developmental trade-off. ABA also involves the integration of hormonal adjustments and the regulation of antioxidant enzymes. In summary, 5 µM ABA promotes efficient histodifferentiation and germination of embryos, enabling in vitro cloning, conservation, and genetic improvement of the species.

Nanofiltration-assisted electro-Fenton treatment of pharmaceuticals in real surface water: matrix conditioning for energy-efficient concentrate treatment - Alexandre Giacobbo; Louidi L. Albornoz; Raíssa E. Guimarães; Marco A.S. Rodrigues; Andréa M. Bernardes; Salatiel W. da Silva (Desalination, 2026)

Corrigendum to “Pseudo-ternary chromatographic separation of dihydroxyacetone from the glycerol oxidation byproducts on a simulated moving bed cascade” [Chem. Eng. J. 476 (2023) 146447] - Pedro M. Walgode; Rui P.V. Faria; Alírio E. Rodrigues (Chemical Engineering Journal, 2026)

First description of the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi (Acari: Ixodidae), Amazon, Pará, Brazil - Lucas Henrique da Silva e Silva; Fábio Silva da Silva; Sandro Patroca da Silva; Paulo Henrique Gomes de Castro; Anita Roberta Stone; Leonardo Henrique Almeida Hernández; Daniel Damous Dias; Sâmia Luzia Sena da Silva; Lucia Aline Moura Reis; Hanna Carolina Farias Reis; Liliane Leal das Chagas; Tania Cristina Alves da Silveira da Cunha; et al. (Experimental and Applied Acarology, 2026)
The genus Amblyomma koch, 1844 contains approximately 138 species, which are mainly distributed in the Afrotropical, Oriental, Neotropical and Australasian zoogeographic regions. This is an important group of arthropod vectors responsible for transmitting a wide range of etiological agents that cause infections and diseases in humans and animals, and is therefore of great interest to public and veterinary health.This study describes and characterizes, for the first time, the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi . The obtained sequences presented a circular molecule structured in 37 functional subunits with 13 Protein-Coding Genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNA (rRNAs), two replication control regions, and two regions called “Tick-box”. The phylogeny reconstructed using the maximum likelihood method, based on the 13 concatenated PCGs, produced a monophyletic group for the genus Amblyomma , including the investigated sequences. A. humerale and A. geayi were grouped into the clades formed by the subgenera Walkeriana and Anastosiella , respectively. By integrating complete sequences, the approach adopted expands the number of comparable characters, reduces biases associated with the use of isolated mitochondrial markers, and contributes to better statistical support for the recovered nodes, resulting in more stable and interpretable phylogenetic topologies. The data and information generated in this study can contribute to future taxonomic and evolutionary research on the genus Amblyomma .

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Pigmented fungi derived from hot and cold deserts ecosystems: taxonomy, genomic and biotechnological approach - Mayanne Karla da Silva; Rubens Correia da Silva; Beatriz Medeiros de Souza Melo; Thiago José Carvalho Cavalcante; Leonardo da Silva Santos; João Gabriel Pereira e Silva; Vannêssa Rodrigues Teles Maia; Monelly da Silva Bernardo; Kelvin da Silva Sousa; Averlane Vieira da Silva; Adeildo Júnior de Oliveira; Aline Cavalcanti de Queiroz; et al. (World Journal of Microbiology and Biotechnology, 2026)

Clinical efficacy and safety of a spray formulation containing carvacrol and eugenol against Rhipicephalus linnaei and Ctenocephalides felis felis in artificially infested dogs - Fernando Rocha Miranda; Isabelle Vilela Bonfim; Anna Julia Bessa Fernandes; Ingrid Lins Raquel de Jesus; Taynara Monsores e Silva; Matheus Eduardo Costa da Silva; Mathias Pittizer da Silva; Gabrielle de Lima Monzato; Clara Rodrigues Dutra; Ygor Henrique da Silva; Brena Gava Guimarães; Diefrey Ribeiro Campos; et al. (Veterinary Parasitology, 2026)

Evaluation of ceramic and polymeric membranes for crossflow microfiltration of coconut water: Filtration performance and composition of the clarified coconut water - José Diogo da Rocha Viana; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Carlos Alberto Kenji Taniguchi; Arthur Claudio Rodrigues de Souza; Fernando Antônio Pinto de Abreu; José Carlos Cunha Petrus; Kirley Marques Canuto (Journal of Food Engineering, 2026)

Hafnium and silicon isotope evidence for multiple unsilicified basaltic sources at the origin of Rhyacian TTG magmas in the Mineiro Belt (Brazil) - Syro Lacerda; Martin Guitreau; Leonardo Gonçalves; Hugo Moreira; Cristiane C. Gonçalves; Stéphany Rodrigues Lopes; Sandro Mauri; Marco Aurélio Pinheiro; Cassiano Costa e Castro; Régis Doucelance (Geochimica et Cosmochimica Acta, 2026)

Disentangling the ecological drivers of woody plant hyperdominance in the Cerrado: A dissociation between abundance and biomass in forest and savanna formations - Hallefy Junio de Souza; Eder Pereira Miguel; José Roberto Rodrigues Pinto; Carlos de Melo e Silva Neto; Mário Lima dos Santos; Renata Dias Françoso (Forest Ecology and Management, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Synthesis and characterization of chitosan-functionalized nanostructured lipid carriers with temozolomide: cytotoxic effects and chromosomal instability in human glioblastoma cells - Helber Alves Negreiros; João Pedro Alves Damaceno do Lago; Victor Alves de Oliveira; Lia Raquel Alves Silva; Ana Carolina Lima de Melo; Igor Gabriel Barbosa de Sousa; Jefferson da Cruz Esteves; Sérgio Eduardo Matos Cazarotti Francisco; Samuel Lemos Paiva; João Pedro Crispim Guerra Rodrigues; Lucas Medeiros Martins Carvalho; Pedro Henricke Oliveira de Souza; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Multiform glioblastoma (GBM) is the most aggressive primary brain tumor, associated with high heterogeneity, treatment resistance, and poor survival. Temozolomide (TMZ), although the main chemotherapeutic agent used, shows limited efficacy due to low solubility, chemical instability, and acquired resistance. In this context, nanostructured systems can enhance their antitumor efficacy. This study aimed to develop and characterize chitosan-functionalized nanostructured lipid carriers loaded with Temozolomide (NLCTQ), as well as to assess their biological activity in human glioblastoma cells (U87-MG). Lipid nanoparticles functionalized with chitosan were prepared by hot emulsification and sonication. Physicochemical characterization included DLS, zeta potential, FTIR, and HPLC for drug quantification and encapsulation efficiency. Biological activity was evaluated in U87-MG cells using the cell viability assay MTT and trypan blue, the comet assay, the spheroid model, fluorescence cell death, and the CBMN assay. The formulation presented a homogeneous nanometric size and positive zeta potential, although with moderate encapsulation efficiency (39%). Biological assays demonstrated that NLCTQ significantly reduced cell viability, overcoming the U87-MG cell line’s resistance to TMZ by achieving cytotoxicity at doses up to 20 times lower than free TMZ. Additionally, NLCTQ promoted the formation of biomarkers of chromosomal instability, such as micronuclei, bridges, and nuclear buds, which may explain the observed cytotoxic effects. Together, the results indicate that TMZ nanoencapsulation in NLCTQ enhances its antitumor efficacy, representing a promising strategy to overcome the limitations of conventional chemotherapy in glioblastoma treatment.

Water Deficit and Salinity Stresses Alone or Simultaneously: How Are Exogenous Salicylic Acid-Mediated Tolerance Mechanisms Enhanced in Young Citrus Plants? - Milton Carriço Sá; Raul Antonio Araújo do Bonfim; Maiara Costa Silva; Vinícius Alves Rodrigues; Laélcio Novato Ribeiro Filho; Gustavo Kawan Almeida Costa; Camila Valentim Silva Sousa; Rosilene Gomes de Souza Pinheiro; Matheus Ferreira Almeida; Natália Deniz Brito; Marcela Ferraz e Silva; Paulo Araquém Ramos Cairo (Journal of Plant Growth Regulation, 2026)
Water deficit and salinity pose significant challenges to the cultivation and distribution of citrus plants ( Citrus sinensis ) worldwide. Although these two types of abiotic stress are harmful throughout the biological cycle, they can become critical for plant survival and establishment in the early development stages. This study aimed to investigate the effects of salicylic acid (SA) foliar application on the physiological and biochemical traits of young citrus plants subjected to water deficit and salinity conditions, either alone or simultaneously. A greenhouse experiment was conducted with seven-month-old citrus plants subjected to four growing conditions - no stress, water deficit (WD), salinity (S), and WD + S - and pre-treated with SA application at 0, 1, 2, and 4 mM. Results showed that water deficit and salinity reduced gas exchange and damaged the photosynthetic apparatus by increasing reactive oxygen species (ROS) levels. Simultaneous stresses caused more photosynthetic pigment degradation and reduced gas exchange than water deficit and salinity stresses alone. The application of 2 mM SA mitigated the adverse effects of stress by improving osmoregulation and enhancing antioxidant enzyme activity and phenolic content. Furthermore, it prevented electrolyte leakage and ROS accumulation, with the intensity of these effects varying depending on the type of stress. SA also improved gas exchange under individual stresses, while increasing water-use efficiency under combined water deficit and salinity. These findings suggest the foliar application of SA as an effective strategy to improve tolerance to water deficit and salinity, whether occurring individually or in combination, in young post-transplanted citrus plants.

Pathogens in the bay: environmental Staphylococcus saprophyticus strains mirror clinical counterparts in virulence, biofilm formation, antimicrobial resistance, pathogenicity, and phage susceptibility - Isabella Monteiro Carvalho; Erica Cristina Soares e Silva; Geovana Lacerda Rodrigues; Natállia Duarte dos Santos; Raienne Vitória da Silva Soares; Monalessa Fábia Pereira; Ciro César Rossi; Marcia Giambiagi-deMarval (Antonie van Leeuwenhoek, 2026)
Staphylococcus saprophyticus is a leading cause of urinary tract infections, yet little is known about its environmental reservoirs and traits outside clinical settings. This study aimed to compare clinical and environmental S. saprophyticus strains isolated from a polluted coastal ecosystem in Brazil, assessing their virulence-associated traits, antimicrobial resistance, biofilm formation, and susceptibility to bacteriophages. Forty strains (20 clinical, 20 environmental) were characterized using GTG 5 -PCR, virulence gene screening, antibiotic susceptibility testing, biofilm assays, exposure to sub-inhibitory concentrations of ciprofloxacin, Tenebrio molitor infection model, and phage activity tests. Genetic fingerprinting and virulence gene profiles revealed a high degree of similarity between environmental and clinical isolates, indicating the presence of shared virulence-associated determinants. Environmental strains exhibited resistance to multiple antibiotics and showed biofilm formation and larval survival patterns comparable to those observed for clinical isolates. Exposure to sub-inhibitory concentrations of ciprofloxacin increased biofilm formation in several strains. Bacteriophage CSF, originally isolated from swine farm effluent, displayed lytic and antibiofilm activity against a substantial proportion of the isolates. These findings highlight the presence of clinically relevant traits among environmental S. saprophyticus strains and underscore the importance of continued microbiological surveillance in anthropized aquatic environments.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Chemical analysis and biological activity of crude extracts obtained from leaves of Passiflora foetida (Subg. Passiflora ) and Passiflora morifolia (Subg. Decaloba) - Ohana Luiza Santos de Oliveira; Oscar Caetano da Silva Neto; Gabriele Rodrigues Conceição; Fábio Alexandre Chinalia; Daniel Pereira Bezerra; Milena Botelho Pereira Soares; Valdenizia Rodrigues Silva; Luciano de Souza Santos; Carla Junqueira Moragas Tellís; João Victor da Silva e Silva; Caroline Conceição da Guarda; Jorge Mauricio David; et al. (Natural Product Research, 2026)

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

River transport of cattle in northern Brazil - a systematic review - Welligton Conceição da Silva; Éder Bruno Rebelo da Silva; Italo Messias Ferreira de Souza; Vanessa Sousa Pinto; Luís Gustavo Paixão Vilela; Carlos Eduardo Lima Sousa; Thiago Nogueira da Silva; Alinne da Silva Souza; João Paulo de Sousa Cunha; Vinicius Costa Gomes de Castro; Raimundo Nonato Colares Camargo-Júnior; Rubens Lima de Andrade; et al. (Tropical Animal Health and Production, 2026)
The river transport of cattle by barges is a common practice in western Pará, where rivers are the main access routes to livestock production, slaughter, and marketing areas. In this context, the long journeys made by boats or ferries adapted for cattle transport can expose animals to conditions of thermal stress, due to the high relative humidity of the region, temperature and humidity fluctuations, and wind speed. This review was conducted through a literature search in the ScienceDirect and PubMed databases. Inclusion criteria were full-text articles written in English and Portuguese that discussed the legal aspects, stress, management, challenges, and prospects of river transport of cattle in northern Brazil. As exclusion criteria, studies that did not align with the study’s objective were disregarded. The PRISMA checklist was used for conducting this review. The region relies on river transport due to road limitations, using rivers as the main logistical routes for moving products. The poor infrastructure of ports and vessels compromises animal welfare and highlights the need for investments to ensure efficiency and competitiveness in the production chain. River transport of cattle in western Para is an important component of Amazon livestock farming, being essential for product distribution and the integrity of the production chain. This activity involves challenges related to animal welfare, associated with adverse environmental factors, stocking density, long travel periods, and the constant movement of vessels. The implementation of good management practices, adequate infrastructure, and continuous monitoring strategies emerges as an effective way to reduce stress and prevent injuries during transport, along with technologies for monitoring and evaluating composite indices.

Cat-transmitted Sporotrichosis: A Clonal Household Outbreak with Atypical Human and Canine Disease Due to Sporothrix brasiliensis - Bruno Balduino Berber-Freitas; Lara Rocha Batista; Bruno Siqueira Prudente; Leonardo Eurípedes Andrade e Silva; Simone Regina Argenton-Perrella; Érica Rivera Coimbra; Ana Beatriz Oliveira de Souza; Larissa Sousa Araújo; Marilia Prior Fuga; Ivonete Helena Rocha; Jamile Ambrósio de Carvalho; Anderson Messias Rodrigues; et al. (Mycopathologia, 2026)
The epidemiology of sporotrichosis, a neglected mycosis caused by Sporothrix species, has shifted in South America from classic sapronosis to urban zoonosis driven by feline transmission of the hypervirulent Sporothrix brasiliensis . However, the fine-scale transmission dynamics of this epidemic, particularly within households, remain poorly understood. Here, we dissect an intrafamilial outbreak in Brazil involving a cat (the index case), a dog, and three humans. High-resolution genotyping using 15 microsatellite markers revealed a clonal transmission event, with isolates from the index cat and human patients being genetically indistinguishable (100% similarity). Multiple bioinformatic analyses, including principal component analysis, minimum spanning tree, and self-organizing maps, corroborated these findings. Strikingly, this outbreak strain produced markedly divergent clinical phenotypes, including Parinaud’s oculoglandular syndrome in an 8-year-old girl, a fixed cutaneous lesion in her 5-year-old brother, and a disseminated maculopapular exanthem in her 28-year-old mother. This clinical pleomorphism from a genetically invariant pathogen unequivocally demonstrates the pivotal role of host factors, such as age, immune response, and inoculation site, in dictating disease manifestation. Furthermore, all outbreak isolates belonged to the MAT1-1 idiomorph, a finding that challenges the paradigm of a monolithic epidemic dominated by MAT1-2 strains and suggests a more complex, polycentric expansion of S. brasiliensis . Overall, this study provides strong evidence of zoonotic transmission and highlights how host determinants, not pathogen variability, shape the clinical diversity of sporotrichosis.

Endophytes induce volatile emission in olive trees with repellent activity against Bactrocera oleae - Ana E. Cunha; Nuno Rodrigues; Pedro Casquero; José A. Pereira; Paula Baptista (Journal of Pest Science, 2026)
The olive fruit fly, Bactrocera oleae (Rossi), is a key pest of the olive tree worldwide. This study explores whether the endophytes Alcaligenes faecalis , Aureobasidium pullulans , Bacillus amyloliquefaciens , and Penicillium commune can trigger the emission of repellent volatile organic compounds (VOCs) in olive trees, targeting B. oleae . Accordingly, olive trees were inoculated with each endophyte or with buffer (control), and after 3 months, both fruits and leaves were collected to perform olfactometer assays and to evaluate VOCs by HS-SPME and GC–MS. Alcaligenes faecalis , A. pullulans , and B. amyloliquefaciens were found to significantly repel B. oleae females, with each treatment inducing a distinct VOC profile. Alcaligenes faecalis and B. amyloliquefaciens were characterized by higher levels of alkenes, including o-cymene and d-limonene, while P. commune and A. pullulans induced the emission of alkanes. Six VOCs were found to be negatively correlated with fly entries in the olfactometer assays, with beta-myrcene being the most prominent, followed by d-limonene, o-cymene, and 5-octadecene (E). These repellent VOCs were positively correlated with each other, indicating that their combined emission may produce synergistic effects, potentially enhancing their repellency. In contrast, 1, 4-hexadiene, 5-methyl-3-(1-methyl ethylidene) was identified as an attractant, showing a strong positive correlation with fly entries, and appeared to be produced through different biosynthetic pathways than the repellent VOCs. Overall, this work identifies three endophytes and a combination of repellent VOCs as promising new strategies for sustainable management of the olive fruit fly.

Conversion of MDF waste into CoCl2-functionalized activated carbon for enhanced phosphate removal from landfill leachate - A. G. dos Santos; L. C. S. Coelho; D. A. Bertuol; M. A. S. Rodrigues; E. H. Tanabe (International Journal of Environmental Science and Technology, 2026)

Correction: Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)

Osteophagy in Ozotoceros bezoarticus: a field observation from the Brazilian Cerrado - Vívian da Silva Braz; Vanderlei Alves do Nascimento Neto; Frederico Gustavo Rodrigues França; Myrella Machado Bernardes; Carlos de Melo e Silva Neto; Thiago Eduardo Pereira Alves; Adriani Hass (acta ethologica, 2026)

A hybrid simulated moving bed/pressure swing adsorption process for methane and nitrogen separation - Rafael O.M. Dias; Alexandre F.P. Ferreira; Alírio E. Rodrigues; Ana M. Ribeiro (Chemical Engineering Journal, 2026)

Reduction of cobalt species on biochar from corn husk waste for NaBH4 hydrolysis - Melany Alejandra Ruiz López; Humberto Vieira Fajardo; André Esteves Nogueira; Guilherme Max Dias Ferreira; Thamiris Ferreira de Souza; Thenner Silva Rodrigues; Felipe Anchieta e Silva; Gabriel Max Dias Ferreira (Biomass and Bioenergy, 2026)

Exploring the Probiotic Potential and Immunomodulatory Capacity of Lactococcus lactis NCDO 2118 Against Bacterial Pathogens and Trypanosoma cruzi - Mariana Oliveira Silva; Malu Mateus Santos Obata; Rafael Obata Trevisan; Chamberttan Souza Desidério; Hugo Felix Perini; Weslley Guimarães Bovi; Isabella de Oliveira Ferrato Sousa; Isabela Sguilla Rotta; Marcela Fernandes da Matta; Julia de Moura Bernardi; Nadine Aparecida de Souza Benedito; Anna Victória Bernandes e Borges; et al. (Probiotics and Antimicrobial Proteins, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

Ischemic preconditioning with active reperfusion does not improve high-intensity intermittent exercise in youth team sport players - Gustavo R. Mota; Izabela A. Santos; Anderson Luiz Rodrigues; Bernardo N. Ide; Tom Citherlet; Jeffer E. Sasaki; Moacir Marocolo (European Journal of Applied Physiology, 2026)
Purpose We investigated whether an active protocol of ischemic preconditioning (IPC-A) would improve high-intensity intermittent exercise performance in youth team sport players. Methods Fifteen male amateur team sport players (15.5 ± 0.5 yrs) attended four different preconditioning sessions before the YoYo Intermittent Recovery Test level 1 (YYIR1) interspersed by seven days in a counterbalanced randomized cross-over design. IPC protocol consisted of three cycles of 5 min occlusion (220 mmHg) and 5 min reperfusion (0 mmHg) in both thighs. SHAM was similar to the IPC protocol, but ‘occlusion’ pressure was set up at 20 mmHg. Active protocols (IPC-A/ SHAM-A) were similar to the IPC/SHAM, but participants exercised (intermittent run) during the ‘reperfusion’ phases instead of resting. Six minutes after the protocol, the participants performed the YYIR1. Results The distance covered in the YYIR1 did not differ ( p = 0.46) among the protocols: IPC (917 ± 204 m) vs. IPC-A (931 ± 211 m) vs. SHAM (968 ± 201 m) vs. SHAM-A (933 ± 204 m). Blood lactate concentration, and mean heart rate did not differ either ( p > 0.05) among the protocols. Conclusions Active ischemic preconditioning involving exercise during reperfusion phase does not improve high-intensity intermittent exercise performance nor alter physiological or perceptual responses in youth team sport players.

Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)
The consumption of vegetables is essential for human health. However, in regions affected by mining activities, this practice may pose serious risks due to potential heavy metal contamination at the soil–plant interface. This study evaluated the phytotoxicity and metal mobility in lettuce cultivated in mine tailing-contaminated soils after the Córrego do Feijão dam failure (Brumadinho, Minas Gerais, Brazil). The increase in soil metal concentrations negatively influenced morphological parameters such as root and shoot length, fresh biomass, germination, chlorophyll content, and the pattern and frequency of stomata on the leaf surface. Translocation factors of Fe, Ni, Mn, Cd, Cu, Pb, and Zn from roots to shoots of lettuce indicated significant risks to human health. In shoots, the concentrations of As, Cd, Pb, and Cu exceeded the maximum permissible limits for human consumption in lettuce and other leafy Asteraceae by up to 407-, 98-, 5,483-, and 28-fold, respectively. These results highlight the urgent need for mitigation, remediation, and protective strategies to safeguard human and animal health in mining regions, particularly where mining, agriculture, and livestock production coexist.

On vertical plasma drift measurements made by a new medium power incoherent scatter radar (MP ISR) mode at the Jicamarca Radio Observatory - Alexander A. Massoud; Anthony A. Abubakar; Fabiano S. Rodrigues; Karim M. Kuyeng; Marcos Inoñán; Danny E. Scipión (Advances in Space Research, 2026)

Machine learning for land use change analysis in environmental protection areas - Mayra Vannessa Lizcano Toledo; Johnnatan Rodrigues de Oliveira; Luis Armando De Oro Arenas; Leopoldo André Dutra Lusquinho Filho; Arthur Pereira dos Santos; Raphael de Vicq Ferreira da Costa; Roberto Wagner Lourenço; Darllan Collins da Cunha e Silva (Environmental Monitoring and Assessment, 2026)
Anthropogenic land use and land cover change (LULCC), combined with ongoing climate variability, poses significant challenges to environmental protection areas (EPAs) by altering ecosystem structure, degrading vegetation integrity, and disrupting local climate regulation. Despite their importance, traditional LULCC approaches often fail to incorporate dynamic environmental drivers, limiting their capacity to represent complex landscape-climate interactions. This study investigates the environmental dynamics of the Guaraqueçaba Environmental Protection Area and evaluates the landscape’s potential for automated classification and prediction of impacts associated with land use change. A multitemporal dataset spanning 15 years (2009–2023) was analyzed, comprising an original set of approximately 30.2 million records of annual time series of precipitation, maximum and minimum temperatures, evapotranspiration, global solar radiation, relative humidity, wind speed, land use and land cover information, and the Normalized Difference Vegetation Index (NDVI). To address class imbalance, a balanced subset of 3.6 million records was used for modeling. Predictive models were developed using multiple linear regression (MLR), k -nearest neighbors (KNN), and random forest (RF), with performance assessed under both imbalanced and balanced data conditions using accuracy, $$R^{2}$$ R 2 , precision, recall, and F1-score metrics. The results indicate pronounced local climate changes, including increasing temperatures in anthropogenically modified areas and altered humidity patterns associated with vegetation loss. Among the evaluated models, RF exhibited the highest predictive performance, achieving accuracies of up to 96% and an R $$^{2}$$ 2 of 88.6%, effectively capturing the nonlinear interactions between LULCC, climate variables, and vegetation dynamics. Precipitation and NDVI emerged as the most influential drivers of LULCC processes. These findings demonstrate the effectiveness of machine learning approaches for identifying environmental degradation trajectories in protected areas and provide a robust framework to support targeted mitigation strategies and policy development applicable to other EPAs facing increasing anthropogenic pressure and climate variability.

Oncology Education in Undergraduate Medical Students: A Cross-Sectional Comparison of Expectations and Perceptions Between First- and Sixth-Year Cohorts - Lincoln Lopes Ferreira; Ariel E Hirsch; Pedro Lucas Alvarez Rodrigues; Maria Eduarda Santos Miranda; Ana Paula Drummond-Lage (Journal of Cancer Education, 2026)
Cancer is projected to become the leading cause of death in Brazil within the next decade. Despite this growing burden, oncology education remains inconsistently structured in undergraduate medical curricula, potentially limiting physicians’ preparedness for cancer care. To compare expectations and perceptions of oncology education between independent cohorts of first- and sixth-year medical students and to assess whether academic stage is independently associated with perceived preparedness and interest in oncology careers. A cross-sectional study was conducted using structured questionnaires administered to first-year ( n = 152) and sixth-year medical students ( n = 100) at a Brazilian institution. Multivariable logistic regression models were used to estimate adjusted odds ratios (ORs) with 95% confidence intervals (CIs), controlling for sex and family history of cancer. Sensitivity analyses were performed using ordinal regression, including all response categories. First-year students reported higher expected preparedness for oncology training, whereas sixth-year students reported lower self-perceived preparedness based on their educational experiences (80.9% vs. 68.0%; p < 0.001). Interest in oncology careers was also higher among first-year students (24.3% vs. 11.0%; p = 0.008). In adjusted analyses, academic stage remained independently associated with perceived preparedness (OR 3.83, 95% CI 1.51–9.73; p = 0.005) and career interest (OR 2.54, 95% CI 1.21–5.34; p = 0.014). First-year students were also more likely to rate key treatment modalities, including chemotherapy, radiotherapy, and immunotherapy, as essential components of undergraduate training. Sensitivity analyses yielded consistent results. Differences between cohorts were observed in expected and self-perceived preparedness, as well as in the perceived importance of oncology-related domains. These findings should be interpreted as reflecting differences in expectations and perceptions rather than changes over time or training.

Low doses of ascorbic acid modulate the effect of chemotherapy agents in sarcoma 180 tumor-bearing mice - Josemar José da Silva Júnior; Leonardo da Rocha Sousa; Victor Alves de Oliveira; Antonio Lima Braga; Ag-Anne Pereira Melo de Meneses; Ricardo Melo de Carvalho; Joedna Cavalcante Pereira; Reyca Rodrigues e Silva; Raí Pablo Sousa de Aguiar; Antonielly Campinho dos Reis; Sérgio Eduardo Matos Cazarotti Francisco; Shamya Gabriella Corrêa Coêlho; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Functional dynamics of fish assemblages in a tropical estuary during different phases of El Niño‒Southern Oscillation - Rayssa Soares da Silva Rodrigues; e André Luiz Machado Pessanha (Marine Environmental Research, 2026)

Effect of pH adjustment on wetting mitigation in textile wastewater treatment by membrane distillation - Mariana E. Rodrigues; Andreia S.F. Farinha; Geert-Jan Witkamp; Johannes Vrouwenvelder; Luca Fortunato (Journal of Water Process Engineering, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Genomic, biological, and chemical studies of Streptomyces sp. LaBMicrA B280 isolated from the rhizosphere of Inga edulis Martius in the Amazon - Rafael de Souza Rodrigues; Antonia Queiroz Lima de Souza; Jania Lilia da Silva Bentes; Kamila Rangel Primo Fernandes; Felipe Moura Araújo da Silva; Maria de Fátima Oliveira Almeida; Rafael Pinto e Souza; Anderson Nogueira Barbosa; Fábio César Sousa Nogueira; Gabriel Reis Alves Carneiro; Ricardo de Melo Katak; Ivanildes dos Santos Bastos; et al. (Antonie van Leeuwenhoek, 2026)
In this study, we investigated the taxonomic identity and biotechnological potential of the actinobacterium Streptomyces sp. LaBMicrA B280, isolated from the rhizosphere of Inga edulis (Mart.). Our approach combined a phylogenomic approach, annotation of metabolic subsystems and biosynthetic gene clusters (BGCs), biological assays to assess antifungal, antimalarial, cytotoxic, and larvicidal activities, classical molecular networking analysis, and characterization of the major compound in the most active fraction (FR3). The digital DNA–DNA hybridization values, using the d2 (GGDC) and d4 (TYGS) formulas, average nucleotide identity, and average amino acid identity ( Streptomyces genus. Our genomic analysis revealed 39 BGCs, including the cluster responsible for pentamycin biosynthesis, 314 metabolic subsystems, and 24 gene categories. In the molecular networking analysis, pentamycin was the only compound identified. Biological assays with fraction FR3 at a concentration of 50 µg/mL showed 96.59% ± 0.03 and 72.39% ± 0.18 inhibition against Plasmodium falciparum strains W2 and 3D7, respectively, as well as 91.45% ± 0.55 cytotoxicity against the HEp-2 cancer cell line. Larvicidal activity assays demonstrated 100% efficacy against Aedes aegypti (FO) at 250 µg/mL after 48 h. Pentamycin, a known antifungal compound, was successfully isolated from the highly active FR3 fraction. These findings highlight that LaBMicrA B280 exhibits a broad biotechnological potential and represents a promising source of important secondary metabolites for future application.

Immune Mediator Profile in the Inflammatory Microenvironment Reveals Potential Biomarkers of Wound Healing in Localized Cutaneous Leishmaniasis - Jaqueline Paulino de Souza; Célia Maria Ferreira-Gontijo; Francislane Ramalho Varella Pereira; Marcela Tavares Caldas Eller; Matheus Figueiredo Garrocho Ottoni-Vieira; Julia Pereira-Martins; Maryana Prates Rodrigues; Joaquim Pedro Brito-de-Sousa; Ariane Soares Nascimento; Maria Nilza Pereira de Brito; Bruno Oliveira Souza e Silva; Thadeu Ramalho da Silva; et al. (Current Tissue Microenvironment Reports, 2026)
Localized cutaneous leishmaniasis (LCL) is the most prevalent form of leishmaniasis, with infection control primarily dependent on cell-mediated immunity. Lesion healing results from a complex interplay among immune cells and soluble mediators. Using Luminex technology, we evaluated circulating and lesion microenvironment immune mediators, including chemokines, cytokines, and growth factors, in patients with LCL and nonspecific dermatitis. A robust proinflammatory response was observed in the lesion microenvironment of LCL patients, characterized by elevated levels of growth factors, important immune mediators potentially involved in tissue repair. Predictive modeling identified FGF, G-CSF, GM-CSF, IL-2, and IL-9 as key immune mediators distinguishing LCL from nonspecific dermatitis. Our results reveal that LCL presents a distinct soluble immune mediator signature from nonspecific dermatitis, exhibiting a set of biomarkers that not only define its immune mediator signature but also signal a possible role in the tissue repair process. Furthermore, we characterized the profile of soluble immune mediators of LCL patients, categorized according to the time evolution lesion. Our analysis revealed a predominance of biomarkers within the lesion microenvironment in patients with recent lesions (< 2 months of evolution). On the other hand, in late lesions patients (> 2 months of evolution), our data showed a predominance of biomarkers in the systemic circulation. Collectively, these findings provide novel insights into the immunopathogenesis of LCL and highlight candidate immune mediators for targeted prognostic evaluation.

Erratum to “A call for CARE in animal behaviour: an holistic ethical research framework” [Animal Behaviour 231 (2026) 123428] - Gal Badihi; Jennifer Taylor-O’Connor; Gabriela Bezerra de Melo Daly; Viola Komeda; Sophia Daoudi-Simison; Evelina D. Rodrigues; Michael M. Webster; Drew M. Altschul; Catherine Hobaiter; Charlotte Wiltshire; Harmonie Klein; Elodie Freymann; et al. (Animal Behaviour, 2026)

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Detection of Brucella spp. in compost-bedding pack barn and its relationship with infections in dairy cows during the transition period - Marcilene Daniel Damasceno; Maysa Serpa Gonçalves; Maria Eduarda de Souza Teixeira Campos; Amanda Carvalho Rosado Ferreira; Dircéia Aparecida Costa Custódio; Eduarda Moraes Magossi Silva; Vivian Aparecida Malta; Alice Gonçalves dos Reis; Bruno Borges Silva; Ana Clara de Serpa Carvalho; Júlia Lima Paz; Pedro Felipe Rodrigues e Oliveira; et al. (Research in Veterinary Science, 2026)

Integrating elemental and total reflection X-ray spectral fingerprints with machine learning for advanced seafood traceability - Nuno M. Rodrigues; Vanessa F. Fonseca; Renato Mamede; Susanne E. Tanner; Bernardo Duarte; Sara Silva (Food Control, 2026)

Rehydrated ground corn silage as alternative to feedlot lambs: feeding behavior and performance - Leandro A. S. da Silva; Cláudia L. S. Lima; Gleidson G. P. de Carvalho; Henry D. R. Alba; Maria L. G. M. L. de Araújo; Cláudia H. da Cruz; Carlindo S. Rodrigues; Dalton H. Pereira; José E. de Freitas Júnior; Manuela S. L. Tosto; Douglas dos S. Pina (Tropical Animal Health and Production, 2026)

Efficient cryopreservation of Antillean manatee skin-derived somatic cells via reduced intracellular cryoprotectant concentration - Luanna Lorenna Vieira Rodrigues; Lhara Ricarliany Medeiros de Oliveira; Yasmin Beatriz França Moura; Yara Letícia Frutuoso e Silva; João Vitor da Silva Viana; Leonardo Vitorino Costa de Aquino; Radan Elvis Matias de Oliveira; Fernanda Loffler Niemeyer Attademo; Fábia Oliveira Luna; Alexsandra Fernandes Pereira (In Vitro Cellular & Developmental Biology - Animal, 2026)

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Comparative genomic analyses reveal key traits for biocontrol and the promotion of plant growth in Paenibacillus strains - Luciano Nascimento de Almeida; Mirelly Jady Fernandes e Silva; Blenda de Freitas Rodrigues Jesuino; Sumaya Martins Tupy; Jorge Henrique Resende Vieira; Gabriela Amaral Xavier; João Paulo Lopes da Rocha; Osiel Silva Gonçalves; Mateus Ferreira Santana (World Journal of Microbiology and Biotechnology, 2026)
Paenibacillus species have emerged as promising candidates for sustainable agriculture due to their functional versatility in plant growth promotion and biocontrol. We performed a comparative genomic analysis of 428 high-quality Paenibacillus genomes to assess their ecological adaptability and biotechnological potential. The analyzed strains originated from diverse environments, reflecting broad ecological distribution. Functional annotation revealed a widespread occurrence of plant growth-promoting traits (PGPTs), including phosphate and potassium solubilization, siderophore biosynthesis, nitrogen fixation, and phytohormone-related compounds. On average, the genomes contained 249 genes associated with biofertilization, 190 with phytohormone production, 97 linked to bioremediation, and around 322 involved in competitive exclusion. The open pan-genome configuration ( b = 0.503) highlights notable genetic plasticity and ongoing gene acquisition. While the core genome was enriched in essential functions, accessory and unique fractions carried genes associated with environmental adaptation and niche specialization. Analysis of mobile genetic elements (MGEs) showed that some PGPT-related genes occur in mobile regions, suggesting horizontal gene transfer contributes to the dissemination of beneficial traits. Diverse BGCs, including those encoding Bacillopaline, Tridecaptin, Fusaricidin B, Paeninodin, and Polymyxin, were identified, many with antimicrobial potential. CAZyme profiling revealed abundant chitinases, supporting pathogen suppression capacity. No virulence factors were detected, and antibiotic resistance genes were rare, underscoring the genus’ low pathogenicity. Altogether, these findings position Paenibacillus as a genetically and functionally diverse group with strong potential as a safe, sustainable resource for developing biofertilizers and biopesticides.

Metabolic profiling of Metternichia macrocalyx and Metternichia principis (Solanaceae) using LC-ESI-Q-TOF-MS/MS data in molecular networking and chemometric analysis - Thiago Araújo de Medeiros Brito; Anauara Lima e Silva; Yasmin Ferreira de Araújo; Natyele Rodrigues Fonseca; Giulia Cavalcanti Ottino; Domingos Benício Oliveira Silva Cardoso; Josean Fechine Tavares; Lucas Silva Abreu; Marcelo Sobral da Silva (Natural Product Research, 2026)

Screening of Brazilian cowpea cultivars for resistance to Meloidogyne incognita and M. javanica - Gerson Luís dos Santos Rodrigues Júnior; Micheline do Amaral Dias; Gabriele Stefanello Manfio; Kaesel Jackson Damasceno e Silva; Juvenil Enrique Cares; Robert Neil Gerard Miller; Jansen Rodrigo Pereira Santos (Crop Protection, 2026)

Biomonitoring of microplastics in the Caribbean Sea with invasive lionfish - Sahara M. Ríos-Bonilla; Jaaziel E. García-Hernandez; Daniel A. Toledo-Rodríguez; Nikolaos V. Schizas; Lisa J. Rodrigues (Marine Pollution Bulletin, 2026)

Greywater use in anaerobic digestion of cattle manure: Advancing biogas yield, energy efficiency, and digestate valorization for environmental sustainability in semi-arid regions - Daniela Silva Gomes Moreira do Valle; Marcélio Alves Teotônio; Jadde Milena Guedes Secundino; Tassia Cristina da Silva; Elisabete Albuquerque dos Santos Benvenuto; Allan Almeida Albuquerque; Bárbara Ribeiro Alves Alencar; Alexandre Nunes da Silva; Sergio Peres; Rejane Rodrigues da Costa e Carvalho; Emmanuel Damilano Dutra; Rômulo Simões Cezar Menezes (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Red light–mediated enhancement of the antifungal activity of Physalis angulata against Candida species - Bianca Borges de Alencar; Maria Laura Faleiros Ribeiro de Melo; Wanderson Zuza Cosme; Matheus Henrique Francisco Dias; Camila Cristina Baccetti Medeiros; Rodrigo Sorrechia; Rosemeire Cristina Linhari Rodrigues Pietro; Fabiano Guimarães Silva; Marcio Luís Andrade e Silva; Wilson Roberto Cunha; Patrícia Mendonça Pauletti; Regina Helena Pires; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Cork stripping alters the seasonal carbon allocation patterns of Quercus suber in a dry year - Clara A. Pinto; Filipe Costa-e-Silva; Alexandra C. Correia; José Graça; Olfa Zarrouk; Teresa S. David; José C. Rodrigues; João S. Pereira; Maria Manuela Chaves; Carla Pinheiro (Forest Ecology and Management, 2026)

Obtaining and characterizing bacuri (Platonia insignis) seed flour: a strategy for valuing fruit co-products from a sustainable food perspective - Simone Kelly Rodrigues Lima; Luiz Brito de Souza Filho; José Otávio Carvalho Sena de Almeida; José Moreira Tavares Neto; Michel Muálem de Moraes Alves; Arkellau Kenned Silva Moura; Antônia Maria das Graças Lopes Citó; Francisco Cardoso Figueiredo; Leandro Josuel da Costa Santos; Liduína Soares de Carvalho Mendes; André Filipe Sousa Loiola; Joyce Lopes Macedo; et al. (Food Chemistry, 2026)

An adsorptive reactor for biomethane purification and production - Joana A. Martins; Alírio E. Rodrigues; Luis M. Madeira (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Metarhizium anisopliae engineering mediated by a CRISPR/Cas9 recyclable system - Maria Letícia de Siqueira Virgílio; Eliane Dias Quintela; Liriel Helen Rodrigues Maciel; Gabriela Souza Silva Goulart; José Francisco Arruda e Silva; Marcio Vinicius de Carvalho Barros Cortes (Folia Microbiologica, 2026)

Chemical composition and acaricidal activity of essential oils from Alpinia zerumbet, Bixa orellana, Mesosphaerum suaveolens and Syzygium cumini against Oligonychus punicae on clonal seedlings of Eucalyptus grandis - Adriele de Castro Ferreira; Rosenya Michely Cintra Filgueiras; Paulo Roberto Ramalho Silva; Izaias Santos Marques; Antonio José Cantanhede Filho; Bruno de Araújo Gomes; Edson Rodrigues Filho; Franciele Costa de Sousa; Eslane Reis Farias Mendes; Helane Cristina De Andrade Rodrigues Severo; Alyne Freire de Melo; Kamilla de Andrade Dutra; et al. (Crop Protection, 2026)

An overview of the contaminant mixtures present in key consumed fish and seafood species along the Portuguese territory - Filipe Costa; Manuel J. Rodrigues; Filipe Martinho; Maria E. Pereira; Miguel A. Pardal; João P. Coelho (Marine Pollution Bulletin, 2026)

A call for CARE in animal behaviour: an holistic ethical research framework - Gal Badihi; Jennifer Taylor-O’Connor; Gabriela Bezerra de Melo Daly; Viola Komeda; Sophia Daoudi-Simison; Evelina D. Rodrigues; Michael M. Webster; Drew M. Altschul; Catherine Hobaiter; Charlotte Wiltshire; Harmonie Klein; Elodie Freymann; et al. (Animal Behaviour, 2026)

Expression pattern of the HIFα-family in equine chorioallantois during pregnancy and placental pathology - Yatta Boakari; Hossam El-Sheikh Ali; Gustavo Henrique Doná Rodrigues Almeida; Kirsten E. Scoggin; Claudia Barbosa Fernandes; Sophia Panelli Marchio; Mats H.T. Troedsson; Ana Claudia Oliveira Carreira (Theriogenology, 2026)

Microglial Inflammatory Response in the Glioblastoma Microenvironment in Preclinical Models - Ana Helena Larangeira Nóbrega; Ana Paula Soares do Prado; Rafael Sampaio Pimentel; Áquila Rodrigues Costa Santos; Rafaela Rodrigues Valerio; Luiza Clemente dos Santos de Souza; Maria Alice de Souza; Patrícia Machado Rodrigues e Silva; Marco Aurélio Martins; Rudimar Luiz Frozza; Andressa Bernardi (Molecular Neurobiology, 2026)

Isotopic niche analysis of sympatric hermit crabs (Decapoda: Anomura) reveals different trends among generalist consumers - G. F. B. Rodrigues; V. E. Costa; A. L. Castilho (Hydrobiologia, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Two species and two karyotypes? Cytogenetic differentiation between Passiflora foetida L. and P. vesicaria L. (Passifloraceae) - Bruna Zirpoli; Arthur Monteiro; Pablo E. Rodriguez; Bruno Leal Viana; Jefferson Rodrigues Maciel; Andrea Pedrosa-Harand; Mariela A. Sader (Systematics and Biodiversity, 2025)

Antinociceptive, anti-inflammatory, and antioxidant effects of a flavonoid-rich phytocomplex from the leaves of Celtis iguanaea (jacq.) Sargent (Cannabaceae) - Dionys de Souza Almeida; Luiza Sousa Honorato; Lorrane Kelle da Silva Moreira; Larissa Córdova Turones; Rúbia Bellard e Silva; Mairon Cesar Coimbra; Laura Jéssica Pereira; Marx Osório Araújo Pereira; James Oluwagbamigbe Fajemiroye; José Realino de Paula; Júlio Onésio Ferreira Melo; José Luis Rodrigues Martins; et al. (Natural Product Research, 2025)

An adsorptive reactor for CO2 capture from flue gas and conversion to CH4–Parametric analysis - Joana A. Martins; Alírio E. Rodrigues; Luis M. Madeira (Fuel, 2025)

Cashew nut protein concentrate as a potential ingredient for the emerging alternative protein industry - Jéssica Silva do Carmo; José Diogo da Rocha Viana; Arthur Claudio Rodrigues de Souza; Kelvi Wilson Evaristo Miranda; Celli Rodrigues Muniz; Lorena Mara Alexandre e Silva; Matheus Dias de Carvalho; Ana Carla Kawazoe Sato; Daniele Maria Alves Teixeira Sá; Wellington da Silva Oliveira; Fernanda Furlan Gonçalves Dias; Ana Paula Dionísio (Food Chemistry, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Impact of silvopastoral shade on thermal stress and conception rates of beef cows in tropical pastures - Amanda Beatriz de Lima Costa; Rafael Henrique Tonissi e Buschinel de Goes; Jefferson Rodrigues Gandra; Gustavo Mafra Fernandes; Gregory Fedri; Lorrayne de Souza Araujo Martins Motta; Antônio Campanha Martinez (Tropical Animal Health and Production, 2025)

Reticular outflow, ruminal dynamics and ingestive behavior of steers in grazing supplemented with Capsicum oleoresin - Igor Moreno Souza Lopes; Juliana Reolon Pereira; Fabiano Ferreira da Silva; Gleidson Giordano Pinto de Carvalho; Carlindo Santos Rodrigues; Murilo Ramos Santiago; Maria Leonor Garcia Melo Lopes de Araújo; Ricardo Diniz Guerra e Silva; Douglas dos Santos Pina; Marcus Vinícius Galvão Loiola; Lara Maria Santos Brant; José Esler de Freitas Júnior (Tropical Animal Health and Production, 2025)

Green infrastructure for urban climate mitigation and adaptation: methods, strategies, and typology selection based on ecosystem services - B. N. Rodrigues; A. L. F. Favoreti; V. E. Molina Júnior; C. M. Silva; F. B. Canteras (International Journal of Environmental Science and Technology, 2025)

Highlighting the marine fungi Cunninghamella echinulata-9A5 as bioemulsifier for treating tannery leather residue - Mariana Bueno do Nascimento; Wanderson Zuza Cosme; Heber Eduardo Andrada; Kátia Roberta Prieto de Oliveira; Maria Isabela da Silva Figueiredo; Vanessa Mendes Rego; Marcos Antonio Soares; Rodrigo Sorrechia; Sarah Santana Sanchez; Rosemeire Cristina Linhari Rodrigue Pietro; Gustavo Muniz Dias; Marcio Luís Andrade e Silva; et al. (Brazilian Journal of Microbiology, 2025)

Correction: Bridging the Gap: Addressing the Disparity between Expectations and Practical Training in Oncology during Medical School - Lincoln Lopes Ferreira; Ariel E. Hirsch; Pedro Lucas Alvarez Rodrigues; Maria Eduarda Santos Miranda; Ana Paula Drummond-Lage (Journal of Cancer Education, 2025)

Technology roadmap of low-carbon hydrogen: Trends for risk management strategies - Danielle Rodrigues de Moraes; Laene Oliveira Soares; Vanessa de Almeida Guimarães; Daniel Cerqueira Lima e Penalva Santos; Ronney Arismel Mancebo Boloy (Process Safety and Environmental Protection, 2025)

Compliance with mandatory conservation policies among rural properties in the Eastern Amazon - Tatiane Camila Martins Silva; Luiz Edinelson Cardoso e Cardoso; Renato Augusto Soares Rodrigues; José Maria Cardoso da Silva; Ima Célia Guimarães Vieira (Land Use Policy, 2025)

Ultrasound-enhanced bioaccessibility and pharmacological activities of curcumin in inclusion complexes - Matheus X. Oliveira; Irisvan S. Ribeiro; Francisca Vanessa C. Canafístula; Stephanie Ferreira M. Muniz; Lorena Maria F. Sampaio; Alyne Rodrigues A. Nobre; Fábio Oliveira S. Ribeiro; Raí E. Silva; Jessica Maria T. Souza; Erick Joniher B. Torres; José Delano Barreto M. Filho; Ana J. Araújo; et al. (Food Chemistry, 2025)

Metabolomic profiles and antioxidant intake in female soccer players: a cross-sectional study - M. M. S. Gouveia; M. B. A. Nascimento; A. C. Crispim; E. R. da Rocha; M. P. P. Santos; E. S. Bento; T. M. Aquino; P. Balikian; N. A. Rodrigues; T. Ataide-Silva; G. G. de Araujo; F. A. B. Sousa (European Journal of Applied Physiology, 2025)

Behavioral, regenerative, and reproductive responses of Girardia tigrina to imidacloprid exposure - Aline Arantes de Oliveira; Thays Millena Alves Pedroso; Andreia C. M. Rodrigues; Daniela de Melo e Silva; Renato Almeida Sarmento; Suzana Maria Loures de Oliveira Marcionílio; Hellem Victoria Ribeiro dos Santos; Aline Silvestre Pereira Dornelas; Althiéris de Souza Saraiva (Ecotoxicology, 2025)

Understanding the effects of hematite and brucite additions on fresh- and hardened-state properties of metakaolin-based geopolymer cements - Jie Ren; Mohammad G. Matar; Naiara Rodrigues Tonin; Christine Pu; Claire E. White; Wil V. Srubar (Applied Clay Science, 2025)

Response of sugarcane under water deficit to amorphous silica doses: biomass, C:N:P homeostasis, and nutritional efficiency - Fabiano Simplicio Bezerra; Renato de Mello Prado; Gelza Carliane Marques Teixeira; Deyvielen Maria Ramos Alves; Steffany Daiana da Costa Berto; Wellinton Julio Ferreira Gonçalves; Lucas Yago de Carvalho Leal; Martha Katharinne Silva Souza Paulino; José Alfredo Nunes; Cícero Aparecido Ferreira Araújo; Ênio Farias de França e Silva; Clístenes Williams Araújo do Nascimento; et al. (Plant and Soil, 2025)

Recent Advances in Subcritical Water Pretreatment of Lignocellulosic Biomass: Integrating Modern Extraction Techniques for Biorefinery Applications - Carolina E. Demaman Oro; Jéssica Mulinari; Carlos Rafael Silva de Oliveira; Afonso Henrique da Silva Júnior; Éllen Francine Rodrigues; Rogério Marcos Dallago; Marcus V. Tres (BioEnergy Research, 2025)

Bridging the Gap: Addressing the Disparity Between Expectations and Practical Training in Oncology During Medical School - Lincoln Lopes Ferreira; Ariel E. Hirsch; Pedro Lucas Alvarez Rodrigues; Maria Eduarda Santos Miranda; Ana Paula Drummond-Lage (Journal of Cancer Education, 2025)

Probability of sub-hourly extreme precipitation events in Recife, Brazil - A.F. Fonseca; D.T. Rodrigues; W.A. Gonçalves; JB Cabral Júnior; D.O. de Souza; C.M. Santos e Silva (Journal of South American Earth Sciences, 2025)

Luteal features and serum concentrations of progesterone and hCG in dairy goats submitted to estrus induction followed by intrauterine or intramuscular hCG administration - Alice L. Martins; Luana R. Côrtes; Juliana N.D. Rodrigues; Paulo Sergio C. Rangel; Ana Lucia R. e S. Maia; Felipe Z. Brandão; Luiz Gustavo B. Siqueira; Bruna W. de Freitas; Jeferson F. Fonseca (Domestic Animal Endocrinology, 2025)

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Molecularly imprinted polymer integrated disposable pipette extraction method for rapid quantification of melatonin and metabolites in breast milk - Lucas Santos Machado; Naiara Raica Lopes de Oliveira; Laysa Luana Silva de Macedo; Steffany de Souza Santos; Flávio Olímpio Sanches Neto; Flávia Silva e Oliveira; Flaviana Vely Mendonca Vieira; Jussara Valente Roque; Andrea Rodrigues Chaves (Analytica Chimica Acta, 2025)

Fluoride Content and pH in Yerba Mate Infusions: A Study of South American Varieties - Lídia Audrey Rocha Valadas; Constanza E. Fernández; Francisco Josimar Girão Júnior; Mary Anne Medeiros Bandeira; Angela Argentieri; Edilson Martins Rodrigues Neto; Thereza Cristina Farias Botelho Dantas; Aldo Squassi (Biological Trace Element Research, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Analysis of the implementation of green-blue infrastructure for optimising recharge in coastal aquifers - Leandro Rodrigues Capítulo; Silvina C. Carretero; Samanta M. Anguiano; Carlos E. Dalto; Eduardo E. Kruse (Groundwater for Sustainable Development, 2025)

Propolis and geopropolis from stingless bees as a source of bioactive compounds with antioxidant and antimicrobial action: A review - Jonilson de Melo e Silva; Fernanda Wariss Figueiredo Bezerra; Ingryd Rodrigues Martins; Gustavo Guadagnucci Fontanari; Johnatt Allan Rocha de Oliveira; Luiza Helena da Silva Martins (Food Research International, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Systemic Infection Caused by Mycobacterium fortuitum Following Aortic Valve Transplantation—Employing Combined Molecular Techniques for Accurate Species Identification - Max Roberto Batista de Araújo; Débora Marques da Silveira e Santos; Jailan da Silva Sousa; Gerson Fernandes do Prado; Diogo Luiz de Carvalho Castro; Moacir Soares Dias Júnior; Hugo Felix Perini; Cíntia Minafra; Siomar de Castro Soares; Evandro Bento Rodrigues; Luan Freitas Lana; Letícia Aparecida Caldeira Gonçalves; et al. (Current Microbiology, 2025)

Rhabdomyosarcomas in dystrophin-deficient Sprague Dawley rats - M. Rodrigues; E. Reyes-Gomez; L. Tiret; P. Lafuste; F. Relaix (Journal of Comparative Pathology, 2025)

Effect of the genotype and environment interaction on body weight traits in Nelore cattle (Bos indicus) - Raimundo Nonato Colares Camargo-Júnior; Cláudio Vieira de Araújo; Caio de Souza Teixeira; Simone Inoe de Araújo; Raysildo Barbosa Lôbo; Lílian Roberta Matimoto Nakabashi; Letícia M. Mendes de Castro; Flávio Luiz Menezes; André Guimarães Maciel e Silva; José Ribamar Felipe Marques; Welligton Conceição da Silva; Marco Aurélio Lopes Della Flora; et al. (Tropical Animal Health and Production, 2025)

Humic acid from vermicompost effectively regulates the redox status and mitigates the progression of experimental periodontitis - Hugo Giordano Tavares; Patrícia Ribeiro Orlando; Ramona Ramalho de Souza Pereira; Caíque Olegário Diniz e Magalhães; Gabriela Silva; Alice dos Santos Nunes Ferreira; Bruna Caroline Chaves Garcia; Karen Rodrigues Lima; Etel Rocha Vieira; Leonardo Barros Dobbss; Marco Fabrício Dias-Peixoto; Alan Rodrigues Teixeira Machado; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Relationship between estrus and reactivity on the reproductive performance of beef cows - Francisco A.R. Catalano; Luiz E. Kozicki; Isis V. Rodrigues; Ruan R. Daros (Applied Animal Behaviour Science, 2025)

Understanding the impact of different post-digestion enzymatic inhibition methods and storage conditions on standardized gastrointestinal model (INFOGEST): A case study of Pleurotus ostreatus mushroom biomass - Helena Araújo-Rodrigues; Ana Sofia Salsinha; Ezequiel R. Coscueta; João Bettencourt Relvas; Freni K. Tavaria; Manuela E. Pintado (Food Research International, 2025)

The role of the P2X7 receptor in inactivated SARS-CoV-2-induced lung injury - N. C. Carvalho-Barbosa; Fabiana Cristina-Rodrigues; Jairo R. Temerozo; Thiago M. L. Souza; Andre L. Gouvêa; Claudio A. Canetti; Eleonora Kurtenbach; Dumith Chequer Bou-Habib; Claudia F. Benjamim; Christina M. Takiya; Luiz E. B. Savio; Robson Coutinho-Silva (Purinergic Signalling, 2025)

Purines and purinergic receptors in primary tumors of the central nervous system - Adinei Abadio Soares; Helamã Moraes dos Santos; Keyllor Nunes Domann; Natália Pratis Rocha Alves; Bernardo Ribeiro Böhm; Carolina Maliska Haack; Kailane Paula Pretto; Emily Sanini Guimarães; Guilherme Francisquini Rocha; Igor Rodrigues de Paula; Lucas Efraim de Alcântara Guimarães; Harlan Cleyton de Ávila Pessoa; et al. (Purinergic Signalling, 2025)

Biochar amendment as a sustainable alternative to KCl application and its effects on sugarcane physiology and metabolome - Pablo Aislan Freitas e Silva; Mariana Vitória Silvério Alves; Júlia Cristina Amâncio Vieira; Elizabeth Luciana Marinho Miguel; Wisley Moreira Farias; Adriana Barboza Alves; Arthur César Mônico; Elisângela Aparecida da Silva; João Alberto Fischer Filho; Gustavo Henrique Gravatim Costa; Leandro de Souza Pinheiro; Lúcia Pinheiro Santos Pimenta; et al. (Plant Physiology Reports, 2025)

Unveiling the Genomic Landscape of Understudied Salmonella enterica Serovars from Poultry and Human: Implications for Food Safety - Valdinete P. Benevides; Mauro M. S. Saraiva; Viviane A. Ferreira; Michelli Inácio G. Funnicelli; Lucas B. Rodrigues Alves; Adriana M. Almeida; Henrik Christensen; John E. Olsen; Angelo Berchieri Junior (Current Microbiology, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Socioenvironmental impacts of the Belo Monte hydroelectric power plant as revealed by Indigenous and ribeirinho monitoring - Josiel Jacinto Pereira Juruna; Raimundo da Cruz e Silva; Orcylene Barbosa dos Reis; Amildon Moura Assunção; Anderson Sampaio da Silva; Helio Bezerra da Silva; Jailson Jacinto Pereira Juruna; Josimary Abreu Nunes; Micaele Souza Santos Kleme; Paulo Passos Ferreira; Ronald Txakui Viana da Silva Juruna; Rosilene Sousa dos Santos; et al. (Conservation Biology, 2025)
Hydroelectric dams, once seen as clean and renewable energy sources, have been the subject of extensive research, particularly concerning their socioenvironmental impacts. The Belo Monte hydroelectric power plant (HPP) relies on the operation of 2 dams that divert water from a 130‐km stretch of the Xingu River to generate energy. The dam has disrupted the seasonal flooding cycle (flood pulse) along the Volta Grande do Xingu (VGX) and created a reduced discharge condition analogous to a prolonged and extreme dry season in the watershed. Before the Belo Monte HPP, local communities relied on the highly diverse and abundant fish assemblage supported by seasonal flooding of the ecosystem. Local VGX residents sought partnerships and established the Independent Territorial Environmental Monitoring Program (MATI‐VGX). Through this program, locals monitored fish spawning sites and fishing dynamics. This monitoring complemented and quantified local communities’ perceptions about the environmental impacts caused by the Belo Monte HPP. The HPP was associated with a water discharge shortage that critically undermined the river's capacity to sustain vital ecosystem processes that support local people's lives. Drastic transformations of traditional lifestyles, shifts in fishing practices, and a significant decline in fishing yield occurred that jeopardized food sovereignty and security. The Belo Monte HPP environmental licensing process ignored local ecological knowledge and the vital links among the river's flood pulse, the aquatic and seasonally flooded ecosystems, and the traditional lifestyles of VGX residents. To ensure the ecological sustainability of the VGX, the Belo Monte HPP operation needs to change to support key spawning areas, maintain water discharge, avoid short‐term water fluctuations, and emulate natural interannual discharge variability to mitigate flood pulse disruption. Local ecological knowledge should never be ignored in projects where local communities are the most affected. These communities should be central in decision‐making regarding socioenvironmental impact assessment, mitigation, and monitoring.

Baccharis dracunculifolia and Brazilian green propolis extracts improve “two-hit” liver injury in MICE - Ana Caroline dos Santos; Tauani Caroline Santos França; Thiago Farias de Queiroz e Silva; Debora Munhoz Rodrigues; Sarah Freygang Mendes Pilati; Jairo Kenupp Bastos; Luísa Mota da Silva (Natural Product Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Low temperature production of FAMEs from waste cooking oil with ball-milling synthesized mixed lithium salts derived from spent bleaching clay - Wen-jie Cong; Cristiano E. Rodrigues Reis; Jianguo Zhang; Jie Zhang; Xiaoya Luo (Fuel, 2025)

Multivariate analysis to evaluate the storage time of cocoa honey (Theobroma cacao L.) processed by pasteurization and high intensity ultrasound - Manuela B. Nascimento; Bruno N. Paulino; Suzana B. Silva; Kathleen R. Deegan; Joseane C.G. Alencar; Adriana C.R. Ferreira; Frederico M. Rodrigues; Paulo R.R. Mesquita; Sergio E. Soares (Food Chemistry, 2025)

Do behavioral attitudes of livestock farmers in Cameroon influence the adoption of insect-based feed? An application of the theory of planned behavior - Ruth T. Nembu; Boris D. Soh Wenda; Hervé K. Mube; Hervé W. Napi; Shaphan Y. Chia; Sali A. Ndindeng; Rodrigue B. Kamga; Dorothy E. Fon (Food and Humanity, 2025)

Efficacy of a formulation of chlorfenvinphos and dichlorvos on Rhipicephalus microplus in vivo test in Bahia, Brazil - Aline Kelly Araújo Costa Velame Ferreira; Wagner Carvalho e Silva Neto; Igor de Castro Oliveira; Maria Clara Bastos Rodrigues; Ângela Cristina de Oliveira Lima; Tiago Velame Ferreira; Carolina Carneiro de Matos; Ana Karina da Silva Cavalcante; Lorendane Millena de Carvalho; Wendell Marcelo de Souza Perinotto (Tropical Animal Health and Production, 2025)

Self-assembly and 3D Bioprinting of Neurospheres and Evaluation of Caffeine and Photobiomodulation Effects in an Alzheimer’s Disease In Vitro Model - Geisa Rodrigues Salles; Alessandro E. C. Granato; Fernanda Tibolla Viero; Cristina Pacheco-Soares; Sérgio T. Ferreira; Marimelia Porcionatto; Henning Ulrich (Stem Cell Reviews and Reports, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Correction to: Potential of Marine Strains of Pseudoalteromonas to Improve Resistance of Juvenile Sea Bass to Pathogens and Limit Biofilm Development - A. Rahmani; L. Parizadeh; M. Baud; Y. Francois; A. Bazire; S. Rodrigues; Y. Fleury; H. Cuny; E. Debosse; J. Cabon; L. Louboutin; L. Bellec; et al. (Probiotics and Antimicrobial Proteins, 2025)

Potential of Marine Strains of Pseudoalteromonas to Improve Resistance of Juvenile Sea Bass to Pathogens and Limit Biofilm Development - A. Rahmani; L. Parizadeh; M. Baud; Y. Francois; A. Bazire; S. Rodrigues; Y. Fleury; H. Cuny; E. Debosse; J. Cabon; L. Louboutin; L. Bellec; et al. (Probiotics and Antimicrobial Proteins, 2025)

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Toxicity of essential oils on Callosobruchus maculatus (Fabr., 1775) in grains of Vigna unguiculata - Ozael David Valério da Silva; Paulo Roberto Ramalho Silva; Leticia Rodrigues da Silva; Rodrigo de Carvalho Brito; Kamilla de Andrade Dutra; Daniela Maria do Amaral Ferraz Navarro; Douglas Rafael e Silva Barbosa; Solange Maria de França (Journal of Plant Diseases and Protection, 2025)

Detection of an Alphacoronavirus in a Brazilian Bat (Molossus sp.) - C. L. Molina; M. M. Magalhães; A. C. Rodrigues; S. A. Taniwaki; S. O. de Souza Silva; G. A. König; P. E. Brandão (Journal of Molecular Evolution, 2025)

Retraction notice to “The exposure in ovo of embryos belonging to Amazonian turtle species Podocnemis expansa (Testudines) to commercial glyphosate and fipronil formulations impairs their growth and changes their skeletal development” [Sci. Total Environ. 842 (2022) 156709] - Juliana dos Santos Mendonça; Líria Queiroz Luz Hirano; André Luiz Quagliatto Santos; Daniela de Melo e Silva; Carolina de Castro Pereira; Matheus Santos Costa; Phâmella Neres de Lima; Amanda Pereira da Costa Araújo; Guilherme Malafaia; Isabela Sayuri Ambrósio; Lais de Moura Bife Castilho; Allyson Leandro Rodrigues dos Santos; et al. (Science of The Total Environment, 2025)

Relationship between attributes extracted from carcass image: Prediction of carcass tissue characteristics and meat quality of hair sheep lambs - Carolina Sarmanho Freitas; Alinne Andrade Pereira; Samanta do Nascimento Monteiro; Gabriel Xavier Serrão; Jonas Carneiro Araújo; Manuela Paula de Mesquita Nunes; Hugo Andrey Santos dos Santos; Thomaz Cyro Guimarães de Carvalho Rodrigues; Jamile Andréa Rodrigues da Silva; Luciara Celi Chaves Daher; André Guimarães Maciel e Silva; Welligton Conceição da Silva; et al. (Small Ruminant Research, 2025)

Analysis of germination and vigor of cashew seeds for germplasm conservation by NMR and uPLC-qTOF-MS/MS based metabolomics - Elenilson Godoy Alves Filho; João Ravelly Alves de Queirós; Oriel Herrera Bonilla; Hilton César Rodrigues Magalhães; Edy Sousa de Brito; Paulo Riceli Vasconcelos Ribeiro; Kirley Marques Canuto; Lorena Mara Alexandre e Silva; Ana Cecília Ribeiro de Castro (Food Research International, 2025)

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Assessing the predicted impact of single amino acid substitutions in calmodulin for CAGI6 challenges - Paola Turina; Giuditta Dal Cortivo; Carlos A. Enriquez Sandoval; Emil Alexov; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Piero Fariselli; Lukas Folkman; Akash Kamandula; Panagiotis Katsonis; et al. (Human Genetics, 2025)

Detection of Rocahepevirus ratti in Bivalve Mollusks from São Luís Island, Maranhão, Brazil: A Potential Transmission Route of an Emerging Zoonotic Pathogen? - Andreza Soriano Figueiredo; Isabella Rodrigues Negreiros; Aldaleia do Nascimento e Silva; Caroline Roberta Soares Salgado; Natália Lourenço dos Santos; Marcelo Alves Pinto; Alcina Vieira de Carvalho Neta; José Paulo Gagliardi Leite; Carina Pacheco Cantelli (Food and Environmental Virology, 2025)

Particle‐Associated Bacterioplankton Communities Across the Red Sea - Larissa Frühe; Shannon G. Klein; Carlos Angulo‐Preckler; Anastasiia Martynova; Taiba Alamoudi; Jacqueline V. Alva García; Silvia Arossa; Jessica Breavington; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Anieka J. Parry; et al. (Environmental Microbiology, 2025)
Pelagic particle‐associated bacterioplankton play crucial roles in marine ecosystems, influencing biogeochemical cycling and ecosystem functioning. However, their diversity, composition, and dynamics remain poorly understood, particularly in unique environments such as the Red Sea. In this study, we employed eDNA metabarcoding to comprehensively characterise bacterioplankton communities associated with pelagic particles in a three‐dimensional assessment spanning depths from the surface to a depth of 2300 m along the full length of the eastern Red Sea within the exclusive economic zone of the Kingdom of Saudi Arabia. Our results reveal a diverse assemblage of taxa, with Pseudomonadota, Cyanobacteriota, and Planctomycetota being the dominant phyla. We identified pronounced spatial variability in community composition among five major Red Sea geographical regions, with a third of all amplicon sequence variants being unique to the Southern Red Sea in contrast to a relatively homogenous distribution along the water column depth gradient. Our findings contribute to a deeper understanding of microbial ecology in the Red Sea and provide valuable insights into the factors governing pelagic particle‐associated bacterioplankton communities in this basin.

Contextualizing the Upper Paleolithic of the Armenian Highlands: New data from Solak-1, central Armenia - Tanner Z. Kovach; Artur Petrosyan; Keith N. Wilkinson; Yannick Raczynski-Henk; Kathleen Rodrigues; Ellery Frahm; Emily Beverly; Jayson P. Gill; Jennifer E. Sherriff; Boris Gasparyan; Hayk G. Avetisyan; Artak V. Gnuni; et al. (Journal of Human Evolution, 2025)

Development of polyols analogous to neopentyl glycol and trimethylolpropane for the production of oleic acid-based biolubricants - Denise Ramos Moreira; Michael Worman; Elano Nery Ferreira; Paulo Roberto Campos Flexa Ribeiro Filho; Larissa Morais Ribeiro da Silva; Tathilene Bezerra Mota Gomes Arruda; Francisco Eduardo Arruda Rodrigues; Francisco Murilo Tavares de Luna; César Liberato Petzhold; Martin E. Maier; Nágila Maria Pontes Silva Ricardo (Fuel, 2025)

Pollution affects even oceanic marine protected areas in Southwestern Atlantic - Thayná J. Mello; Cybelle M. Longhini; Bruno Mattos Silva Wanderley; Cesar Alexandro da Silva; Bethânia Dal'Col Lehrback; Fábio Cavalca Bom; Renato Rodrigues Neto; Fabian Sá; Edson A. Vieira; Vladmir E. Costa; Guilherme O. Longo (Environmental Pollution, 2025)

Comparative effects of Serendipita indica and a mix of arbuscular mycorrhizal fungi on the growth, photosynthetic capacity, and proteomics of Schinus terebinthifolius Raddi - Amanda A. Bertolazi; Lucas Z. Passamani; Sávio B. de Souza; Weverton P. Rodrigues; Eliemar Campostrini; Vitor B. Pinto; Vanildo Silveira; Carlos E. de Rezende; Cristina Cruz; Elke J. B. N. Cardoso; Alessandro Coutinho Ramos (Planta, 2025)

Laboratory and physiological aspects of substitute metazoan models for in vivo pharmacotoxicological analysis - Paulo Michel Pinheiro Ferreira; Carla Lorena Silva Ramos; José Ivo Araújo Beserra Filho; Micaely Lorrana Pereira Conceição; Mateus Lima Almeida; Débora Caroline do Nascimento Rodrigues; Jhonatas Cley Santos Porto; João Marcelo de Castro e Sousa; Ana Paula Peron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

An automated technique and decision support system for lightning early warning - M. A. Alves; B. A. S. Oliveira; D. B. S. Ferreira; A. P. P. Santos; W. F. S. Maia; W. S. Soares; F. P. Silvestrow; L. F. M. Rodrigues; E. L. Daher; O. Pinto (International Journal of Environmental Science and Technology, 2025)

Therapeutic efficacy of brown propolis from Araucaria sp. in modulating rheumatoid arthritis - Poliana Marques Pereira; Silvio de Almeida-Junior; Naomi Nalini de Melo Taveira; Eveline Maria de Melo; Mario Ferreira Conceição Santos; Lilian Cristina Gomes do Nascimento; Marcela Aldrovani Rodrigues; Jennyfer A. Aldana-Mejía; Marcio Luís Andrade e Silva; Sérgio Ricardo Ambrósio; Jairo Kenupp Bastos; Samir A. Ross; et al. (Inflammopharmacology, 2025)

Impact of Drilling Fluids on Borehole Hydraulic Conductivity in Geotechnical Investigations - F. Schnaid; B. A. Rodrigues; D. E. Lourenço; G. M. A. do Patrocínio; S. Maghous; J. L. dos Santos; M. L. P. Alves; R. Fonseca; V. B. de Araújo (Geotechnical and Geological Engineering, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

In vivo anthelmintic activity of hydroethanolic extract of Piper cubeba fruits in sheep naturally infected with gastrointestinal nematodes - Clara de Araújo Sanchez; Juliana Alencar Gonçalves; Márcio Luís Andrade e Silva; Maria Gabriela Fontanetti Rodrigues; Fernanda Amorim Santos; Rosangela da Silva de Laurentiz; Ricardo Velludo Gomes de Soutello (Veterinary Parasitology, 2025)

Warmer air temperatures predicted to result in wetland drying in the Upper Columbia River Valley, British Columbia, Canada - Italo Sampaio Rodrigues; Christopher Hopkinson; Laura Chasmer; Ryan J. MacDonald; Suzanne E. Bayley (Science of The Total Environment, 2025)

Evaluation of dried blood spots for serological surveys of myxoma and rabbit hemorrhagic disease viruses in their wild reservoir - Joana Ferreira-e-Silva; Saúl Jiménez-Ruiz; Marisa Rodrigues; Emídio Santos; Sabrina Castro-Scholten; Vitor Lizana; Alba Martí-Marco; Tereza Almeida; Ana M. Lopes; Joana Abrantes; Juan Bárcena; Esther Blanco; et al. (Preventive Veterinary Medicine, 2025)

Granular anaerobic membrane bioreactor coupled hybrid forward osmosis − membrane distillation module for organic matter, nutrient and bisphenol A removal: Integrated assessment of performance, cost, toxicity, and risks - Carolina Rodrigues dos Santos; Guilherme Otávio Rosa e Silva; Ane Alice Dias Araújo; Thamiris Gualberto Serafim; Guilherme Pinheiro Drumond; Vera Lúcia dos Santos; Luyara de Almeida Fernandes; Juliana Calabria de Araújo; Gemima Santos Arcanjo; Lucilaine Valéria de Souza Santos; Míriam Cristina Santos Amaral (Chemical Engineering Journal, 2025)

Exogenous systemin peptide treatment in olive alters Bactrocera oleae oviposition preference - Luiza Sánchez; Ana E. Cunha; Nuno Rodrigues; José Alberto Pereira; Paula Baptista (Journal of Pest Science, 2025)
The olive fruit fly, Bactrocera oleae (Rossi), is a key pest of the olive crop, whose control relies mostly on the use of insecticides. Plant peptides may represent a more environmentally-friendly tool to manage olive fly, due to their recognized role to activate and/or prime plant defence responses against pests. In this work, behavioural experiments (no-choice and two-choice) and analysis of volatile compounds were carried out to evaluate the impact of the exogenous application of the peptide systemin to olive tree on olive fly infestation, and to elucidate its mode of action to prime plant defence. The treatment of olive branches with 10 nM systemin showed to confer protection against olive fly, by reducing significantly the ovipositions (up to 3.0-fold) and the number of infested fruits (up to 2.9-fold) when compared to non-treated branches. This protective effect was even detected in neighbouring non-treated branches, suggesting the ability of systemin to trigger plant-to-plant communication. The deterrent activity of the primed olives was associated with the emission of the volatiles 2-ethyl-1-hexanol, 4-tert-butylcyclohexyl acetate and 1, 2, 3-trimethyl-benzene, which were negatively correlated with oviposition and fly infestation. Systemin has also showed to trigger the biosynthesis of specific volatiles (esters) in olives in response to fly attacks. Overall, the observed protection conferred by systemin against olive fly is likely due to the emission of specific volatiles that can act as a defence and/or as signalling molecules to upregulate the plant defence response. Thus, systemin represents a novel and useful tool to manage olive fruit fly.

Basic and translational research in rare diseases in low- and middle-income countries: challenges and solutions - Graziella Rodrigues; Edina Poletto; Filippo Pinto e Vairo; Guilherme Baldo (Journal of Community Genetics, 2024)

Airborne DNA: State of the art – Established methods and missing pieces in the molecular genetic detection of airborne microorganisms, viruses and plant particles - C.-E. Pogner; C. Antunes; G.P. Apangu; N. Bruffaerts; S. Celenk; A. Cristofori; N. González Roldán; A. Grinn-Gofroń; B. Lara; M. Lika; D. Magyar; M. Martinez-Bracero; et al. (Science of The Total Environment, 2024)

Forecasting the impact of marine heat waves on farmed bivalves Nodipecten nodosus and Magallana gigas - Roberta Rodrigues das Chagas Pereira; Renan Ribeiro e Silva; Vinicius Peruzzi de Oliveira; Jean Louis Valentin (Regional Studies in Marine Science, 2024)

A multicommuted system using bacterial cellulose for urease immobilization and copper (II)-MOF colorimetric sensor for urea spectrophotometric determination in milk - Julyana C. Rodrigues; Caio S. Bezerra; Lidiane M.A. Lima; Danielle D. Neves; Ana Paula S. Paim; Wagner E. Silva; André F. Lavorante (Food Chemistry, 2024)

Taxonomy, systematics and conservation of the highly threatened and endemic Mexican genus Tridimeris (Annonaceae) - Andrés Ernesto Ortiz-Rodriguez; Francis J. Nge; Carlos Rodrigues-Vaz; Vincent Soulé; George E. Schatz; María Fernanda Martínez-Velarde; Leopoldo Hurtado-Reveles; Moises Rangel-Olguin; Thomas L. P. Couvreur (Plant Systematics and Evolution, 2024)
Tridimeris is the only genus of Annonaceae endemic to Mexico, and since its description more than 150 years ago, the genus has been largely ignored. Here, based on herbarium specimens and a comprehensive phylogenomic study involving hundreds of nuclear markers, the first taxonomic revision of the genus Tridimeris (Annonaceae, Malmeioideae, subtribe Sapranthinae) is presented. Ten species are recognized, six of which are newly described here. All the species are exclusively found in Mexico's most humid forests, particularly in the montane cloud forest and the tropical rainforest. The genus Tridimeris is morphologically distinguished from other neotropical genera of the Annonaceae by its leaves with pocket domatia present in the axils of the secondary veins, by its dimerous flowers (two sepals and four petals), basally fused sepals with ciliated margins, by a reduced number of carpels per flower (1–5) and by its large and fleshy fruits (monocarps) with numerous seeds. A highly resolved phylogenetic hypothesis provides strong support for the relationships among Tridimeris species, forming two well-supported clades. Consequently, two new sections are proposed, namely Tridimeris sect. Tridimeris and Tridimeris sect. Zoque . A detailed description of the morphology of the genus is presented, including the description of the pollen, domatia and its phylogenetic relationships. Taxonomic treatments of the species include synonyms, geographic and ecological notes, comparisons with similar species and a preliminary assessment of their conservation status. All species of the genus are potentially threatened with extinction and eight are assessed as Critically Endangered, which makes it the most threatened lineage of Mexican trees. This study emphasizes the importance of scientific collections as invaluable sources of data for current taxonomic revisions and conservation. It is a formal invitation to preserve and support the basic scientific research.

Investigating cryopreservation techniques for maintaining morphology and in vitro viability of cartilage and skin from Spix’s yellow-toothed cavies (Galea spixii Wagler, 1831) for conservation through biobanks - Samara Lima Olindo; Leonardo Vitorino Costa de Aquino; Yasmin Beatriz França Moura; Yara Letícia Frutuoso e Silva; Ana Lívia Rocha Rodrigues; Vinicius Dantas da Silva; Alexsandra Fernandes Pereira (Journal of Molecular Histology, 2024)

Dietary supplementation of mineral nanoparticles for channel catfish (Ictalurus punctatus) - Vitor F. Silva; José Luiz P. Mouriño; Maurício L. Martins; Pedro L. P. F. Carvalho; Edgar D. Rodrigues; Delbert M. Gatlin; Matt J. Griffin; Caitlin E. Older; Fernando Y. Yamamoto (Fish Physiology and Biochemistry, 2024)

Polymyxin resistance in Enterobacter cloacae complex in Brazil: phenotypic and molecular characterization - Bianca Santos da Costa; Renata Stavracakis Peixoto; Orlando Carlos da Conceição Neto; Leilane da Silva Pontes; Thamirys Rachel Tavares e Oliveira; Camila Bastos Tavares Teixeira; Ivson Cassiano de Oliveira Santos; Melise Chaves Silveira; Daiana Cristina Silva Rodrigues; Bruno Rocha Pribul; Cláudio Marcos Rocha-de-Souza; Ana Paula D.’Alincourt Carvalho-Assef (Brazilian Journal of Microbiology, 2024)

Effects of supplementation frequency on nutritional performance and metabolism of cattle fed low-quality tropical forage - Tadeu E. da Silva; Cristhiane V.R. de Oliveira; Aline N. Rodrigues; Málber N.N. Palma; Larissa F. Camacho; Luciana N. Rennó; Marcia O. Franco; Edenio Detmann (Animal Feed Science and Technology, 2024)

Chlorantraniliprole mediating the survival and behavior of adults of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in tomato - Matheus Rodrigues Martins; Ana Flávia Soares Nascimento; Maria Elisa de Sena Fernandes; Jairo Tronto; Luciano Ferreira da Fonseca; Ryan Fernando Silva e Silva; Flávio Lemes Fernandes (International Journal of Tropical Insect Science, 2024)

Water level regime variation is a crucial driver for taxonomic, functional, and phylogenetic diversity in seasonally flooded tropical forests - Fernanda Moreira Gianasi; Vinícius de Andrade Maia; Aline Meyer Oliveira; Patrícia Vieira Pompeu; Cléber Rodrigo de Souza; Camila Laís Farrapo; André Maciel da Silva-Sene; Fernanda de Oliveira; Thiago Magalhães Meireles; Ana Lívia de Carvalho Rodrigues; Denise Moura Madeira; Felipe Carvalho Araújo; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

Contribution to the Iberian thermomediterranean oak woods (Spain, Portugal): the importance of their teaching for the training of experts in environmental management - Cano E.; Piñar Fuentes J.C.; Cano Ortiz A.; Quinto Canas R.; Rodrigues Meireles C.; Mauro R.; Pinto Gomes C.J.; Spampinato G.; Musarella C. M. (Plant Biosystems, 2024)

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Holistic evaluation of the environmental impacts of shipping in the sensitive region of Ria de Aveiro - A. Monteiro; V. Rodrigues; A. Picado; J.M. Dias; N. Abrantes; A. Ré; M. Rosa; M. Russo; A. Barreirinha; M. Potiris; M. Aghito; R. Hänninen; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pennsylvanian epicontinental sea dynamics in Western Gondwana: Stratigraphic, petrographic, and C, O, and Sr isotopic insights from the Itaituba Formation, Amazonas Basin - Maria D. Traslaviña-Bueno; Juliana C. Marques; Afonso C. Nogueira; Pedro A. Silva; Juan S. Gomez-Neita; Amanda G. Rodrigues; André A. Martins; Paulo A. Souza; Ana K. Scomazzon; Marcia E. Longhim (Journal of South American Earth Sciences, 2024)

Biohydrogen production from wastewater: Production technologies, environmental and economic aspects - Guilherme Otávio Rosa e Silva; Thais Girardi Carpanez; Carolina Rodrigues Dos Santos; Giovanni Souza Casella; Victor Rezende Moreira; Eduardo Coutinho de Paula; Míriam Cristina Santos Amaral (Journal of Environmental Chemical Engineering, 2024)

First climatology of F-region UHF echoes observed by the AMISR-14 system at the Jicamarca radio observatory and comparison with the climatology of VHF echoes observed by the collocated JULIA radar - Alexander A. Massoud; Fabiano S. Rodrigues; Jonas Sousasantos; Marco A. Milla; Danny E. Scipion; Joab M. Apaza; Karim M. Kuyeng; Carlos Padin (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Ultrasound-assisted extraction of anthocyanins from grape pomace using acidified water: Assessing total monomeric anthocyanin and specific anthocyanin contents - Betina Louise Angioletti Decker; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Edy Sousa de Brito; Fabiano André Narciso Fernandes; Thatyane Vidal Fonteles; Sueli Rodrigues (Food Research International, 2024)

Ecotoxicological study of seven pharmaceutically active compounds: Mixture effects and environmental risk assessment - Carolina Rodrigues dos Santos; Guilherme Otávio Rosa e Silva; Camila de Figueiredo Valias; Lucilaine Valéria de Souza Santos; Míriam Cristina Santos Amaral (Aquatic Toxicology, 2024)

Analysis of environmental variables and deforestation in the amazon using logistical regression models - Helder J. F. da Silva; Weber A. Gonçalves; Bergson G. Bezerra; Cláudio M. Santos e Silva; Cristiano P. de Oliveira; Jório B. Cabral Júnior; Daniele T. Rodrigues; Fabrício D. S. Silva (Environmental Monitoring and Assessment, 2024)

Sonification of electronic dynamical systems: Spectral characteristics and sound evaluation using EEG features - G. Acosta Martínez; E. Guevara; E. S. Kolosovas-Machuca; P. G. Rodrigues; D. C. Soriano; E. Tristán Hernández; L. J. Ontañón-García (Cognitive Neurodynamics, 2024)

P01-23 Optimization of predictive liver toxicity modeling based on the drug-induced cholestasis index - A. Drees; V. Nassiri; A. Tabernilla Garcia; J. Serroyen; E. Gustin; B. dos Santos Rodrigues; D.M. Moss; A. De Smedt; M. Vinken; F. Van Goethem; J. Sanz-Serrano (Toxicology Letters, 2024)

Allelopathic effects of cyanotoxins on the physiological responses of Chlorella vulgaris - Maria Virgínia da Conceição Albuquerque; Railson de Oliveira Ramos; Maria Célia Cavalcante de Paula e Silva; Roberta Milena Moura Rodrigues; Valderi Duarte Leite; Wilton Silva Lopes (Toxicon, 2024)

Environmental exposure to metal(loid)s and hypertensive disorders of pregnancy: A systematic review - Nayra Carla de Melo; Priscilla Cristovam Sampaio e Souza; Rejane Correa Marques; José Vicente Elias Bernardi; Wanderley Rodrigues Bastos; Mônica Pereira Lima Cunha (Environmental Research, 2024)

Atmospheric and oceanic mechanisms in precipitation in March 2018 in Ceará, Brazil - Bruno Dias Rodrigues; Cleiton da Silva Silveira; Francisco das Chagas Vasconcelos Júnior; Francisco Agustinho de Brito Neto; Iago Alvarenga e Silva; Meiry Sayuri Sakamoto; Eduardo Sávio Passos Rodrigues Martins (Theoretical and Applied Climatology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Intake, digestibility, serum metabolites, and growth performance of male feedlot lambs fed different fat sources - Henry D.R. Alba; José E. de Freitas; Laudí C. Leite; José A.G. Azevêdo; Stefanie A. Santos; Douglas dos S. Pina; Luis G.A. Cirne; Carlindo S. Rodrigues; Manuela S.L. Tosto; Silvia C. Bento; Amanda B. Grimaldi; Gleidson G.P. de Carvalho (Livestock Science, 2024)

The thermal equation of state of xenon: Implications for noble gas incorporation in serpentine minerals and their transport to depth - A.D. Rosa; F. Zecchi; P. Condamine; M.A. Bouhifd; J.E.F.S. Rodrigues; E. Mijit; T. Irifune; O. Mathon; G. Garbarino; M. Mezouar; A. Dewaele; N. Ishimatsu (Geochimica et Cosmochimica Acta, 2024)

Diurnal cycle of precipitation in Brazil - Cláudio Moisés Santos e Silva; Daniele Tôrres Rodrigues; Felipe Medeiros; Aléxia Monteiro Valentim; Paula Andressa Alves de Araújo; Joicy da Silva Pinto; Pedro Rodrigues Mutti; Keila Rêgo Mendes; Bergson Guedes Bezerra; Cristiano Prestrelo de Oliveira; Weber Andrade Gonçalves (Theoretical and Applied Climatology, 2024)

Emerging Cases of Cat-Transmitted Sporotrichosis Driven by Sporothrix brasiliensis in Northeast Brazil - Pollyanne Raysa Fernandes de Oliveira; Jamile Ambrósio de Carvalho; Taizi Rodrigues Costa; Bruno Pajeú e Silva; Gabriela Gonçalves da Silva; Anderson Messias Rodrigues; Rinaldo Aparecido Mota (Mycopathologia, 2024)

Depth, hard coral, and turf cover as predictors of micro-scale spatial distribution of fishes in a subtropical rocky reef - Thiago E. Rodrigues; Vinícius J. Giglio; Fernando Z. Gibran; Fernanda A. Rolim; Leonardo M. Neves; Guilherme Henrique Pereira-Filho; Gustavo Shintate; Gabriel R. S. Souza; Domingos Garrone-Neto; Fabio S. Motta (Environmental Biology of Fishes, 2024)

A novel tool for modeling the near- and far-field dispersion of brine effluent from desalination plants - Silvano Porto Pereira; Melissa Fontenelle Rodrigues; Paulo Cesar Colonna Rosman; Patrícia Rosman; Tobias Bleninger; Iran Eduardo Lima Neto; Carlos E. P. Teixeira; Iván Sola; José Luis Sánchez Lizaso (Frontiers in Marine Science, 2024)
Regardless of the specific technology adopted, the use of desalination to produce fresh water from seawater results in a discharge of brine effluent containing a high concentration of salts and other desalination by-products that must be dealt with appropriately. Until now, this effluent has most commonly been discharged into the sea through a submarine outfall. Computational tools are used to simulate the behavior of these brine discharges to minimize their impact on the marine environment. Environmental assessments of desalination plants that are made using these tools can include consideration of the rates of effluent production and flow, diffuser configurations, marine conditions (e.g., currents, tides, salinity, temperature), and the proximity of plants to environmentally significant areas. Computational tools can also assist in the design of programs for monitoring the surroundings of brine disposal points. In this study, we developed a new tool for modeling brine discharges from submarine outfalls based on an adaptation of a near-field mathematical model coupled with a Lagrangian model. This new model was specifically designed for application to negatively buoyant effluent discharges. The near-field dilution results that were obtained for various current velocities and different diffuser vertical inclinations using this tool were compared with those obtained using a reference tool (Visual Plumes), considering four different desalination plants. Excellent correlation and a mean absolute percentage error lower than 10% were obtained between the two sets of results along with good reproducibility. Additionally, the existence of an integrated wave propagation model in the simulation software allowed the analysis of changes in the brine plume direction produced by waves formed far from the outfall area. Using the new model, it was possible to evaluate how the diffuser configuration affected the performance of the diffuser line, and the saline plume generated by the combined Lagrangian and near-field model realistically reproduced the behavior of a submarine brine outfall. This combined model is potentially applicable to a range of other situations, including studies that aim to minimize the environmental impact of desalination plants based on considerations of outfall locations and optimization of the diffuser configuration.

Timed-artificial insemination protocols for Bos indicus beef heifers: Evaluation of protocol length and variations in prostaglandin F2α treatments - Rodrigo L.O.R. Alves; Lucas O.e Silva; Mateus A.da Silva; Carlos E.C. Consentini; José R.S. Gonçalves; Leonardo de F. e Melo; Marcelo B. Rodrigues; Roberto Sartori (Theriogenology, 2024)

Machine learning regression algorithms for predicting muscle, bone, carcass fat and commercial cuts in hairless lambs - Samanta do Nascimento Monteiro; Alinne Andrade Pereira; Carolina Sarmanho Freitas; Gabriel Xavier Serrão; Marco Antônio Paula de Sousa; Alyne Cristina Sodré Lima; Luciara Celi da Silva Chaves Daher; Thomaz Cyro Guimarães de Carvalho Rodrigues; Welligton Conceição da Silva; Éder Bruno Rebelo da Silva; André Guimarães Maciel e Silva; Andréia Santana Bezerra da Silva; et al. (Small Ruminant Research, 2024)

Nitrogen efficiency indices for sustainable sweet potato production in tropical environments - Adalton M. Fernandes; Patricio Sandaña; Rogério P. Soratto; Nathalia P. Ribeiro; Fabricio E. Rodrigues; Ítala T. Guimarães (Field Crops Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Cytotoxic screening of plants from the Brazilian Atlantic Forest has led to the identification of Casearia arborea and Sorocea hilarii as sources of antitumor compounds - L. A. Rodrigues; A. A. Almeida; A. P. Agrizii; N. Pacheco; B. C. R. Carvalho; A. C. Zanatta; M. Kohlhoff; C. M. M. E. Torres; G. C. Bressan; J. P. V. Leite (Natural Product Research, 2024)

Solar thermo-photocatalytic methanation using a bifunctional RuO2:TiO2/Z13X photocatalyst/adsorbent material for efficient CO2 capture and conversion - Larissa O. Paulista; Alexandre F.P. Ferreira; Alírio E. Rodrigues; Ramiro J.E. Martins; Rui A.R. Boaventura; Vítor J.P. Vilar; Tânia F.C.V. Silva (Journal of Environmental Chemical Engineering, 2024)

Texture prediction of natural soils in the Brazilian Amazon through proximal sensors - Quésia Sá Pavão; Paula Godinho Ribeiro; Gutierre Pereira Maciel; Sérgio Henrique Godinho Silva; Suzana Romeiro Araújo; Antonio Rodrigues Fernandes; José Alexandre Melo Demattê; Pedro Walfir Martins e Souza Filho; Silvio Junio Ramos (Geoderma Regional, 2024)

Physical exercise as a modulator of the purinergic system in the control of sarcopenia in individuals with chronic kidney disease on hemodialysis - Débora Tavares de Resende e Silva; Matheus Ribeiro Bizuti; Natan Rodrigues de Oliveira; Lucas Zannini Medeiros Lima; Victória Galletti dos Santos Arraes; Ana Carolina Gonçalves Zietz; Carolina Zin; Guilherme Vinício de Sousa Silva; Josiano Guilherme Puhle; Fabiana Brum Haag (Purinergic Signalling, 2024)

A densely sampled molecular phylogeny of Tachigali (Leguminosae), an evolutionarily successful lineage of neotropical ant-housing canopy trees - Isau Huamantupa-Chuquimaco; Vitor Hugo Maia; Haroldo Cavalcante de Lima; Maristerra Rodrigues Lemes; Cristiane Snak; Bernarda Gregório; Sérgio Ricardo S. Cardoso; Luciano Paganucci de Queiroz; Charles E. Zartman; Gwilym P. Lewis; Euan K. James; Kyle G. Dexter; et al. (Brazilian Journal of Botany, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Two decades of clear-cutting threats in the Brazilian Amazonian protected areas around the Jirau, Santo Antônio, and Belo Monte large dams - Silvia Sayuri Mandai; Evandro Albiach Branco; Evandro Mateus Moretto; Jocilene Dantas Barros; Guilherme Prado Alves; Renata Utsunomiya; Gustavo Felipe Balué Arcoverde; Cyro Assahira; Caroline C. Arantes; Guilherme de Sousa Lobo; Miquéias Freitas Calvi; Carolina Rodrigues da Costa Doria; et al. (Journal of Environmental Management, 2024)

Plant gums in Pickering emulsions: A review of sources, properties, applications, and future perspectives - Asma Sharkawy; Alírio E. Rodrigues (Carbohydrate Polymers, 2024)

Evolution of wind speed observed in Brazil between 1961 and 2020 - Gizelly Cardoso Lima; Daniele Tôrres Rodrigues; Cláudio Moisés Santos E Silva; Patrícia Catarine de Sousa Costa (International Journal of Climatology, 2024)
The study's main objective was to analyse daily wind speed data in Brazil collected on‐site from 1961 to 2020 and assess changes in two 30‐year climatological normals, denoted as P1 and P2. Data were sourced from 54 INMET‐managed meteorological stations, with missing data filled using the bootstrap expectation maximization algorithm. Imputation performance was evaluated, and results suggested that the 10% imputed level was most reliable, showing low RMSE values (below 0.5), SD values near 1, and r values exceeding 0.93. This method proved suitable for reconstructing historical wind speed data in Brazil. The analysis included the application of the Mann–Kendall test to detect linear trends and Sen's slope test to quantify trend intensity, both at a 5% significance level. Positive trends during P2 were observed in the Amazon basin and Brazil's semiarid region, while negative trends increased along the coast and in the Southeast region. Average wind speeds during P1 were higher than in P2. Comparing the two climatological normals revealed significant positive trends in some regions during P2, with an increase in average monthly variation of up to 0.85 m·s −1 . The average slopes of significant trends were −1 and 1 m·s −1 ·decade −1 for all periods. The results indicated high wind magnitudes, with maximum power density of 778.08 W·m −2 for the NEB region, 170.90 W·m −2 for the SEB region and 401.67 W·m −2 for the SUB, making these regions promising for future wind power projects. These findings have the potential to enhance the optimization of renewable wind energy generation in Brazil.

β-cyclodextrin versus hydroxypropyl-β-cyclodextrin: is inclusion complexation a suitable alternative to improve the properties of hop-derived β-acids? - Tarsila Rodrigues Arruda; Rafael Resende Assis Silva; Clara Suprani Marques; Allan Robledo Fialho e Moraes; Patrícia Campos Bernardes; Taíla Veloso de Oliveira; Sukarno Olavo de Oliveira; Peter Muranyi; Nilda de Fátima Ferreira Soares (Food Hydrocolloids, 2024)

The vicariant role of Caribbean formation in driving speciation in American loliginid squids: the case of Doryteuthis pealeii (Lesueur 1821) - João Bráullio Luna Sales; Frank E. Anderson; Bianca Lima Paiva; Yasmim T. C. Cunha; Alan Érik Souza Rodrigues; Yrlene Ferreira; Luis Fernando S. Rodrigues-Filho; Paul W. Shaw; Manuel Haimovici; Unai Markaida; Jonathan S. Ready; Iracilda Sampaio (Marine Biology, 2024)

Effectiveness of photo-ozone therapy against equine Pythium insidiosum - V.S. Rodrigues; L.A.C. Trevisan; B.S. Cintra; R.H. Pires; A.B. Ribeiro; D.C. Tavares; E. Oberhaus; J.C. Ferreira (Journal of Equine Veterinary Science, 2024)

Degradation in soil of active cellulose acetate and zein blend films incorporated with different plasticizers and garlic essential oil - Clara Suprani Marques; Rafael Resende Assis Silva; Tarsila Rodrigues Arruda; Taíla Veloso de Oliveira; Allan Robledo Fialho e Moraes; Sukarno Olavo Ferreira; Nathália Ramos de Melo; Marali Vilela Dias; Maria Cristina Dantas Vanetti; Nilda de Fátima Ferreira Soares (Food Packaging and Shelf Life, 2024)

Modeling sugarcane development and growth within ECOSMOS biophysical model - Michel Anderson Almeida Colmanetti; Santiago Vianna Cuadra; Rubens Augusto Camargo Lamparelli; Osvaldo Machado Rodrigues Cabral; Daniel de Castro Victoria; José Eduardo Boffino de Almeida Monteiro; Helber Custódio de Freitas; Marcelo Valadares Galdos; Anderson Carlos Marafon; Aderson Soares de Andrade Junior; Sergio Delmar dos Anjos e Silva; Vinicius Bof Buffon; et al. (European Journal of Agronomy, 2024)

Spatiotemporal variability in human thermal comfort perception in open-air spaces: application to the state of Minas Gerais, Brazil - Lucas Rodrigues Oliveira; Tadayuki Yanagi Junior; Gabriel Araújo e Silva Ferraz; Sílvia de Nazaré Monteiro Yanagi; Marcelo Bahuti (International Journal of Biometeorology, 2024)

RETRACTED: Using structural equation modeling to assess the genotoxic and mutagenic effects of heavy metal contamination in the freshwater ecosystems: A study involving Oreochromis niloticus in an urban river - Jordany Gomes da Silva; Cristiano Aparecido Chagas; Talita Giselly dos Santos Souza; Marlyete Chagas de Araújo; Lívia Caroline Alexandre de Araújo; Andr'e Maurício Melo Santos; Rafael Artur de Queiroz Cavalcanti de Sá; Rayanna Barroso de Oliveira Alves; Rosner Henrique Alves Rodrigues; Hernande Pereira da Silva; Guilherme Malafaia; Ranilson de Souza Bezerra; et al. (Science of The Total Environment, 2024)

Degradation of diazinon by dielectric barrier discharge plasma - Francisco E. Rodrigues Júnior; Fabiano A.N. Fernandes (Journal of Environmental Chemical Engineering, 2024)

Rainfall and rain pulse role on energy, water vapor and CO2 exchanges in a tropical semiarid environment - Cláudio M. Santos e Silva; Bergson G. Bezerra; Keila R. Mendes; Pedro R. Mutti; Daniele Tôrres Rodrigues; Gabriel Brito Costa; Pablo Eli Soares de Oliveira; Jean Reis; Thiago V. Marques; Rosaria Rodrigues Ferreira; Suany Campos; Tarsila M. Ramos; et al. (Agricultural and Forest Meteorology, 2024)

Meta-analysis of carbon stocks and biodiversity outcomes across Brazilian restored biomes - Catarina Jakovac; Katarzyna A. Korys; Aline F. Rodrigues; Amanda Ronix; Fernanda Tubenchlak; Lara M. Monteiro; Luisa Lemgruber; Herlle Souza Santos; Maiara Mendes; André B. Junqueira; Renato Crouzeilles; Veronica Maioli; et al. (Science of The Total Environment, 2024)

Biomarkers of oxidative stress in an estuarine catfish species caught near a port complex on the Brazilian Amazon coast - Gustavo Henrique Rodrigues Vale de Macedo; Jonatas da Silva Castro; Wanda Batista de Jesus; Hetty Salvino Torres; Lina Clara Gayoso e Almendra Ibiapina Moreno; Rayssa Guimarães Rosa; Raimunda Nonata Fortes Carvalho Neta; Débora Batista Pinheiro Sousa (Regional Studies in Marine Science, 2024)

Beach ridge sequence evolution of Punta Verde, northern coast of the San Matías Gulf, Argentina - José Carlos Rodrigues Nunes; Eduardo Puhl; Salvador Aliotta; Elírio E. Toldo; Paula Nogueira Machado Schffer; Cristiano Fick; Francisco Pinheiro Lima-Filho; João Andrade dos Reis Junior; Gilberto Silveira dos Santos; Carla Annes Barros; Felipe Rafael Secco da Silva; Cristian Valenti Schenk (Journal of South American Earth Sciences, 2024)

Mineral chemistry in apatite from heavy mineral concentrate samples as a prospecting tool for carbonatites in the Angico dos Dias region, BA/PI border, Brazil - Douglas Almeida Silveira; Paola Ferreira Barbosa; Cassiano Costa e Castro; Guilherme Ferreira da Silva; Joseneusa Brilhante Rodrigues (Journal of Geochemical Exploration, 2024)

Climate-growth relation and isotopic △13carbon responses of field-grown Pinus caribaea var. hondurensis and Pinus taeda to nutrient availability - Deborah Rodrigues de Souza Santos; Carlos de Melo e Silva-Neto; Cecilia Pereira Theodoro Chotti; Wagner Wilson Ávila Bombardelli; Rafael Battisti; Mario Tomazello-Filho; José Lavres (Forest Ecology and Management, 2024)

Experimental and Theoretical Investigation of the Effect of Cellulose Nanowhiskers on the Pb(II) Adsorption by Superabsorbent Hydrogel Nanocomposites - André R. Fajardo; Robson S. Oliboni; Carlos E. C. de Magalhães; Maria G. M. Chaves; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2024)

Effects of feeding mycotoxin-contaminated diets and the use of an adsorbent on the intake, digestibility, rumen fermentation, nitrogen balance and physiological parameters in the blood of Nellore steers - Luis Henrique C. Batista; Gustavo R. Siqueira; Luiz F. Costa e Silva; Anne Koontz; Yury T. Granja-Salcedo; Igor M. Ferreira; Iorrano A. Cidrini; Karla A. Oliveira; Amanda Caroliny M. de Queiroz; Aline N. Rodrigues; Flávio D. de Resende (Animal Feed Science and Technology, 2024)

Evaluation of the effect of sample suspension concentration and viral load on the outcome of the rabies tissue culture infection test - Tatiane de Cassia Pardo de Souza; Gilmara de Sousa e Silva; Willian de Oliveira Fahl; Adriana Candido Rodrigues; Karen Miyuki Asano; Karin Corrêa Scheffer; Enio Mori; Amanda Siena; Keila Iamamoto (Archives of Virology, 2024)

Semen quality of Nellore and Angus bulls classified by fertility indices and relations with field fertility in fixed-time artificial insemination - Camile Sanches Silva; Eliane Vianna da Costa-e-Silva; Margot Alves Nunes Dode; Andrielle Thainar Mendes Cunha; Wagner Rodrigues Garcia; Breno Fernandes Barreto Sampaio; Juliana Correa Borges Silva; Francisco Eduardo Machado Vaz; Karl Kerns; Peter Sutovsky; Eriklis Nogueira (Theriogenology, 2023)

Natural radioactivity in mineral phosphate fertilizers and its impacts on human health: an overview - Camila Rodrigues e Silva; Fabiana Monteiro de Oliveira (Environmental Science and Pollution Research, 2023)

Microplastics distribution in river side bars: The combined effects of water level and wind intensity - Nicolás A. Garello; Martín C.M. Blettler; Luis A. Espínola; Stephane Rodrigues; Guido N. Rimondino; Karl M. Wantzen; Ana Pia Rabuffetti; Pierre Girard; Fabio E. Malanca (Science of The Total Environment, 2023)

Towards sustainable conservation and domestication of Balanites aegyptiaca L. (Zygophyllaceae) in Africa: progress and challenges - Ahmat A. Chérif; Juliano S.H. Houndonougbo; Rodrigue Idohou; Sylvanus Mensah; Akomian F. Azihou; Carolle Avocèvou-Ayisso; Achille E. Assogbadjo; Brice Sinsin (Journal of Arid Environments, 2023)

Microencapsulation of Limosilactobacillus reuteri (DSM 23878) for application in infant formula: Heat resistance and bacterial viability during long-time storage - Mariana Alves Gragnani Vido; Izabela Dutra Alvim; Gabriel Vinderola; Maria Isabel Berto; Patricia Blumer Zacarchenco Rodrigues de Sá; Cristian Mauricio Barreto Pinilla; Adriana Torres Silva e Alves (Food Research International, 2023)

Ultrasonic pre-treatment to enhance drying of potentially probiotic guava (Psidium guajava): Impact on drying kinetics, Lacticaseibacillus rhamnosus GG viability, and functional quality - Daniele Juliana Rodrigues Gonçalves; Nataly de Almeida Costa; Maria José do Amaral e Paiva; Vanessa Caroline de Oliveira; Nicole Marina Almeida Maia; Isabela Soares Magalhães; Larissa Lorrane Rodrigues Borges; Paulo César Stringheta; Eliane Mauricio Furtado Martins; Érica Nascif Rufino Vieira; Meliza Lindsay Rojas; Bruno Ricardo de Castro Leite Júnior (Food Research International, 2023)

Chitosan with modified porosity and crosslinked with genipin: A dynamic system structurally characterized - Elí Emanuel Esparza-Flores; Larissa Bertoldo Siquiera; Fernanda Dias Cardoso; Tania Haas Costa; Edilson Valmir Benvenutti; Iliana E. Medina-Ramírez; Mercedes Perullini; Patricio R. Santagapita; Rafael C. Rodrigues; Plinho F. Hertz (Food Hydrocolloids, 2023)

Pseudo-ternary chromatographic separation of dihydroxyacetone from the glycerol oxidation byproducts on a simulated moving bed cascade - Pedro M. Walgode; Rui P.V. Faria; Alírio E. Rodrigues (Chemical Engineering Journal, 2023)

A cyclic sorption-reaction process for continuous synthetic methane production from flue gas and green hydrogen - Joana A. Martins; Vanessa F.D. Martins; Carlos V. Miguel; Alírio E. Rodrigues; Luis M. Madeira (Chemical Engineering Journal, 2023)

Utilization of Rosuvastatin and Endogenous Biomarkers in Evaluating the Impact of Ritlecitinib on BCRP, OATP1B1, and OAT3 Transporter Activity - Yeamin Huh; Anna Plotka; Hua Wei; Julia Kaplan; Nancy Raha; Justin Towner; Vivek S. Purohit; Martin E. Dowty; Robert Wolk; Manoli Vourvahis; Amanda King-Ahmad; Sumathy Mathialagan; et al. (Pharmaceutical Research, 2023)
Purpose Ritlecitinib, an inhibitor of Janus kinase 3 and tyrosine kinase expressed in hepatocellular carcinoma family kinases, is in development for inflammatory diseases. This study assessed the impact of ritlecitinib on drug transporters using a probe drug and endogenous biomarkers. Methods In vitro transporter-mediated substrate uptake and inhibition by ritlecitinib and its major metabolite were evaluated. Subsequently, a clinical drug interaction study was conducted in 12 healthy adult participants to assess the effect of ritlecitinib on pharmacokinetics of rosuvastatin, a substrate of breast cancer resistance protein (BCRP), organic anion transporting polypeptide 1B1 (OATP1B1), and organic anion transporter 3 (OAT3). Plasma concentrations of coproporphyrin I (CP-I) and pyridoxic acid (PDA) were assessed as endogenous biomarkers for OATP1B1 and OAT1/3 function, respectively. Results In vitro studies suggested that ritlecitinib can potentially inhibit BCRP, OATP1B1 and OAT1/3 based on regulatory cutoffs. In the subsequent clinical study, coadministration of ritlecitinib decreased rosuvastatin plasma exposure area under the curve from time 0 to infinity (AUC inf ) by ~ 13% and maximum concentration (C max ) by ~ 27% relative to rosuvastatin administered alone. Renal clearance was comparable in the absence and presence of ritlecitinib coadministration. PK parameters of AUC inf and C max for CP-I and PDA were also similar regardless of ritlecitinib coadministration. Conclusion Ritlecitinib does not inhibit BCRP, OATP1B1, and OAT3 and is unlikely to cause a clinically relevant interaction through these transporters. Furthermore, our findings add to the body of evidence supporting the utility of CP-I and PDA as endogenous biomarkers for assessment of OATP1B1 and OAT1/3 transporter activity.

Effects of chemotherapeutic drugs on the antioxidant capacity of human erythroleukemia cells with MDR phenotype - Maiara Bernardes Marques; Filipe Reis Teodoro Andrade; Estela Fernandes e Silva; Bruno Rodrigues Oliveira; Daniela Volcan Almeida; Ana Paula de Souza Votto; Luis Fernando Marins (Molecular and Cellular Biochemistry, 2023)

P16-06: High-content imaging of human hepatic spheroids for studying compounds with cholestatic liability - B. dos Santos Rodrigues; X. Cendoya Garmendia; M. Steemans; E. Gustin; F. Van Goethem; M. Vinken (Toxicology Letters, 2023)

Architecture of Shelly beach ridges in a sheltered beach environment in Punta Perdices beach, San Antonio bay, Argentina - Paula Nogueira Machado Schffer; Elírio E. Toldo Junior; José Carlos Rodrigues Nunes; Cristiano Fick; Francisco Pinheiro Lima-Filho; Salvador Aliotta; Eduardo Puhl; João Andrade dos Reis Junior; Elis Figueiredo Oliveira (Journal of South American Earth Sciences, 2023)

Separation of alkane isomers in a hierarchically structured 3D-printed porous carbon monolith - Adriano Henrique; Hendryk Steldinger; Jose L. Diaz de Tuesta; Jan Gläsel; Alírio E. Rodrigues; Helder T. Gomes; Bastian J.M. Etzold; José A.C. Silva (Chemical Engineering Journal, 2023)

Fitness costs associated with spinetoram resistance in Spodoptera frugiperda is driven by host plants - Rubens H. Kanno; Aline S. Guidolin; Fernando E. O. Padovez; Juliana G. Rodrigues; Celso Omoto (Journal of Pest Science, 2023)

Repeated manure inputs to a forage production soil increase microbial biomass and diversity and select for lower abundance genera - Jordan M. Sayre; Daoyuan Wang; Jonathan Y. Lin; Rachel E. Danielson; Kate M. Scow; Jorge L. Mazza Rodrigues (Agriculture, Ecosystems & Environment, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Different patterns of maize hybrids responses under variable phosphorus availability - R. E. Rodrigues; A. R. Neto; L. S. Jesus; L. T. M. Guedes; L. S. Santos; M. N. Xavier; L. A. Souza (Acta Physiologiae Plantarum, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Development of a multigrid operational forecast system for the oceanic region off Rio de Janeiro State - Fernando T.C. Barreto; Franciane E. Curbani; Gabriel M. Zielinsky; Matheus B.L. da Silva; Kaio C. Lacerda; Douglas F. Rodrigues (Ocean Modelling, 2023)

The potential of almonds, hazelnuts, and walnuts SFE-CO2 extracts as sources of bread flavouring ingredients - Júlia C. Kessler; Vanessa Vieira; Isabel M. Martins; Yaidelin A. Manrique; Patrícia Ferreira; Ricardo C. Calhelha; Andreia Afonso; Lillian Barros; Alírio E. Rodrigues; Madalena M. Dias (Food Chemistry, 2023)

Carbon dioxide separation and capture by adsorption: a review - Mohsen Karimi; Mohammad Shirzad; José A. C. Silva; Alírio E. Rodrigues (Environmental Chemistry Letters, 2023)

Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Andre Rodrigues; Andrew J. Johnson; Ross A. Joseph; You Li; Nemat O. Keyhani; Edward L. Stanley; Benjamin Weiss; Martin Kaltenpoth; Matthew E. Smith; Jiri Hulcr (Symbiosis, 2023)

Performance of Bemisia tabaci MEAM1 on soybean and resistance traits of cultivars - Maria Carolina Farias e Silva; Arielly de Sousa Rodrigues; Raimundo Henrique Ferreira Rodrigues; Bruno Ettore Pavan; Luciana Barboza Silva (Journal of Asia-Pacific Entomology, 2023)

Green solvents for the selective extraction of bioactive compounds from by-products of the coffee production chain - Mariana Rodrigues da Silva; Rebecca E. Jelley; Renato Lajarim Carneiro; Bruno Fedrizzi; Cameron C. Weber; Cristiano Soleo Funari (Innovative Food Science & Emerging Technologies, 2023)

The antidepressant-like effect of guanosine involves the modulation of adenosine A1 and A2A receptors - Anderson Camargo; Luis E. B. Bettio; Priscila B. Rosa; Julia M. Rosa; Glorister A. Altê; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2023)

Combined Application of Antisense Oligomers to Control Transcription Factors of Candida albicans Biofilm Formation - D. Araújo; B. Gonçalves; D. Vilas Boas; M. E. Rodrigues; M. Henriques; S. Silva (Mycopathologia, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Shifts in functional traits and interactions patterns of soil methane‐cycling communities following forest‐to‐pasture conversion in the Amazon Basin - Dasiel Obregon Alvarez; Leandro Fonseca de Souza; Lucas William Mendes; Moacir Tuzzin de Moraes; Micaela Tosi; Andressa Monteiro Venturini; Kyle M. Meyer; Plínio Barbosa de Camargo; Brendan J. M. Bohannan; Jorge L. Mazza Rodrigues; Kari E. Dunfield; Siu Mui Tsai (Molecular Ecology, 2023)
Deforestation threatens the integrity of the Amazon biome and the ecosystem services it provides, including greenhouse gas mitigation. Forest‐to‐pasture conversion has been shown to alter the flux of methane gas (CH 4 ) in Amazonian soils, driving a switch from acting as a sink to a source of atmospheric CH 4 . This study aimed to better understand this phenomenon by investigating soil microbial metagenomes, focusing on the taxonomic and functional structure of methane‐cycling communities. Metagenomic data from forest and pasture soils were combined with measurements of in situ CH 4 fluxes and soil edaphic factors and analysed using multivariate statistical approaches. We found a significantly higher abundance and diversity of methanogens in pasture soils. As inferred by co‐occurrence networks, these microorganisms seem to be less interconnected within the soil microbiota in pasture soils. Metabolic traits were also different between land uses, with increased hydrogenotrophic and methylotrophic pathways of methanogenesis in pasture soils. Land‐use change also induced shifts in taxonomic and functional traits of methanotrophs, with bacteria harbouring genes encoding the soluble form of methane monooxygenase enzyme (sMMO) depleted in pasture soils. Redundancy analysis and multimodel inference revealed that the shift in methane‐cycling communities was associated with high pH, organic matter, soil porosity and micronutrients in pasture soils. These results comprehensively characterize the effect of forest‐to‐pasture conversion on the microbial communities driving the methane‐cycling microorganisms in the Amazon rainforest, which will contribute to the efforts to preserve this important biome.

Phytochemical analysis, in vitro antioxidant and anticholinesterase activities of Solanum paniculatum L. and an in-silico test with the AChE enzyme - João Paulo Rodrigues da Silva; Adriane da Cunha Rios Aragão; Ronaldo dos Santos Sousa Junior; Clara Andrezza Crisóstomo Bezerra Costa; Orlando Francisco da Silva Moura; Thaís Danyelle Santos Araújo; Durcilene Alves da Silva; Antonio Rodrigues da Silva Neto; Kessia da Costa Silva; Tatiana de Oliveira Lopes; Penina Sousa Mourão; Lorena Thayla Nascimento e Sousa; et al. (South African Journal of Botany, 2023)

Monitoring the impacts of a mega-dam on Amazonian understorey herbs - Marcelo B. Medeiros; Washington L. Oliveira; Flávio R.O. Rodrigues; Renata D. Silva; Íris J.K. Ferreira; Wellyngton E. Ayala; Suelma R. Silva; Rafaela T. Souza; Marcelo F. Simon (Forest Ecology and Management, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Peroxisomes : novel findings and future directions - Ana G. Pedrosa; Katharina Reglinski; Celien Lismont; Suzan Kors; Joseph Costello; Tony A. Rodrigues; Mariana Marques; Nicole Linka; Catherine Argyriou; Isabelle Weinhofer; Sai Kocherlakota; Victoria Riccio; et al. (Histochemistry and Cell Biology, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Nitrogen fate during agricultural managed aquifer recharge: Linking plant response, hydrologic, and geochemical processes - Elad Levintal; Laibin Huang; Cristina Prieto García; Adolfo Coyotl; Matthew W. Fidelibus; William R. Horwath; Jorge L. Mazza Rodrigues; Helen E. Dahlke (Science of The Total Environment, 2023)

How Can Geoscience Communication Foster Public Engagement with Geoconservation? - Joana Rodrigues; Elsa Costa e Silva; Diamantino Insua Pereira (Geoheritage, 2023)
Geoscience and geodiversity, two sides of the same coin, deal with very poor social visibility and recognition. Ensuring the protection of geodiversity is not only in the geoscientists’ hands and all of society needs to be involved. Therefore, public engagement with geodiversity demands new solutions and a change of paradigm in geoscience communication. Most of the science communication activities undertaken by geoscientists, even when they use modern approaches and technologies, are mainly designed based on empirical experience, laid on didactical approaches and assuming the public’s knowledge deficit. In order to engage the society with geodiversity, it is not enough to focus on scientific literacy and deficit models in which lack of knowledge is considered to be the main obstacle between science and society. It is fundamental to establish a commitment between society and science based on dialogue where lay public is not seen anymore as a single entity with a knowledge deficit. Non-experts must become also protagonists in scientific decisions with social impact and integrate their knowledge and concerns in public participation and decision-making. Engagement with geoscience and geodiversity would benefit from more effective and targeted communication strategies, with different approaches to engage with communities, local stakeholders, media, students and teachers, scientific community, tourists, politicians or policy-makers, and groups with different concerns and distinct relations with science. In the last 20 years, science communication research has made many relevant contributions in order to promote more participatory processes with which society is asked to engage. Regarding geoscience communication as a discipline, it is a very recent Earth science branch that also incorporates social science, behavioral science, and science communication, but still lacks a clear and formal definition. This study provides a comprehensive review of the literature in order to develop a conceptual framework for geoscience communication research, identifying the main challenges and opportunities.

Strategies of energy supplementation for cattle fed tropical forage and infrequently supplemented with protein - Malber N.N. Palma; William L.S. Reis; João P.P. Rodrigues; Tadeu E. Silva; Marcia O. Franco; Luciana N. Rennó; Edenio Detmann (Animal Feed Science and Technology, 2023)

Rainfall effects on vertical profiles of airborne fungi over a mixed land-use context at the Brazilian Atlantic Forest biodiversity hotspot - Maurício C. Mantoani; Ana P.M. Emygdio; Cristiane Degobbi; Camila Ribeiro Sapucci; Lara C.C. Guerra; Maria A.F.S. Dias; Pedro L.S. Dias; Rafael H.S. Zanetti; Fábio Rodrigues; Gabriel G. Araujo; Dulcilena M.C. Silva; Valter Batista Duo Filho; et al. (Agricultural and Forest Meteorology, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Local and Systemic Hypoxia as Inductors of Increased Aluminum and Iron Brain Accumulation Promoting the Onset of Alzheimer’s Disease - Ana Cirovic; Aleksandar Cirovic; Orish E Orisakwe; Rafael Rodrigues Lima (Biological Trace Element Research, 2023)

Quartz OSL sensitivity from dating data for provenance analysis of pleistocene and holocene fluvial sediments from lowland Amazonia - Priscila E. Souza; Fabiano N. Pupim; Carlos E.M. Mazoca; Ian del Río; Thays D. Mineli; Fernanda C.G. Rodrigues; Naomi Porat; Gelvam A. Hartmann; André O. Sawakuchi (Quaternary Geochronology, 2023)

Assessment of total evaporation rates and its surface distribution by tridimensional modelling and remote sensing - Sofia M.G. Rocha; Ernesto Molinas; Italo S. Rodrigues; Iran E. Lima Neto (Journal of Environmental Management, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

RELATIONSHIP BETWEEN SELENIUM NUTRITIONAL STATUS AND MARKERS OF LOW-GRADE CHRONIC INFLAMMATION IN OBESE WOMEN - Larissa Cristina Fontenelle; Mickael de Paiva Sousa; Loanne Rocha dos Santos; Bruna Emanuele Pereira Cardoso; Thayanne Gabryelle Visgueira de Sousa; Tamires da Cunha Soares; Stéfany Rodrigues de Sousa Melo; Jennifer Beatriz Silva Morais; Thaline Milany da Silva Dias; Francisco Erasmo de Oliveira; Débora Cavalcante Braz; João Marcelo de Castro e Sousa; et al. (Biological Trace Element Research, 2023)

Functional composition enhances aboveground carbon stock during tropical late-secondary forest succession - Alice Cristina Rodrigues; Pedro Manuel Villa; Fernando Silla; Lhoraynne Pereira Gomes; João Augusto Alves Meira-Neto; Carlos Moreira M. E. Torres; Andreza Viana Neri (Plant Biosystems, 2023)

Dietary glutamine improves growth and intestinal morphology of juvenile GIFT tilapia (Oreochromis niloticus) but has limited effects on innate immunity and antioxidant capacity - Pedro L.P.F. Carvalho; William dos S. Xavier; Matheus G. Guimarães; Edgar J.D. Rodrigues; Wilson M. Furuya; Fernando Y. Yamamoto; Luiz E. Pezzato; Delbert M. Gatlin; Margarida M. Barros (Aquaculture, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Process strategies to reduce cellulase enzyme loading for renewable sugar production in biorefineries - Cristiano E. Rodrigues Reis; Nelson Libardi Junior; Heitor B.S. Bento; Ana Karine F. de Carvalho; Luciana Porto de Souza Vandenberghe; Carlos Ricardo Soccol; Tejraj M. Aminabhavi; Anuj K. Chandel (Chemical Engineering Journal, 2023)

Seasonal climate impact on Brazilian pasture (Brachiaria brizantha cv Marandu): growth rate, CO2 efflux, and irrigation strategies - Milton E. Pereira-Flores; Flavio Justino; Jackson M. Rodrigues; Davi Boehringer; Anderson Adriano Martins Melo; Andressa G. Cursi; Vagna da Costa Pereira; Odilon Gomes Pereira; Ursula M. Ruiz-Vera (Theoretical and Applied Climatology, 2023)

Biochars as culture medium additives influence organogenic potential of plant explants through changes in endogenous phytohormone and carbohydrate contents in Daphne species - Alina Wiszniewska; Kinga Dziurka; Michał Dziurka; Aline F. Rodrigues; Agnieszka E. Latawiec (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Biochar applicability as culture medium amendment is rarely investigated due to its uncovered impact on in vitro cultured plants. This study assessed the feasibility of several biochars as alternatives to activated charcoal, for micropropagation of two ornamental Daphne species (Thymelaeaceae). We distinguished metabolic responses that were specific for: a) medium supplementation with any type of charcoal; b) biochar addition; c) biochar activation; d) the process of charcoal activation itself. We compared impacts of industrially produced biochar and three different biochars made in small-scale stoves (from residues of Gliricidia sepium) on organogenic capacity and physiological status in Daphne sp. shoots. Metabolite profiling revealed that biochars differently modulated accumulation of endogenous phytohormones and osmolytes in the shoots. Biochars reduced accumulation of proline, betaines and stress-related phytohormones (ABA, jasmonates), and impacted carbohydrate profile. For D. jasminea the most impactful was biochar activation, which increased micropropagation efficiency by elevating cytokinin and soluble sugars content. For D. tangutica charcoal/biochar activation, and application of biochar reduced accumulation of ABA and jasmonic acid, increased level of gibberellins, salicylic and benzoic acid, and altered carbohydrate composition. The study revealed that tested biochars can be used as a sustainable medium supplements without negative impact on production of new microshoots. Based on studied species we showed that biochar supplements could stimulate plantlet formation ( D. jasminea ,) ameliorate stress response ( D. tangutica ), and constitute a way of undesired biomass utilization (invasive species G. sepium ).

First record of Boulenger's anthias Sacura boulengeri (Heemstra 1973) in the Red Sea - Viktor Nunes Peinemann; Lucía Pombo‐Ayora; Jesse E. M. Cochran; Fabio Marchese; Giovanni Chimienti; Mattie Rodrigue; Ameer A. Eweida; Paul A. Marshall; Francesca Benzoni; Michael L. Berumen (Journal of Fish Biology, 2023)
In November 2020, we observed several individuals and collected one juvenile of an unidentified anthiadine fish (Serranidae) between depths of 250 and 307 m near vertical walls of rocky reefs in the northern Red Sea. Further morphological and molecular analyses revealed that the collected specimen matches Sacura boulengeri , a species previously reported only from the Gulf of Oman to India.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Apparent prevalence and risk factors for bovine tuberculosis in the state of Paraná, Brazil: an assessment after 18 years since the beginning of the Brazilian program - Diego Leonardo Rodrigues; Elenice Aparecida Amorim; Fernando Ferreira; Marcos Amaku; Oswaldo Santos Baquero; José Henrique de Hildebrand e Grisi Filho; Ricardo Augusto Dias; Marcos Bryan Heinemann; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; Christopher Compton; José Soares Ferreira Neto (Tropical Animal Health and Production, 2022)
Bovine tuberculosis (bTB) impacts considerably animal production and one health worldwide. To describe the prevalence, risk factors, and spatial pattern of the disease in the state of Paraná, Brazil, a cross-sectional study was conducted from September 2018 to February 2019. The area was divided into seven regions. Within each region, farms were randomly selected, and a predetermined number of cows was selected and tested by a comparative cervical tuberculin test. 17,210 animals were tested across 1757 farms. Herd prevalence of bTB-infected herds in Paraná was 2.5% [1.87–3.00%]. It has varied from 0.8 to 3.98% among seven regions, with clustering being detected in the west, central, and northeast areas. Animal prevalence was 0.35% [0.21–0.59%] and has varied from 0.08 to 0.6% among the pre-set regions. No major shifts in the prevalence of bTB were detected since 2007. Large-sized herds, dairy production, and feeding with whey were detected to be correlated with the presence of bTB. Exclusively among dairy herds, veterinary assistance from cooperatives, possession of self-owned equipment to cool milk, and feeding with whey were correlated with the disease. Considering these results, it is recommended that the state of Paraná seek to implement a surveillance system for the detection of bTB-infected herds transforming them into free ones, if possible, incorporating elements of risk-based surveillance. Health education is also recommended to inform farmers about the risks of introducing animals without testing and of feeding raw whey to calves.

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

SARS-CoV-2 Omicron BA.1, BA.2, and XAG identification during routine surveillance on a university campus in Belo Horizonte, Brazil, 2022 - Daniel Costa Queiroz; Natália Virtude Carobin; Luiza Campos Guerra de Araújo e Santos; Paula Luize Camargos Fonseca; Isabela Lorraine Braga-Paz; Rillery Calixto Dias; Jorge Gomes Goulart Ferreira; Túlio Resende Freitas; Diego Menezes; Sílvia Cristina Verde Mendes Nolasco; Simone Rodrigues Ribeiro; Thaís Salviana Ribeiro; et al. (Brazilian Journal of Microbiology, 2022)

Characteristics of the Isu1 C-terminus in relation to [2Fe-2S] cluster assembly and ISCU Myopathy - Brianne E. Lewis; Courtney J. Campbell; Andria Rodrigues; Lindsey Thompson; Ashutosh K. Pandey; Sarah N. Gallagher; Debkumar Pain; Andrew Dancis; Timothy L. Stemmler (JBIC Journal of Biological Inorganic Chemistry, 2022)

Combination of synthetic acaricides with (E)-cinnamaldehyde to control Rhipicephalus microplus - Bruno César Ferreira Gonzaga; Nélio Roberto de Moraes; Gabriel Webert Gomes; Ana Lúcia Coutinho; Francisca Letícia Vale; Lainny Jordana Martins Pereira e Sousa; Laís Marreto; Daniel de Castro Rodrigues; Márcia Cristina de Azevedo Prata; Paula Marchesini; Welber Daniel Zanetti Lopes; Caio Monteiro (Experimental and Applied Acarology, 2022)

Behavioural responses of a cold-water benthivore to loss of oxythermal habitat - Tazi H. Rodrigues; Andrew J. Chapelsky; Lee E. Hrenchuk; Graham R. Mushet; Lauren J. Chapman; Paul J. Blanchfield (Environmental Biology of Fishes, 2022)
Climate-driven declines in oxythermal habitat in freshwater lakes can impose prolonged constraints on cold-water fishes sensitive to hypoxia. How fish cope with severe habitat limitations is not well understood, yet has implications for their persistence. Here, we use acoustic-positioning telemetry to assess seasonal habitat occupancy and activity patterns of lake whitefish ( Coregonus clupeaformis ), a cold-water benthivore, in a small boreal lake that regularly faces severe oxythermal constraints during summer stratification. During this stratified period, they rarely (< 15% of detections) occupied depths with water temperatures > 10 °C (interquartile range = 5.3–7.9 °C), which resulted in extensive use (> 90% of detections) of water with < 4 mg L −1 dissolved oxygen (DO; interquartile range = 0.3–5.3 mg L −1 ). Lake whitefish were least active in winter and spring, but much more active in summer, when only a small portion of the lake (1–10%) contained optimal oxythermal habitat (< 10 °C and > 4 mg L −1 DO), showing frequent vertical forays into low DO environments concurrent with extensive lateral movement (7649 m d −1 ). High rates of lateral movement (8392 m d −1 ) persisted in the complete absence of optimal oxythermal habitat, but without high rates of vertical forays. We found evidence that lake whitefish are more tolerant of hypoxia (< 2 mg L −1 ) than previously understood, with some individuals routinely occupying hypoxic habitat in winter (up to 93% of detections) despite the availability of higher DO habitat. The changes in movement patterns across the gradient of habitat availability indicate that the behavioural responses of lake whitefish to unfavourable conditions may lead to changes in foraging efficiency and exposure to physiological stress, with detrimental effects on their persistence.

An update on the phylogeny of Spintharinae with analysis based on morphological characters and taxonomy of Janula (Araneae, Theridiidae) - Everton Nei Lopes Rodrigues; Patrícia E. S. Rodrigues; Antonio D. Brescovit; Joseph K. H. Koh (Organisms Diversity & Evolution, 2022)

Elite Bradyrhizobium strains boost biological nitrogen fixation and peanut yield in tropical drylands - Raphael Silva Jovino; Thaíse Rosa da Silva; Ruth Terezinha Rodrigues; Jackson Rafael de Sá Carvalho; Jussara Barboza de Alencar Cunha; Liziane Maria de Lima; Roseane Cavalcanti dos Santos; Carolina Etienne de Rosália e Silva Santos; Paula Rose de Almeida Ribeiro; Ana Dolores Santiago de Freitas; Lindete Míria Vieira Martins; Paulo Ivan Fernandes-Júnior (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Development of a Nanoformulation for Oral Protein Administration: Characterization and Preclinical Orofacial Antinociceptive Effect - Marina de Barros Mamede Vidal Damasceno; Sacha Aubrey Alves Rodrigues Santos; João Ronielly Campêlo Araújo; Lana Karine Vasconcelos Barroso; Samara Casemiro Benevides; Francisco Ernani Alves Magalhães; Kaio César Simiano Tavares; Renato de Azevedo Moreira; Ana Cristina de Oliveira Monteiro-Moreira; Angelo Roncalli Alves e Silva; Adriana Rolim Campos (AAPS PharmSciTech, 2022)

Dried distiller’s grains for feedlot Nellore cattle fed non-forage-based diets - Pedro Ivo José Lopes da Rosa e Silva; Yasmim Rodrigues Vilas Boas e Silva; Pedro Veiga Rodrigues Paulino; Daniel de Paula Sousa; Adriano Jorge Possamai; Lucien Bissi da Freiria; Henrique Castrillon Leiva Rolim; Waldir de Castro Dias Júnior; Luciano da Silva Cabral (Tropical Animal Health and Production, 2022)

A sustainable approach in the management of Callosobruchus maculatus: essential oil of Protium heptaphyllum and its major compound d-limonene as biopesticides - Rosalba Maria Borges de Andrade Rodrigues; Lucia da Silva Fontes; Rodrigo de Carvalho Brito; Douglas Rafael e Silva Barbosa; Antonia Maria das Graças Lopes Citó; Iolanda Souza do Carmo; Emanoela Maria de Jesus Sousa; Gutierres Nelson Silva (Journal of Plant Diseases and Protection, 2022)

Assessment of integrated MSW management using multicriteria analysis in São Paulo City - E. Rodrigues; G. Mondelli (International Journal of Environmental Science and Technology, 2022)

Contrasting tourism regimes due to the COVID-19 lockdown reveal varied genomic toxicity in a tropical beach in the Southern Atlantic - José Rodolfo de Lima e Silva; Anderson Rodrigues Balbino de Lima; Demétrios Lucas da Silva; José Souto Rosa Filho; Mônica Lúcia Adam (Environmental Monitoring and Assessment, 2022)

Asynchrony, density dependence, and persistence in an amphibian - Freya E. Rowland; Elizabeth S. Schyling; L. Kealoha Freidenburg; Mark C. Urban; Jonathan L. Richardson; A. Z. Andis Arietta; Susan B. Rodrigues; Adriana D. Rubinstein; Michael F. Benard; David K. Skelly (Ecology, 2022)
Understanding drivers of metapopulation dynamics remains a critical challenge for ecology and conservation. In particular, the degree of synchrony in metapopulation dynamics determines how resilient a metapopulation is to a widespread disturbance. In this study, we used 21 years of egg mass count data across 64 nonpermanent freshwater ponds in Connecticut, USA to evaluate patterns of abundance and growth and to assess regional as well as local factors in shaping the population dynamics of wood frogs ( Rana sylvatica = Lithobates sylvaticus ). In particular, we asked whether a species known to undergo metapopulation dynamics exhibited spatial synchrony in abundances. With the exception of a single year when breeding took place during severe drought conditions, our analyses revealed no evidence of synchrony despite close proximity (mean minimum distance

Different fat sources in supplements for beef cattle at pasture - Lucien Bissi da Freiria; Joanis Tilemahos Zervoudakis; Nelcino Francisco de Paula; Mozart Alves Fonseca; Pedro Ivo José Lopes da Rosa e Silva; Yasmim Rodrigues Vilas Boas e Silva; Adriano Jorge Possamai (Tropical Animal Health and Production, 2022)

Influence of exercise and vitamin D on the immune system against Covid-19: an integrative review of current literature - Matheus Ribeiro Bizuti; Édina Starck; Kimberly Kamila da Silva Fagundes; Josiano Guilherme Puhle; Lucas Medeiros Lima; Natan Rodrigues de Oliveira; Guilherme Vinicio de Sousa Silva; Débora Tavares Resende e Silva (Molecular and Cellular Biochemistry, 2022)

Comparison of sugarcane pressmud with traditional low-cost materials for adsorption of lead and zinc in mining areas - I. M. Raimondi; E. M. Vieira; L. A. A. Vaz; V. G. S. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Thermal comfort conditions at microclimate scale and surface urban heat island in a tropical city: A study on João Pessoa city, Brazil - Regiane de Souza e Silva; Richarde Marques da Silva; Anne Falcão de Freitas; Joel Silva dos Santos; Celso Augusto Guimarães Santos; Eduardo Rodrigues Viana de Lima (International Journal of Biometeorology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

QSAR-Guided Proposition of N-(4-methanesulfonyl)Benzoyl-N’-(Pyrimidin-2-yl)Thioureas as Effective and Safer Herbicides - Natânia E. Rodrigues; Adriana C. de Faria; Ingrid V. Pereira; Elaine F. F. da Cunha; Matheus P. Freitas (Bulletin of Environmental Contamination and Toxicology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Optical time series for the separation of land cover types with similar spectral signatures: cocoa agroforest and forest - João E. Batista; Nuno M. Rodrigues; Ana I. R. Cabral; Maria J. P. Vasconcelos; Adriano Venturieri; Luiz G. T. Silva; Sara Silva (International Journal of Remote Sensing, 2022)

Soil biotic and abiotic traits as driven factors for site quality of Araucaria angustifolia plantations - Tancredo Souza; Mário Dobner; Djalma E. Schmitt; Lucas Jónatan Rodrigues da Silva; Ketlin Schneider (Biologia, 2022)

NeoBat Interactions: A data set of bat–plant interactions in the Neotropics - Guillermo L. Florez‐Montero; Renata L. Muylaert; Marcelo R. Nogueira; Cullen Geiselman; Sharlene E. Santana; Richard D. Stevens; Marco Tschapka; Francisco A. Rodrigues; Marco A. R. Mello (Ecology, 2022)
Data papers and open databases have revolutionized contemporary science, as they provide the long‐needed incentive to collaborate in large international teams and make natural history information widely available. Nevertheless, most data papers have focused on species occurrence or abundance, whereas interactions have received much less attention. To help fill this gap, we have compiled a georeferenced data set of interactions between 93 bat species of the family Phyllostomidae (Chiroptera) and 501 plant species of 68 families. Data came from 169 studies published between 1957 and 2007 covering the entire Neotropical Region, with most records from Brazil (34.5% of all study sites), Costa Rica (16%), and Mexico (14%). Our data set includes 2571 records of frugivory (75.1% of all records) and nectarivory (24.9%). The best represented bat genera are Artibeus (28% of all records), Carollia (24%), Sturnira (10.1%), and Glossophaga (8.8%). Carollia perspicillata (187), Artibeus lituratus (125), Artibeus jamaicensis (94), Glossophaga soricina (86), and Artibeus planirostris (74) were the bat species with the broadest diets recorded based on the number of plant species. Among the plants, the best represented families were Moraceae (17%), Piperaceae (15.4%), Urticaceae (9.2%), and Solanaceae (9%). Plants of the genera Cecropia (46), Ficus (42), Piper (40), Solanum (31), and Vismia (27) exhibited the largest number of interactions. These data are stored as arrays (records, sites, and studies) organized by logical keys and rich metadata, which helped to compile the information on different ecological and geographic scales, according to how they should be used. Our data set on bat–plant interactions is by far the most extensive, both in geographic and taxonomic terms, and includes abiotic information of study sites, as well as ecological information of plants and bats. It has already facilitated several studies and we hope it will stimulate novel analyses and syntheses, in addition to pointing out important gaps in knowledge. Data are provided under the Creative Commons Attribution 4.0 International License. Please cite this paper when the data are used in any kind of publication related to research, outreach, and teaching activities.

Hydrolytic enzyme production from açai palm (Euterpe precatoria) endophytic fungi and characterization of the amylolytic and cellulolytic extracts - Bárbara Nunes Batista; Rosiane Rodrigues Matias; Rafael Lopes e Oliveira; Patrícia Melchionna Albuquerque (World Journal of Microbiology and Biotechnology, 2022)

Pharmacological blockage of the AHR-CYP1A1 axis: a call for in vivo evidence - N. R. Coelho; A. B. Pimpão; M. J. Correia; T. C. Rodrigues; E. C. Monteiro; J. Morello; S. A. Pereira (Journal of Molecular Medicine, 2022)

Climate and management effects on the herbaceous layer productivity of a cork oak woodland - M. C. Bicho; A. C. Correia; A. R. Rodrigues; J. Soares David; F. Costa-e-Silva (Agroforestry Systems, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Spatial controls on riverbed sediment chemistry in three anthropogenically modified tropical mountainous watersheds - J. Papotto; L. J. Rodrigues; E. M. Siebert; E. J. Wagner; S. T. Goldsmith (International Journal of Environmental Science and Technology, 2022)

Assessment of Water Quality Parameters and their Seasonal Behaviour in a Portuguese Water Supply System: a 6-year Monitoring Study - Raquel S. Chaves; Daniel Salvador; Paulo Nogueira; Miguel M. Santos; Paula Aprisco; Célia Neto; Vítor Cardoso; Maria J. Benoliel; João E. Rodrigues; Rui N. Carneiro (Environmental Management, 2022)

Important Key Process Simulations in the Field of Steel Metallurgy - A. Ludwig; C. M. G. Rodrigues; Z. Zhang; H. Zhang; E. Karimi-Sibaki; H. Barati; A. Vakhrushev; M. Al-Nasser; M. Wu; A. Kharicha (BHM Berg- und Hüttenmännische Monatshefte, 2022)
During the last decade, the chair for ‘Simulation and Modelling of Metallurgical Processes’ (SMMP) has worked on different metallurgical processes with the highlights of the following five industrial relevant topics: (i) modelling the as-cast structures of large steel castings; (ii) exploring the formation mechanisms of macrosegregation; (iii) describing magnetohydrodynamic and electrochemical phenomena in remelting processes, (iv) understanding how solidification and flow can be influenced by magnetohydrodynamics during steel continuous casting; and (v) describing nozzle clogging in steelmaking processes. In this contribution, the main achievements from the group on the above five topics are briefly described.

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Hypomagnesemia and Its Relationship with Oxidative Stress Markers in Women with Breast Cancer - Daila Leite Chaves Bezerra; Priscyla Maria Vieira Mendes; Stéfany Rodrigues de Sousa Melo; Loanne Rocha dos Santos; Raisa de Oliveira Santos; Sabas Carlos Vieira; Gilberto Simeone Henriques; Betania de Jesus e Silva de Almendr Freitas; Dilina do Nascimento Marreiro (Biological Trace Element Research, 2021)

Aerobic degradation of 2,4,6-trinitrophenol by Proteus sp. strain OSES2 obtained from an explosive contaminated tropical soil - Osekokhune E. Okozide; Sunday A. Adebusoye; Oluwafemi S. Obayori; Deborah F. Rodrigues (Biodegradation, 2021)

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis - E. C. D. Gonçalves; V. Lieberknecht; V. V. Horewicz; B. D. Rabelo; F. A. Felipetti; A. L. S. Rodrigues; D. F. Martins; R. C. Dutra (Molecular Neurobiology, 2021)

Virulence Genes Profile and Antimicrobial Susceptibility of Community-Acquired Bacterial Urinary Tract Infections in a Brazilian Hospital - Fernanda Morcatti Coura; Vitoria Marra de Souza Savini; Rafael Gariglio Clark Xavier; Carolina Pantuzza Ramos; Rodrigo Otávio Silveira Silva; Marcos Bryan Heinemann; Andrea Micke Moreno; Terezinha Knöbl; Elaine Maria Seles Dorneles; Dirceia Aparecida da Costa Custódio; Carine Rodrigues Pereira; Pedro Felipe Rodrigues e Oliveira; et al. (Current Microbiology, 2021)

Grazer-Induced Chemical Defense in a Microcystin-Producing Microcystis aeruginosa (Cyanobacteria) Exposed to Daphnia gessneri Infochemicals - Mauro Cesar Palmeira Vilar; Thiago Ferreira da Costa Pena Rodrigues; Aloysio da Silva Ferrão-Filho; Sandra Maria Feliciano de Oliveira e Azevedo (Journal of Chemical Ecology, 2021)

Mismatch between bird species sensitivity and the protection of intact habitats across the Americas - Victor Cazalis; Megan D. Barnes; Alison Johnston; James E. M. Watson; Cagan H. Şekercioğlu; Ana S. L. Rodrigues (Ecology Letters, 2021)
Protected areas are highly heterogeneous in their effectiveness at buffering human pressure, which may hamper their ability to conserve species highly sensitive to human activities. Here, we use 60 million bird observations from eBird to estimate the sensitivity to human pressure of each bird species breeding in the Americas. Concerningly, we find that ecoregions hosting large proportions of high‐sensitivity species, concentrated in tropical biomes, do not have more intact protected habitat. Moreover, 266 high‐sensitivity species have little or no intact protected habitat within their distributions. Finally, we show that protected area intactness is decreasing faster where high‐sensitivity species concentrate. Our results highlight a major mismatch between species conservation needs and the coverage of intact protected habitats, which likely hampers the long‐term effectiveness of protected areas at retaining species. We highlight ecoregions where protection and management of intact habitats, complemented by restoration, is urgently needed.

Seroprevalence and risk factors for bovine brucellosis in the state of Paraná, Brazil: an analysis after 18 years of ongoing control measures - Diego Leonardo Rodrigues; Elenice Aparecida Amorim; Fernando Ferreira; Marcos Amaku; Oswaldo Santos Baquero; José Henrique de Hildebrand e Grisi Filho; Ricardo Augusto Dias; Marcos Bryan Heinemann; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; Cord Heuer; José Soares Ferreira Neto (Tropical Animal Health and Production, 2021)

Effects of supplementation on production and age anticipation at first mating of ewe lambs in tropical pastures - Thais Fernanda Farias de Souza Arco; Camila Celeste Brandão Ferreira Ítavo; Luís Carlos Vinhas Ítavo; Maria Inês Lenz Souza; Alexandre Menezes Dias; Gelson dos Santos Difante; Eliane Vianna da Costa e Silva; Fernando de Almeida Borges; Dyego Gonçalves Lino Borges; Kedma Leonora da Silva Monteiro Ferelli; Bruna Junqueira Rodrigues; Aline Aparecida da Silva Miguel; et al. (Tropical Animal Health and Production, 2021)

Pre-inoculation with arbuscular mycorrhizal fungi affects essential oil quality and the reproduction of root lesion nematode in Cymbopogon citratus - Monique Thiara Rodrigues e Silva; Angélica Calandrelli; Angélica Miamoto; Luanna Karoline Rinaldi; Beatriz Pereira Moreno; Camila da Silva; Cláudia Regina Dias-Arieira (Mycorrhiza, 2021)

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics - V. S. Hampel; C. H. E. C. Poli; M. Joy; J. F. Tontini; T. Devincenzi; J. R. B. Pardos; R. E. F. Macedo; E. N. Nalério; A. G. F. Saccol; E. Rodrigues; V. Manfroi; N. M. Fajardo (Tropical Animal Health and Production, 2021)

Structural insights into the allosteric site of Arabidopsis NADP-malic enzyme 2: role of the second sphere residues in the regulatory signal transmission - Mariel Claudia Gerrard Wheeler; Cintia Lucía Arias; Juliana da Fonseca Rezende e Mello; Nuria Cirauqui Diaz; Carlos Rangel Rodrigues; María Fabiana Drincovich; Alessandra Mendonça Teles de Souza; Clarisa Ester Alvarez (Plant Molecular Biology, 2021)

Identification of TIA1 mRNA targets during human neuronal development - Loryn P. Byres; Marat Mufteev; Kyoko E. Yuki; Wei Wei; Alina Piekna; Michael D. Wilson; Deivid C. Rodrigues; James Ellis (Molecular Biology Reports, 2021)
Background Neuronal development is a tightly controlled process involving multi-layered regulatory mechanisms. While transcriptional pathways regulating neurodevelopment are well characterized, post-transcriptional programs are still poorly understood. TIA1 is an RNA-binding protein that can regulate splicing, stability, or translation of target mRNAs, and has been shown to play critical roles in stress response and neurodevelopment. However, the identity of mRNAs regulated by TIA1 during neurodevelopment under unstressed conditions is still unknown. Methods and Results To identify the mRNAs targeted by TIA1 during the first stages of human neurodevelopment, we performed RNA immunoprecipitation-sequencing (RIP-seq) on human embryonic stem cells (hESCs) and derived neural progenitor cells (NPCs), and cortical neurons under unstressed conditions. While there was no change in TIA1 protein levels, the number of TIA1 targeted mRNAs decreased from pluripotent cells to neurons. We identified 2400, 845, and 330 TIA1 mRNA targets in hESCs, NPC, and neurons, respectively. The vast majority of mRNA targets in hESC were genes associated with neurodevelopment and included autism spectrum disorder-risk genes that were not bound in neurons. Additionally, we found that most TIA1 mRNA targets have reduced ribosomal engagement levels. Conclusion Our results reveal TIA1 mRNA targets in hESCs and during human neurodevelopment, indicate that translation repression is a key process targeted by TIA1 binding and implicate TIA1 function in neuronal differentiation.

Impact of growing seasons and pesticides used on the occurrence and severity of the gummy stem blight in melon cultivation in Brazil - Gil Rodrigues dos Santos; P. H. Tschoeke; R. A. Sarmento; E. E. Oliveira; N. Rodrigues-Silva; M. S. Dalcin; K. Haddi; R. S. Silva (European Journal of Plant Pathology, 2021)

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Control of Meloidogyne javanica and induction of resistance-associated enzymes in soybean by extracts of Ascophyllum nodosum - Luanna Karoline Rinaldi; Angélica Miamoto; Angélica Calandrelli; Monique Thiara Rodrigues e Silva; Lana Paola Silva Chidichima; Carolina Bertuzzi Pereira; Claudia Regina Dias-Arieira (Journal of Applied Phycology, 2021)

Phaeodactylum tricornutum biomass in microdiets enhances Senegalese sole (Solea senegalensis) larval growth performance during weaning - André Barreto; Wilson Pinto; Andreia Rodrigues; Rui J. M. Rocha; Carlos Unamunzaga; Tomé Silva; Jorge Dias; Luis E. C. Conceição (Journal of Applied Phycology, 2021)

Correction to: Association of ionophores, yeast, and bacterial probiotics alters the abundance of ruminal microbial species of pasture intensively finished beef cattle - Mircéia Angele Mombach; Luciano da Silva Cabral; Leni Rodrigues Lima; Daniela Cristina Ferreira; Bruno Carneiro e Pedreira; Dalton Henrique Pereira (Tropical Animal Health and Production, 2021)

Cold Tolerance in Sugarcane Progenies Under Natural Stress - Adílson Härter; Sergio Delmar dos Anjos e Silva; Mario Alvaro Aloisio Verissimo; William Rodrigues Antunes; Lucas Silva Lemões; Luize Silva Mascarenhas; João Carlos Bespalhok Filho; Ricardo Augusto de Oliveira (Sugar Tech, 2021)

A Concise Review on Induced Pluripotent Stem Cell-Derived Cardiomyocytes for Personalized Regenerative Medicine - Pallavi Pushp; Diogo E. S. Nogueira; Carlos A. V. Rodrigues; Frederico C. Ferreira; Joaquim M. S. Cabral; Mukesh Kumar Gupta (Stem Cell Reviews and Reports, 2021)

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

A multivariate approach to the physical and physiological quality of hybrid corn seeds affected by Molicutes and MRFV - Jhonata Cantuária Medeiros; Juliana de Fátima Sales; Jacson Zuchi; Kelly Juliane Teles Nascimento; Fernando Higino de Lima e Silva; Stella Tomaz de Castro; Adriano Carvalho Costa; Arthur Almeida Rodrigues (Euphytica, 2021)

Transaminase profile and hepatic histopathological traits in Piaractus mesopotamicus exposed to insecticide Diflubenzuron - André Luiz N. Silva; Robson Andrade Rodrigues; Mayara Schueroff Siqueira; Karine Nathiele Nogueira Farias; Karin Virgínia Kuibida; Lilian Franco-Belussi; Carlos E. Fernandes (Environmental Science and Pollution Research, 2021)

Diclofenac photodegradation with the Perovskites BaFeyTi1-yO3 as catalysts - Ana Sofia Rodrigues; Jefferson E. Silveira; Jaime Carbajo; Juan A. Zazo; Jose A. Casas; Annabel Fernandes; Maria José Pacheco; Lurdes Ciríaco; Ana Lopes (Environmental Science and Pollution Research, 2021)

The electro-oxidation of tetracycline hydrochloride in commercial DSA® modified by electrodeposited platinum - João Paulo Tenório da Silva Santos; Josealdo Tonholo; Adalgisa Rodrigues de Andrade; Vinicius Del Colle; Carmem Lucia de Paiva e Silva Zanta (Environmental Science and Pollution Research, 2021)

Imidacloprid-mediated alterations on the salivary glands of the Neotropical brown stink bug, Euschistus heros - Nathaly L. Castellanos; Noelio A. Ferreira-Filho; Higor S. Rodrigues; Luis Carlos Martínez; José E. Serrão; Eugenio E. Oliveira (Ecotoxicology, 2021)

Neuronal activity regulated pentraxin (narp) and GluA4 subunit of AMPA receptor may be targets for fluoxetine modulation - Isabella A. Heinrich; Andiara E. Freitas; Ingrid A. V. Wolin; Ana Paula M. Nascimento; Roger Walz; Ana Lúcia S. Rodrigues; Rodrigo B. Leal (Metabolic Brain Disease, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

The Zygoptera/Anisoptera ratio as a tool to assess anthropogenic changes in Atlantic Forest streams - Cintia Ribeiro; Leandro Juen; Marciel E. Rodrigues (Biodiversity and Conservation, 2021)

Association of ionophores, yeast, and bacterial probiotics alters the abundance of ruminal microbial species of pasture intensively finished beef cattle - Mircéia Angele Mombach; Luciano da Silva Cabral; Leni Rodrigues Lima; Daniela Cristina Ferreira; Bruno Carneiro e Pedreira; Dalton Henrique Pereira (Tropical Animal Health and Production, 2021)

Modulating the lipid profile of beef using cottonseed and crude glycerin - Adriano Jorge Possamai; Joanis Tilemahos Zervoudakis; André Soares de Oliveira; Luciana Keiko Hatamoto-Zervoudakis; Pedro Ivo José Lopes da Rosa e Silva; Lucien Bissi da Freiria; Yasmim Rodrigues Vilas Boas e Silva (Tropical Animal Health and Production, 2021)

Supplementation with different protein profiles for grazing beef cattle supplemented in tropical grass during the rainy-dry transition season - Yasmim Rodrigues Vilas Boas e Silva; Joanis Tilemahos Zervoudakis; Luciana Keiko Hatamoto-Zervoudakis; Matheus Lima Corrêa Abreu; Luciano da Silva Cabral; Lucien Bissi da Freiria; Pedro Ivo José Lopes da Rosa e Silva; Adriano Jorge Possamai (Tropical Animal Health and Production, 2021)

The usefulness of Olanzapine plasma concentrations in monitoring treatment efficacy and metabolic disturbances in first-episode psychosis - J. A. Arnaiz; C. Rodrigues-Silva; G. Mezquida; S. Amoretti; M. J. Cuesta; D. Fraguas; A. Lobo; A. González-Pinto; M. C. Díaz-Caneja; I. Corripio; E. Vieta; I. Baeza; et al. (Psychopharmacology, 2021)

The CORDEX Flagship Pilot Study in southeastern South America: a comparative study of statistical and dynamical downscaling models in simulating daily extreme precipitation events - M. L. Bettolli; S. A. Solman; R. P. da Rocha; M. Llopart; J. M. Gutierrez; J. Fernández; M. E. Olmo; A. Lavin-Gullon; S. C. Chou; D. Carneiro Rodrigues; E. Coppola; R. Balmaceda Huarte; et al. (Climate Dynamics, 2021)

An epidemiological index for drought vulnerability in the Rio Grande do Norte State, Brazil - Pollyanne Evangelista da Silva; Maria Helena Constantino Spyrides; Lara de Melo Barbosa Andrade; Cláudio Moisés Santos e Silva; Pedro Rodrigues Mutti; Paulo Sérgio Lucio (International Journal of Biometeorology, 2021)

Selection of cowpea cultivars for high temperature tolerance: physiological, biochemical and yield aspects - Juliane Rafaele Alves Barros; Miguel Julio Machado Guimarães; Rodrigo Moura e Silva; Maydara Thaylla Cavalcanti Rêgo; Natoniel Franklin de Melo; Agnaldo Rodrigues de Melo Chaves; Francislene Angelotti (Physiology and Molecular Biology of Plants, 2021)

Different wavelengths of visible light influence the conidial production and tolerance to ultra-violet radiation of the plant pathogens Colletotrichum acutatum and Fusarium fujikuroi - Tacyana P. C. Costa; Eliane M. Rodrigues; Luciana P. Dias; Breno Pupin; Paulo C. Ferreira; Drauzio E. N. Rangel (European Journal of Plant Pathology, 2021)

Conservation of Brazilian freshwater biodiversity: Thinking about the next 10 years and beyond - Valter M. Azevedo-Santos; Jorge Luiz Rodrigues-Filho; Philip M. Fearnside; Thomas E. Lovejoy; Marcelo F. G. Brito (Biodiversity and Conservation, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Intranasal administration of budesonide-loaded nanocapsule microagglomerates as an innovative strategy for asthma treatment - Manoel Ortiz; Diego de Sa Coutinho; Bianca Torres Ciambarella; Everton Tenorio de Souza; Ana Paula Leite D’Almeida; Taís Lusa Durli; Patrícia Machado Rodrigues e Silva; Andressa Bernardi; Fabio Sonvico; Adriana Raffin Pohlmann; Marco Aurelio Martins; Sílvia Stanisçuaski Guterres (Drug Delivery and Translational Research, 2020)

Sanitary quality improvement of fish produced in the northern Benin cotton basin water reservoirs by cage culture and fish transfer in agricultural contaminant-free water: human health implications - Rodrigue O. E. Pèlèbè; Ibrahim Imorou Toko; Issa N. Ouattara; Ulbad P. Tougan; Eloi Y. Attakpa; Jean Fall; Elie Montchowui (Tropical Animal Health and Production, 2020)

Undecane production by cold-adapted bacteria from Antarctica - Michel Rodrigo Zambrano Passarini; Tiago Rodrigues e Silva; Suzan Prado Fernandes Bernal; Nathália Luana Cecchet; Adilson Sartoratto; Marcela Boroski; Alysson Wagner Fernandes Duarte; Júlia Ronzella Ottoni; Luiz Henrique Rosa; Valéria Maia de Oliveira (Extremophiles, 2020)

Costus stripe mosaic virus, a tentative new member of the genus Potyvirus - M. Amelia V. Alexandre; Ligia M. L. Duarte; Pedro L. Ramos-González; Alexandre L. R. Chaves; Ricardo Harakava; Leilane K. Rodrigues; Camila Chabi-Jesus; E. W. Kitajima (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

TNF, IL-6, and IL-10 cytokines levels and their polymorphisms in renal function and time after transplantation - Lorraine Vieira Alves; Suellen Rodrigues Martins; Ana Cristina Simões e Silva; Carolina Neris Cardoso; Karina Braga Gomes; Ana Paula Lucas Mota (Immunologic Research, 2020)

Gonadal remodeling and hormonal regulation during sex change of juvenile dusky grouper Epinephelus marginatus (Teleostei, Serranidae), an endangered protogynous hermaphrodite fish - J. A. Rodrigues-Filho; C. E. O. Garcia; C. G. Chehade; E. G. Sanches; M. I. Borella; F. L. Lo Nostro; B. C. Araújo; G. S. Branco; R. G. Moreira (Fish Physiology and Biochemistry, 2020)

Correction to: Carbon sequestration and nutrient cycling in agroforestry systems on degraded soils of Eastern Amazon, Brazil - Danielle Celentano; Guillaume Xavier Rousseau; Larissa Santos Paixão; Francisneide Lourenço; Ernesto Gómez Cardozo; Thiago Oliveira Rodrigues; Hulda Rocha e Silva; Júlio Medina; Tatiane Marques C. de Sousa; Ariadne Enes Rocha; Fabrício de Oliveira Reis (Agroforestry Systems, 2020)

Carbon sequestration and nutrient cycling in agroforestry systems on degraded soils of Eastern Amazon, Brazil - Danielle Celentano; Guillaume Xavier Rousseau; Larissa Santos Paixão; Francisneide Lourenço; Ernesto Gómez Cardozo; Thiago Oliveira Rodrigues; Hulda Rocha e Silva; Júlio Medina; Tatiane Marques C. de Sousa; Ariadne Enes Rocha; Fabrício de Oliveira Reis (Agroforestry Systems, 2020)

Spatial distribution of the level of return of extreme precipitation events in Northeast Brazil - Daniele T. Rodrigues; Weber A. Gonçalves; Maria H. C. Spyrides; Cláudio M. Santos e Silva; Diego O. de Souza (International Journal of Climatology, 2020)
This study aimed to estimate levels of return of extreme daily precipitation events, associating them with natural disasters in Northeast Brazil (NEB), a region characterized by different climatic conditions and low rates of social and economic development. For this, generalized Pareto distribution (GPD) models were adjusted to the daily extreme precipitation data estimated by the Tropical Rainfall Measuring Mission (TRMM) 3B42 product of the multisatellite precipitation analysis for a period of 16 years (2000–2015). In addition, the estimates of the GPD model were compared using two data sources, TRMM and pluviometer. The investigation showed that the results of the GPD model estimated by means of the extreme data from the rain gauge and the TRMM were statistically the same, with 95% confidence. Thus, using the data referring to the 2,082 grid points of the TRMM, it was possible to map the spatial distribution of the estimates of the levels of return of extreme precipitation to the return periods of 2, 5 and 10 years, per seasonal period. In general, the results indicated that the intensity of expected extreme precipitation depends on the seasonal period and the place of occurrence of precipitation. The eastern NEB stood out as the region where the highest intensities of extreme precipitation are expected. Extreme precipitation values of up to 178 mm are expected in 2 years. The areas where natural disasters occurred in the years 2016, 2017 and 2018 are similar to those in which the highest rainfall intensities are expected. The results of this study can allow the evaluation of the spatial distribution of risks related to extreme precipitation events, and therefore, support the planning of regional public policies and environmental management for the prevention of natural disasters in NEB.

Morpho-Anatomical and Molecular Characterization of the Oversprouting Symptoms Caused by Fusarium decemcellulare in Guarana Plants (Paullinia cupana var. sorbilis) - Claudia Afras de Queiroz; Kedma da Silva Matos; Igor Kelvyn Cavalcante Lobo; Sandra Barbosa de Sousa; Celli Rodrigues Muniz; Michel E. Beleza Yamagishi; Guilherme Julião Zocolo; Rogério Eiji Hanada; Luadir Gasparotto; Nelcimar Reis Sousa; Edmar Vaz de Andrade; Isabelle Bezerra Cordeiro; et al. (Tropical Plant Biology, 2020)

Analysis of Climate Extreme Indices in the MATOPIBA Region, Brazil - Layara Campelo dos Reis; Cláudio Moisés Santos e Silva; Bergson Guedes Bezerra; Pedro Rodrigues Mutti; Maria Helena Constantino Spyrides; Pollyanne Evangelista da Silva (Pure and Applied Geophysics, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

Activity pattern, budget and diurnal rhythmicity of the brown-throated three-toed sloth (Bradypus variegatus) in northeastern Brazil - Diogo de Oliveira Bezerra; Leandro Ricardo Rodrigues de Lucena; Giles E. Duffield; Dominic J. Acri; Antonio Rossano Mendes Pontes (Mammalian Biology, 2020)

Residential radon exposure and seasonal variation in the countryside of southeastern Brazil - Camila Rodrigues e Silva; Joseph M. Smoak; Emmanoel Vieira da Silva-Filho (Environmental Monitoring and Assessment, 2020)

Changes in salivary protein composition of lambs supplemented with aerial parts and condensed tannins: extract from Cistus ladanifer L.—a preliminary study - Elsa Lamy; Lénia Rodrigues; Olinda Guerreiro; David Soldado; Alexandra Francisco; Monica Lima; Fernando Capela e Silva; Orlando Lopes; José Santos-Silva; Eliana Jerónimo (Agroforestry Systems, 2020)

P2X7 siRNA targeted to the kidneys increases klotho and delays the progression of experimental diabetic nephropathy - A. M. Rodrigues; R. S. Serralha; D. Y. Lima; G. R. Punaro; I. Visona; M. J. S. Fernandes; E. M. S. Higa (Purinergic Signalling, 2020)

Entomopathogenic Viruses in the Neotropics: Current Status and Recently Discovered Species - D R Sosa-Gómez; F S Morgado; R F T Corrêa; L A Silva; D M P Ardisson-Araújo; B M P Rodrigues; E E Oliveira; R W S Aguiar; B M Ribeiro (Neotropical Entomology, 2020)

Dog activity in protected areas: behavioral effects on mesocarnivores and the impacts of a top predator - Rita de Cassia Bianchi; Natalie Olifiers; Letícia Lutke Riski; Jéssica Abonízio Gouvea; Clarice Silva Cesário; Larissa Fornitano; Gisele Lamberti Zanirato; Mateus Yan de Oliveira; Kimberly Danielle Rodrigues de Morais; Renan Lieto Alves Ribeiro; Paulo Sergio D’Andrea; Matthew E. Gompper (European Journal of Wildlife Research, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Antibiotic consumption in developing countries defies global commitments: an overview on Brazilian growth in consumption - Paulo Bernardo Neves e Castro; Daniel Aparecido da Silva Rodrigues; Hubert Mathias Peter Roeser; Aníbal da Fonseca Santiago; Robson José de Cássia Franco Afonso (Environmental Science and Pollution Research, 2020)

Assessing ecological function in the context of species recovery - H. Resit Akçakaya; Ana S. L. Rodrigues; David A. Keith; E. J. Milner‐Gulland; Eric W. Sanderson; Simon Hedges; David P. Mallon; Molly K. Grace; Barney Long; Erik Meijaard; P. J. Stephenson (Conservation Biology, 2020)
Species interactions matter to conservation. Setting an ambitious recovery target for a species requires considering the size, density, and demographic structure of its populations such that they fulfill the interactions, roles, and functions of the species in the ecosystems in which they are embedded. A recently proposed framework for an International Union for Conservation of Nature Green List of Species formalizes this requirement by defining a fully recovered species in terms of representation, viability, and functionality. Defining and quantifying ecological function from the viewpoint of species recovery is challenging in concept and application, but also an opportunity to insert ecological theory into conservation practice. We propose 2 complementary approaches to assessing a species’ ecological functions: confirmation (listing interactions of the species, identifying ecological processes and other species involved in these interactions, and quantifying the extent to which the species contributes to the identified ecological process) and elimination (inferring functionality by ruling out symptoms of reduced functionality, analogous to the red‐list approach that focuses on symptoms of reduced viability). Despite the challenges, incorporation of functionality into species recovery planning is possible in most cases and it is essential to a conservation vision that goes beyond preventing extinctions and aims to restore a species to levels beyond what is required for its viability. This vision focuses on conservation and recovery at the species level and sees species as embedded in ecosystems, influencing and being influenced by the processes in those ecosystems. Thus, it connects and integrates conservation at the species and ecosystem levels.

Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Attenuate Collagen-Induced Arthritis after Magnetic Targeting - Maria Fernanda Hornos Carneiro; Ana Rita T. Machado; Lusânia M. G. Antunes; Talita E. Souza; Victor A. Freitas; Luiz C. A. Oliveira; Jairo L. Rodrigues; Marcio C. Pereira; Fernando Barbosa (Biological Trace Element Research, 2020)

Effects of rumen-protected oil supplementation on finishing grazing beef cattle - Pedro Ivo José Lopes da Rosa e Silva; Joanis Tilemahos Zervoudakis; Luciano da Silva Cabral; Luciana Keiko Hatamoto-Zervoudakis; Lucien Bissi da Freiria; Yasmim Rodrigues Vilas Boas e Silva; Pedro Veiga Rodrigues Paulino; Pedro Paulo Tsuneda; Adriano Jorge Possamai (Tropical Animal Health and Production, 2020)

The Galactose-Binding Lectin Isolated from Vatairea macrocarpa Seeds Enhances the Effect of Antibiotics Against Staphylococcus aureus–Resistant Strain - Valdenice F. Santos; Maria S. Costa; Fábia F. Campina; Renato R. Rodrigues; Ana L. E. Santos; Felipe M. Pereira; Karla L. R. Batista; Rafael C. Silva; Raquel O. Pereira; Bruno A. M. Rocha; Henrique D. M. Coutinho; Claudener S. Teixeira (Probiotics and Antimicrobial Proteins, 2020)

Studies in Neotropical Araliaceae. I. Resurrection of the genus Sciodaphyllum P. Browne to accommodate most New World species previously included in Schefflera J. R. Forst. & G. Forst. - Porter P. Lowry II; Gregory M. Plunkett; M. Marcela Mora; Asunción Cano; Pedro Fiaschi; David G. Frodin; Roy E. Gereau; Álvaro Idárraga-Piedrahíta; Jáider Jiménez-Montoya; J. Moisés F. Mendoza; David A. Neill; Orlando Rivera-Diaz; et al. (Brittonia, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Molecular characterization of a germplasm bank of Platonia insignis Mart.: a fruit tree - D. N. Pena; E. F. Moura; S. M. Rodrigues; M. S. P. Oliveira; J. P. Sanches; M. F. Moura (Genetic Resources and Crop Evolution, 2020)

Do improved pastures enhance soil quality of cork oak woodlands in the Alentejo region (Portugal)? - A. R. Rodrigues; F. Costa e Silva; A. C. Correia; M. C. Bicho; M. Madeira; J. Coutinho (Agroforestry Systems, 2020)

Spatial and temporal assessment of the extreme and daily precipitation of the Tropical Rainfall Measuring Mission satellite in Northeast Brazil - Daniele Tôrres Rodrigues; Weber Andrade Gonçalves; Maria Helena Constantino Spyrides; Cláudio Moisés Santos e Silva (International Journal of Remote Sensing, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The antidepressant-like effect of guanosine is dependent on GSK-3β inhibition and activation of MAPK/ERK and Nrf2/heme oxygenase-1 signaling pathways - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Isabel Werle; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2019)

The Fitness and Economic Benefits of Rearing the Parasitoid Telenomus podisi Under Fluctuating Temperature Regime - N L Castellanos; A F Bueno; K Haddi; E C Silveira; H S Rodrigues; E Hirose; G Smagghe; E E Oliveira (Neotropical Entomology, 2019)

Performance of new flat fan nozzle design in spray deposition, penetration and control of soybean rust - Matheus Mereb Negrisoli; Carlos Gilberto Raetano; Diego Miranda de Souza; Felipe Matheus Santos e Souza; Laryssa Moreira Bernardes; Luciano Del Bem Junior; Danilo Morilha Rodrigues; Maria Marcia Pereira Sartori (European Journal of Plant Pathology, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Skeletal muscle miR-34a/SIRT1:AMPK axis is activated in experimental and human non-alcoholic steatohepatitis - André L. Simão; Marta B. Afonso; Pedro M. Rodrigues; Margarida Gama-Carvalho; Mariana V. Machado; Helena Cortez-Pinto; Cecília M. P. Rodrigues; Rui E. Castro (Journal of Molecular Medicine, 2019)

Generation and validation of genetic markers for the selection of carioca dry bean genotypes with the slow-darkening seed coat trait - Renata C. Alvares; Robert Stonehouse; Thiago L. P. O. Souza; Patrícia G. S. Melo; Phillip N. Miklas; Kirstin E. Bett; Leonardo C. Melo; Luana A. Rodrigues; Lorena L. Souza; Helton S. Pereira (Euphytica, 2019)

Phylogeography of eagle rays of the genus Aetobatus: Aetobatus narinari is restricted to the continental western Atlantic Ocean - João Bráullio L. Sales; Cintia Negrão de Oliveira; Wagner César Rosa dos Santos; Matheus Marcos Rotundo; Yrlene Ferreira; Jonathan Ready; Iracilda Sampaio; Claudio Oliveira; Vanessa P. Cruz; Raul E. Lara-Mendoza; Luis Fernando da Silva Rodrigues-Filho (Hydrobiologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Secretomic analysis of Beauveria bassiana related to cattle tick, Rhipicephalus microplus, infection - Lucélia Santi; Caio J. B. Coutinho-Rodrigues; Markus Berger; Lisete A. S. Klein; Eduardo M. De Souza; Rafael L. Rosa; Jorge A. Guimarães; John R. Yates; Wendell M. S. Perinotto; Vânia R. E. P. Bittencourt; Walter O. Beys-da-Silva (Folia Microbiologica, 2019)

Geostatistical stationary space-time covariance functions modeling of Yellow Sigatoka progress in banana crop - J. D. P. Rodrigues; M. C. Alves; A. S. Freitas; E. A. Pozza; M. S. Oliveira; H. J. P. Alves (Australasian Plant Pathology, 2019)

Resource partitioning between two young‐of‐year cownose rays Rhinoptera bonasus and R. brasiliensis within a communal nursery inferred by trophic biomarkers - Bianca de Sousa Rangel; Nigel E. Hussey; Aline D. Gomes; Alexandre Rodrigues; Luiz A. Martinelli; Renata Guimarães Moreira (Journal of Fish Biology, 2019)
Although interspecific trophic interactions plays a principal role within elasmobranch communal nurseries, little is known over variation in foraging strategies adopted by young‐of‐year of sympatric species. To test the hypothesis of dietary resource partitioning between batoids within a communal nursery, we investigated two cownose ray species, Rhinoptera bonasus and R. brasiliensis , which occur in heterospecific groups, a strategy predicted to increase survival and foraging success. Using two biochemical tracers, fatty acids (FA) and stable isotopes (δ 15 N and δ 13 C), the combined effects of maternal investment and the formation of heterospecific groups implying competition for, or partitioning of available food resources were investigated. Through univariate and multivariate analyses of biochemical tracers in several tissues (fin clip, muscle, liver, red blood cells; RBC) and plasma, our results revealed significant interspecific differences in tracers between the two species. Total FAs (∑saturated FA, ∑monounsaturated FA and ∑polyunsaturated FA) and trophic biomarkers ( i.e ., docosahexaenoic acid, arachidonic acid, oleic acid and δ 15 N) were the principle tracers responsible for the differences detected. These data revealed that R. brasiliensis was less enriched in physiologically important essential FAs than R. bonasus . Our findings suggest that these congeneric species differ in maternal investment strategy and moderately partition food resources over relatively fine spatial scales within a single nursery habitat to limit competition. These results provide further knowledge on the foraging strategies adopted by batoids in communal nursery areas, information that is required for improving spatial conservation and management planning.

Orofacial antinociceptive effect of sulphated polysaccharide from the marine algae Hypnea pseudomusciformis in rodents - Caio Átila Prata Bezerra Souza; Breytiner Amaro de Oliveira; Sacha Aubrey Alves Rodrigues Santos; Francisco Lucas Alves Batista; Francisco Regivânio Nascimento Andrade; Eugênio Januário Ramos Neto; José de Maria Albuquerque de Melo Júnior; Francisco Rogenio da Silva Mendes; Lana Karine Vasconcelos Barroso; Kirley Marques Canuto; Francisco Ernani Alves Magalhães; Angelo Roncalli Alves e Silva; et al. (Inflammopharmacology, 2019)

Regulation of cell wall development in Brachypodium distachyon in vitro as affected by cytokinin and gas exchange - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; E. A. Fortini; A. C. F. Cruz; M. G. C. Costa; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Differences in food webs and trophic states of Brazilian tropical humid and semi-arid shallow lakes: implications of climate change - Rosemberg Fernandes Menezes; José Luiz Attayde; Sarian Kosten; Gissell Lacerot; Leonardo Coimbra e Souza; Luciana S. Costa; Leonel da S. L. Sternberg; Anna Claudia dos Santos; Michele de Medeiros Rodrigues; Erik Jeppesen (Hydrobiologia, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Immunological impact of graphene oxide sheets in the abdominal cavity is governed by surface reactivity - Artur Filipe Rodrigues; Leon Newman; Dhifaf A. Jasim; Isabella A. Vacchi; Cécilia Ménard-Moyon; Livia E. Crica; Alberto Bianco; Kostas Kostarelos; Cyrill Bussy (Archives of Toxicology, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Small scale temporal patterns of recruitment and hatching of Atlantic horse mackerel (L.) at a nearshore reef area - Maria Klein; Elisabeth Van Beveren; Diana Rodrigues; Ester A. Serrão; Jennifer E. Caselle; Emanuel J. Gonçalves; Rita Borges (Fisheries Oceanography, 2018)
Atlantic horse mackerel ( Trachurus trachurus , Linnaeus, 1758) is a highly exploited species, common throughout the North‐East Atlantic. As a pelagic‐neritic fish it typically occurs over the shelf from the surface to 200 m deep on sandy bottoms. Most research has focused on distributions of adults or early life stages (eggs and larvae) of this species in offshore waters and only a few studies have reported the occurrence of early stages near the coast. However, these nearshore environments might be important for the early growth and survival of the Atlantic horse mackerel. In addition, little is known on how environmental processes might affect the early stages of this species. Here, we monitored weekly recruitment of horse mackerel to artificial substrates ( SMURFS ) deployed near the coast at both the surface and near the bottom, and back‐calculated hatching cohorts. The relationship of both recruitment and hatching patterns with environmental factors was investigated. From a total of 2,515 fish, 2,490 (99%) recruited to surface SMURFS . A GAM and GAMM analysis of the recruitment and hatching patterns, respectively, revealed a strong relationship with the lunar cycle and upwelling. Both recruitment and hatching showed lunar periodicity, with peaks near the new moon and revealed to be influenced negatively by upwelling. This study suggests that the nearshore environment might be an important nursery area for post‐larval and early juvenile Atlantic horse mackerel.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Reproductive output of the ornamental shrimp Lysmata vittata (Stimpson, 1860) (Decapoda: Caridea) in wild populations and under different maturation diets - Andréa Santos e Almeida; Samara de Paiva Barros-Alves; Gustavo Luis Hirose; Douglas Fernandes Rodrigues Alves (Invertebrate Reproduction & Development, 2018)

Histopathological Evaluation of Combined Impacts of the Synthetic Progestin Levonorgestrel and Temperature on the Female Zebrafish Maturation Using a Semi-quantitative Grading Analysis—Is it Enough? - P. G. Cardoso; D. Rodrigues; T. V. Madureira; M. J. Rocha; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Mitochondrial genome analysis in penile carcinoma - L. F. Araujo; A. T. Terra; C. T. G. Sares; C. F. R. Sobreira; E. F. Faria; R. D. Machado; A. A. Rodrigues; V. F. Muglia; W. A. Silva; R. B. Reis (Molecular Biology Reports, 2018)

Biomarkers in Spinal Cord Injury: from Prognosis to Treatment - Leonardo Fonseca Rodrigues; Vivaldo Moura-Neto; Tania Cristina Leite de Sampaio e Spohr (Molecular Neurobiology, 2018)

Microwave-assisted synthesis of borneol esters and their antimicrobial activity - Aline Teixeira Maciel e Silva; Vinícius Viana Pereira; Jacqueline Aparecida Takahashi; Roqueline Rodrigues Silva; Lucienir Pains Duarte (Natural Product Research, 2018)

Pollen morphology of the Poaceae: implications of the palynological and paleoecological records of the southeastern Amazon in Brazil - José Tasso Felix Guimarães; Léa Maria Medeiros Carreira; Ronnie Alves; Pedro Walfir Martins e Souza Filho; Tereza Cristina Giannini; Higor Jardim Macambira; Edilson Freitas da Silva; Anna Christina Rio Dias; Carla Bastista da Silva; Luiza de Araújo Romeiro; Tarcísio Magevski Rodrigues (Palynology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Vulnerability associated with “symptoms similar to those of mercury poisoning” in communities from Xingu River, Amazon basin - Flávio Mnaoel Rodrigues Da Silva-Junior; Ritta M. Oleinski; Antonia E. S. Azevedo; Kátia C. M. C. Monroe; Marina Dos Santos; Tatiane Britto Da Silveira; Adrianne Maria Netto De Oliveira; Maria Cristina Flores Soares; Tatiana Da Silva Pereira (Environmental Geochemistry and Health, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

Treatment with pentylenetetrazole (PTZ) and 4-aminopyridine (4-AP) differently affects survival, locomotor activity, and biochemical markers in Drosophila melanogaster - Deividi C. S. Soares; José L. R. Portela; Daniel H. Roos; Nathane R. Rodrigues; Karen K. Gomes; Giulianna E. Macedo; Thais Posser; Jeferson L. Franco; Waseem Hassan; Robson L. Puntel (Molecular and Cellular Biochemistry, 2018)

Lignin and cellulose synthesis and antioxidative defense mechanisms are affected by light quality in Brachypodium distachyon - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; A. C. F. Cruz; E. A. Fortini; F. T. S. Nogueira; E. Romanel; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Development of Cleruchoides noackae, an egg-parasitoid of Thaumastocoris peregrinus, in eggs laid on different substrates, with different ages and post-cold storage - Leonardo Rodrigues Barbosa; Ângelo Peruffo Rodrigues; Lohana Neves de Souza; Luís Amilton Foerster; Amanda Rodrigues de Souza; Bárbara Monteiro de Castro e Castro; Carlos Frederico Wilcken; José Cola Zanuncio (BioControl, 2018)

Embryonic and larval development and fatty‐acid profile of Epinephelus marginatus spawned in captivity: tools applied to captive rearing - P. H. Mello; B. C. Araújo; M. F. Campos; J. A. Rodrigues‐Filho; C. E. O. Garcia; R. G. Moreira (Journal of Fish Biology, 2018)
Development, ontogeny of the digestive system and the fatty‐acid (FA) profile, were analysed during development of Epinephelus marginatus . Larvae were analysed 7 and 17 days post fertilization (dpf) to evaluate fatty‐acid profile and morphological variables, respectively. Epinephelus marginatus larvae have relatively slow development of digestive structures, but were able to capture, ingest and digest prey by 5 dpf. Eggs were composed of high percentages of polyunsaturated fatty acids (PUFA) in phospholipids. The percentage of n3 PUFAs was higher than n6, especially docosahexaenoic acid (DHA), which exhibited higher levels compared with other marine species during the first 3 days of development, both in terms of phospholipids and triglycerides. The larvae present a high content of docosahexaenoic acid–eicosapentaenoic acid (DHA–EPA) and, during this phase, live food of small size was required (copepods or SS‐strain Brachionus rotundiformes ), enriched with DHA–EPA. These results may guide future studies on the contribution of FAs required during this stage of the life cycle of E. marginatus , to advance knowledge of the use of these FAs throughout ontogeny and contribute to the culture of this species commercial production or restocking.

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

Area-wide spatial survey of the likelihood of insecticide control failure in the neotropical brown stink bug Euschistus heros - Edmar S. Tuelher; Éder H. da Silva; Hígor S. Rodrigues; Edson Hirose; Raul Narciso C. Guedes; Eugênio E. Oliveira (Journal of Pest Science, 2018)

The invisibility of fisheries in the process of hydropower development across the Amazon - Carolina Rodrigues da Costa Doria; Simone Athayde; Elineide E. Marques; Maria Alice Leite Lima; Jynessa Dutka-Gianelli; Mauro Luis Ruffino; David Kaplan; Carlos E. C. Freitas; Victoria N. Isaac (Ambio, 2017)

Diversity and succession of pelagic microorganism communities in a newly restored Illinois River floodplain lake - Michael J. Lemke; Sara F. Paver; Keenan E. Dungey; Luiz Felipe M. Velho; Angela D. Kent; Luzia Cleide Rodrigues; Doyn M. Kellerhals; Michelle R. Randle (Hydrobiologia, 2017)

Why experiment with success? Opportunities and risks in applying assessment and adaptive management to the Emiquon floodplain restoration project - Richard E. Sparks; K. Douglas Blodgett; Andrew F. Casper; Heath M. Hagy; Michael J. Lemke; Luiz Felipe Machado Velho; Luzia Cleide Rodrigues (Hydrobiologia, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Spittlebugs (Hemiptera: Cercopidae) and their host plants: a strategy for pasture diversification - R. Alvarenga; Alexander M. Auad; Jair C. Moraes; Sandra E. B. Silva; Brunno S. Rodrigues; Giani B. Silva (Applied Entomology and Zoology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Wax Removal and Diamondback Moth Performance in Collards Cultivars - G. A. Silva; R. M. Pereira; N. Rodrigues-Silva; T. C. Souza; D. O. Ferreira; E. A. Queiroz; G. A. R. Silva; M. C. Picanço (Neotropical Entomology, 2017)

Study of macro and microelements in fish from the Cienfuegos Bay. Relationship with its content in sediments - M. Peña-Icart; E. Rodrigues Pereira-Filho; L. Lopes Fialho; J. A. Nóbrega; C. Alonso-Hernández; Y. Bolaños-Alvarez; A. Muñoz-Caravaca; M. S. Pomares-Alfonso (Environmental Monitoring and Assessment, 2017)

Chronic Treatment with Paraquat Induces Brain Injury, Changes in Antioxidant Defenses System, and Modulates Behavioral Functions in Zebrafish - Mauro E. Nunes; Talise E. Müller; Marcos M. Braga; Barbara D. Fontana; Vanessa A. Quadros; Aline Marins; Cíntia Rodrigues; Charlene Menezes; Denis B. Rosemberg; Vania Lucia Loro (Molecular Neurobiology, 2017)

Comparative study of urban development and groundwater condition in coastal areas of Buenos Aires, Argentina - Leandro Rodrigues Capítulo; Silvina C. Carretero; Eduardo E. Kruse (Hydrogeology Journal, 2017)

Identification of potential areas for wild palm cultivation in the Republic of Benin through remote sensing and ecological niche modeling - Rodrigue Idohou; A. Townsend Peterson; Achille E. Assogbadjo; Romaric L. Vihotogbe; Elie Padonou; Romain Glèlè Kakaï (Genetic Resources and Crop Evolution, 2017)

Mice exposure to tannery effluents changes their olfactory capacity, and their response to predators and to the inhibitory avoidance test - Bruna de Oliveira Mendes; Letícia Martins Rabelo; Bianca Costa e Silva; Joyce Moreira de Souza; André Luis da Silva Castro; Anderson Rodrigo da Silva; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Environmental Science and Pollution Research, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Inheritance of resistance to Meloidogyne enterolobii in Psidium guajava x P. guineense hybrid - Soniane Rodrigues da Costa; Carlos Antonio Fernandes Santos; Jose Mauro da Cunha e Castro (European Journal of Plant Pathology, 2017)

Linear and Nonlinear Gait Features in Older Adults Walking on Inclined Surfaces at Different Speeds - Marcus Fraga Vieira; Fábio Barbosa Rodrigues; Gustavo Souto de Sá e Souza; Rina Márcia Magnani; Georgia Cristina Lehnen; Adriano O. Andrade (Annals of Biomedical Engineering, 2017)

P transformations in cacao agroforests soils in the Atlantic forest region of Bahia, Brazil - S. Aleixo; A. C. Gama-Rodrigues; M. G. Costa; M. V. S. Sales; E. F. Gama-Rodrigues; J. R. B. Marques (Agroforestry Systems, 2017)

Larval development and allometric growth of the black‐faced blenny Tripterygion delaisi - F. N. Solomon; D. Rodrigues; E. J. Gonçalves; E. A. Serrão; R. Borges (Journal of Fish Biology, 2017)
Larval development and allometric growth patterns of the black‐faced blenny Tripterygion delaisi are described from a larval series (body length, L B = 3·30–12·10 mm) caught by light traps at the Arrábida Marine Park, Portugal. Larvae of T. delaisi possess distinctive morphometric and meristic characteristics which can be used to identify this species from related taxa. Pigmentation is sparse but characteristic, consisting of pigmented eyes, gas bladder pigmentation in the dorsal region, anal pigmentation and a row of regularly spaced postanal ventral melanophores. This pattern is present from as early as the yolk‐sac stage and persists throughout all stages with just the addition of head and caudal pigmentation during the flexion and postflexion stages, respectively. The majority of fin development (with the exception of the caudal fin), occurs in the later stages of development. Myomere counts range between 37 and 45 for all stages. Growth is allometric during larval development. When inflexion points of growth were detected, growth was found to be biphasic with the inflexion points occurring within a very narrow range of L B (8·70–8·90 mm) close to the mean ± s.d. (9·44 ± 1·48 mm L B ) of postflexion larvae. Considering allometric growth patterns and ontogenetic descriptions together, the first developmental phase includes the preflexion and flexion stage larvae, while the second phase characterises the postflexion larvae prior to the transition from larvae to juvenile.

Influence of forest structure upon the diversity and composition of edaphic diplopods - Patrícia E. S. Rodrigues; Luiz Ernesto Costa-Schmidt; Ricardo Ott; Everton Nei Lopes Rodrigues (Journal of Insect Conservation, 2017)

New technologies in value addition to the thin stillage from corn-to-ethanol process - Cristiano E. Rodrigues Reis; Aravindan Rajendran; Bo Hu (Reviews in Environmental Science and Bio/Technology, 2017)

Extraction and electrophoretic analysis of large dsRNAs from desiccated plant tissues infected with plant viruses and biotrophic fungi - S. Khankhum; C. Escalante; E. Rodrigues de Souto and; R. A. Valverde (European Journal of Plant Pathology, 2017)

Space-time modeling for post-fire vegetation recovery - Lucia Paci; Alan E. Gelfand; María Asunción Beamonte; Marcos Rodrigues; Fernando Pérez-Cabello (Stochastic Environmental Research and Risk Assessment, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Microbial diversification of Diels–Alder cycloadducts by whole cells of Penicillium brasilianum - Zia Ud Din; Taicia P. Fill; M. Carolina Donatoni; Carolina A. A. dos Santos; Timothy J. Brocksom; E. Rodrigues-Filho (Molecular Diversity, 2016)

Diet‐related gut bacterial dysbiosis correlates with impaired development, increased mortality and Nosema disease in the honeybee ( Apis mellifera ) - Patrick W. Maes; Pedro A. P. Rodrigues; Randy Oliver; Brendon M. Mott; Kirk E. Anderson (Molecular Ecology, 2016)
Dysbiosis, defined as unhealthy shifts in bacterial community composition, can lower the colonization resistance of the gut to intrinsic pathogens. Here, we determined the effect of diet age and type on the health and bacterial community composition of the honeybee ( Apis mellifera ). We fed newly emerged bees fresh or aged diets, and then recorded host development and bacterial community composition from four distinct regions of the hosts’ digestive tract. Feeding fresh pollen or fresh substitute, we found no difference in host mortality, diet consumption, development or microbial community composition. In contrast, bees fed aged diets suffered impaired development, increased mortality and developed a significantly dysbiotic microbiome. The consumption of aged diets resulted in a significant reduction in the core ileum bacterium Snodgrassella alvi and a corresponding increase in intrinsic pathogen Frischella perrara . Moreover, the relative abundance of S. alvi in the ileum was positively correlated with host survival and development. The inverse was true for both F. perrara and Parasacharibacter apium . Collectively, our findings suggest that the early establishment of S. alvi is associated with healthy nurse development and potentially excludes F. perrara and P. apium from the ileum. Although at low abundance, establishment of the common midgut pathogen Nosema spp. was significantly associated with ileum dysbiosis and associated host deficiencies. Moreover, dysbiosis in the ileum was reflected in the rectum, mouthparts and hypopharyngeal glands, suggesting a systemic host effect. Our findings demonstrate that typically occurring alterations in diet quality play a significant role in colony health and the establishment of a dysbiotic gut microbiome.

Evaluating genotoxic risks in Brazilian public health agents occupationally exposed to pesticides: a multi-biomarker approach - Fernanda Craveiro Franco; Alessandro Arruda Alves; Fernanda Ribeiro Godoy; Juliana Boaventura Avelar; Douglas Dantas Rodrigues; Thays Millena Alves Pedroso; Aparecido Divino da Cruz; Fausto Nomura; Daniela de Melo e Silva (Environmental Science and Pollution Research, 2016)

Guanosine and its role in neuropathologies - Luis E. B. Bettio; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2016)

Distribution patterns of the ghost crab Ocypode cursor on sandy beaches of a tropical island in the Cabo Verde archipelago, Eastern Central Atlantic - E Rodrigues; R Freitas; N de C Delgado; A Soares-Gomes (African Journal of Marine Science, 2016)

Agmatine, by Improving Neuroplasticity Markers and Inducing Nrf2, Prevents Corticosterone-Induced Depressive-Like Behavior in Mice - Andiara E. Freitas; Javier Egea; Izaskun Buendia; Vanessa Gómez-Rangel; Esther Parada; Elisa Navarro; Ana Isabel Casas; Aneta Wojnicz; José Avendaño Ortiz; Antonio Cuadrado; Ana Ruiz-Nuño; Ana Lúcia S. Rodrigues; et al. (Molecular Neurobiology, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Biological activities of ophiobolin K and 6-epi-ophiobolin K produced by the endophytic fungus Aspergillus calidoustus - Camila Rodrigues de Carvalho; Mariana de Lourdes Almeida Vieira; Charles L. Cantrell; David E. Wedge; Tânia M.A. Alves; Carlos Leomar Zani; Raphael Sanzio Pimenta; Policarpo A. Sales Junior; Silvane M.F. Murta; Alvaro J. Romanha; Carlos Augusto Rosa; Luiz H. Rosa (Natural Product Research, 2016)

Ferulic acid ethyl ester diminished Complete Freund’s Adjuvant-induced incapacitation through antioxidant and anti-inflammatory activity - Francisco Valmor Macedo Cunha; Bruno de Sousa Gomes; Benedito de Sousa Neto; Alana Rodrigues Ferreira; Damião Pergentino de Sousa; Maria do Carmo de Carvalho e Martins; Francisco de Assis Oliveira (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Fungi associated with rocks of the A tacama D esert: taxonomy, distribution, diversity, ecology and bioprospection for bioactive compounds - Vívian N. Gonçalves; Charles L. Cantrell; David E. Wedge; Mariana C. Ferreira; Marco Aurélio Soares; Melissa R. Jacob; Fabio S. Oliveira; Douglas Galante; Fabio Rodrigues; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; et al. (Environmental Microbiology, 2016)
Summary This study assessed the diversity of cultivable rock‐associated fungi from A tacama D esert. A total of 81 fungal isolates obtained were identified as 29 Ascomycota taxa by sequencing different regions of DNA. C ladosporium halotolerans , P enicillium chrysogenum and P enicillium cf. citrinum were the most frequent species, which occur at least in four different altitudes. The diversity and similarity indices ranged in the fungal communities across the latitudinal gradient. The F isher‐α index displayed the higher values for the fungal communities obtained from the siltstone and fine matrix of pyroclastic rocks with finer grain size, which are more degraded. A total of 23 fungal extracts displayed activity against the different targets screened. The extract of P . chrysogenum afforded the compounds α‐linolenic acid and ergosterol endoperoxide, which were active against C ryptococcus neoformans and methicillin‐resistance S taphylococcus aureus respectively. Our study represents the first report of a new habitat of fungi associated with rocks of the A tacama D esert and indicated the presence of interesting fungal community, including species related with saprobes, parasite/pathogen and mycotoxigenic taxa. The geological characteristics of the rocks, associated with the presence of rich resident/resilient fungal communities suggests that the rocks may provide a favourable microenvironment fungal colonization, survival and dispersal in extreme conditions.

Changes in Cd and Zn bioavailability upon an experimental resuspension of highly contaminated coastal sediments from a tropical estuary - Christiane N. Monte; Ana P. C. Rodrigues; Renato C. Cordeiro; Aline S. Freire; Ricardo E. Santelli; W. Machado (Sustainable Water Resources Management, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

Erratum to: Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Habitat associations and behavioural patterns of Symphodus spp. (Pisces: Labridae) - Diana Rodrigues; Bárbara Horta e Costa; Henrique N. Cabral; Emanuel J. Gonçalves (acta ethologica, 2015)

Contribution to the study of deep coastal detritic bottoms: the algal communities of the continental shelf off the Balearic Islands, Western Mediterranean - S. JOHER; E. BALLESTEROS; C. RODRIGUES-PRIETO (Mediterranean Marine Science, 2015)
Three main algal-dominated coastal detritic communities from the continental shelf off Mallorca and Menorca (Balearic Islands, Western Mediterranean) are described herein: maërl beds dominated by Spongites fruticulosus and forests of Laminaria rodriguezii located in the Menorca channel, and Peyssonnelia inamoena beds found along the Southern coast of Menorca. There seems to be a gradient of disturbance from the highly disturbed Peyssonnelia beds to the almost undisturbed L. rodriguezii forests. Whether this gradient is the result of current and past anthropogenic pressure (e.g. trawling intensity) or is driven by natural environmental factors needs further assessment. Finally, the location of the target communities by means of ROV dives combined with the use of a Box-Corer dredge and beam trawl proved to be a good methodology in the study of the composition and structure of these deep water detritic communities.

Resistance to Cowpea aphid-borne mosaic virus in species and hybrids of Passiflora: advances for the control of the passion fruit woodiness disease in Brazil - Eileen Azevedo Santos; Alexandre Pio Viana; Josie Cloviane de Oliveira Freitas; Fernando Higino de Lima e Silva; Rosana Rodrigues; Marcelo Eiras (European Journal of Plant Pathology, 2015)

Linking Brazil’s food security policies to agricultural change - Johan A. Oldekop; M. Jahi Chappell; Felipe E. Borges Peixoto; Adriano Pereira Paglia; Marina Schmoeller do Prado Rodrigues; Karl L. Evans (Food Security, 2015)

Respecification of structural equation models for the P cycle in tropical soils - M. V. S. Sales; A. C. Gama-Rodrigues; N. B. Comerford; W. P. Cropper; E. F. Gama-Rodrigues; P. H. G. Oliveira (Nutrient Cycling in Agroecosystems, 2015)

Disease alters macroecological patterns of N orth A merican bats - Winifred F. Frick; Sébastien J. Puechmaille; Joseph R. Hoyt; Barry A. Nickel; Kate E. Langwig; Jeffrey T. Foster; Kate E. Barlow; Tomáš Bartonička; Dan Feller; Anne‐Jifke Haarsma; Carl Herzog; Ivan Horáček; et al. (Global Ecology and Biogeography, 2015)
Aim We investigated the effects of disease on the local abundances and distributions of species at continental scales by examining the impacts of white‐nose syndrome, an infectious disease of hibernating bats, which has recently emerged in N orth A merica. Location N orth A merica and E urope. Methods We used four decades of population counts from 1108 populations to compare the local abundances of bats in N orth A merica before and after the emergence of white‐nose syndrome to the situation in E urope, where the disease is endemic. We also examined the probability of local extinction for six species of hibernating bats in eastern N orth A merica and assessed the influence of winter colony size prior to the emergence of white‐nose syndrome on the risk of local extinction. Results White‐nose syndrome has caused a 10‐fold decrease in the abundance of bats at hibernacula in N orth A merica, eliminating large differences in species abundance patterns that existed between E urope and N orth A merica prior to disease emergence. White‐nose syndrome has also caused extensive local extinctions (up to 69% of sites in a single species). For five out of six species, the risk of local extinction was lower in larger winter populations, as expected from theory, but for the most affected species, the northern long‐eared bat ( M yotis septentrionalis ), extinction risk was constant across winter colony sizes, demonstrating that disease can sometimes eliminate numerical rarity as the dominant driver of extinction risk by driving both small and large populations extinct. Main conclusions Species interactions, including disease, play an underappreciated role in macroecological patterns and influence broad patterns of species abundance, occurrence and extinction.

Agmatine Induces Nrf2 and Protects Against Corticosterone Effects in Hippocampal Neuronal Cell Line - Andiara E. Freitas; Javier Egea; Izaskun Buendía; Elisa Navarro; Patricia Rada; Antonio Cuadrado; Ana Lúcia S. Rodrigues; Manuela G. López (Molecular Neurobiology, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

Nellore cows and their calves during the lactation period: performance, intake, milk composition, and total apparent digestibility - Luiz Fernando Costa e Silva; Terry Eugene Engle; Sebastião de Valadares Filho; Polyana Pizzi Rotta; Faider Alberto Castaño Villadiego; Flávia Adriane Sales Silva; Edilane Costa Martins; Luis Henrique Rodrigues Silva; Mário Fonseca Paulino (Tropical Animal Health and Production, 2015)

The effect of conventional mechanical periodontal treatment on red complex microorganisms and clinical parameters in Down syndrome periodontitis patients: a pilot study - M. H. Tanaka; T. O. Rodrigues; L. S. Finoti; S. R. L. Teixeira; M. P. A. Mayer; R. M. Scarel-Caminaga; E. M. A. Giro (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Occurrence and analysis of endocrine-disrupting compounds in a water supply system - A. R. M Carvalho; V. V. Cardoso; A. Rodrigues; E. Ferreira; M. J. Benoliel; E. A. Duarte (Environmental Monitoring and Assessment, 2015)

Escovopsis trichodermoides sp. nov., isolated from a nest of the lower attine ant Mycocepurus goeldii - Virginia E. Masiulionis; Marta N. Cabello; Keith A. Seifert; Andre Rodrigues; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2015)

Ecological literacy and beyond: Problem-based learning for future professionals - Thomas M. Lewinsohn; José Luiz Attayde; Carlos Roberto Fonseca; Gislene Ganade; Leonardo Ré Jorge; Johannes Kollmann; Gerhard E. Overbeck; Paulo Inácio Prado; Valério D. Pillar; Daniela Popp; Pedro L. B. da Rocha; Wesley Rodrigues Silva; et al. (Ambio, 2015)

Ichthyofauna of the Selvagens Islands. Do small coastal areas show high species richness in the northeastern Atlantic? - Frederico Almada; David Abecasis; David Villegas-Ríos; Sofia Henriques; Miguel P. Pais; Marisa Batista; Bárbara Horta e Costa; Joana Martins; Inês Tojeira; Nuno Vasco Rodrigues; Ricardo Araújo; Miguel Souto; et al. (Marine Biology Research, 2015)

Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Nutrient stocks in litterfall and litter in cocoa agroforests in Brazil - A. G. Fontes; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. V. S. Sales; M. G. Costa; R. C. R. Machado (Plant and Soil, 2014)

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

Acute ethanol intake induces mitogen-activated protein kinase activation, platelet-derived growth factor receptor phosphorylation, and oxidative stress in resistance arteries - Natália A. Gonzaga; Glaucia E. Callera; Alvaro Yogi; André S. Mecawi; José Antunes-Rodrigues; Regina H. Queiroz; Rhian M. Touyz; Carlos R. Tirapelli (Journal of Physiology and Biochemistry, 2014)

Stability of a Neotropical microrefugium during climatic instability - Vincent Montade; Marie‐Pierre Ledru; Julien Burte; Eduardo Sávio Passos Rodrigues Martins; Christiano Franco Verola; Itayguara Ribeiro da Costa; Francisco Hilder Magalhães e Silva (Journal of Biogeography, 2014)
Aim The primary objectives of this study were (1) to assess, in the light of palaeoecological reconstruction, the climate stability hypothesis used by evolutionary biologists to explain high diversity in historically stable areas, and (2) to identify the response mechanisms of a tropical rain forest microrefugium to climatic variability. Location North‐eastern Brazil, Serra de Maranguape. Methods Vegetation and climatic changes were reconstructed using a pollen record in a sediment core from a forest hollow, and the chronology was based on accelerator mass spectrometry radiocarbon analyses. Results Past vegetation dynamics consisted of three main forest types, shown by major compositional changes in rain forest assemblages between 5000 and 1000 cal. yr bp . Dense ombrophilous forest was abruptly replaced by heliophilous early successional tree taxa at 4275 cal. yr bp . These early successional tree taxa were established over a period of c. 100 years, and their dominance lasted for c. 750 years and was associated with dry conditions until 3525 cal. yr bp . Subsequently, the expansion of secondary successional tree taxa over a period of c. 550 years enabled the recovery of ombrophilous forest. Main conclusions The vegetation changes in the Serra de Maranguape provide evidence for the high sensitivity of this rain forest microrefugium to climatic variability on a multidecadal to millennial time‐scale during the mid‐ to late Holocene. Despite the substantial compositional and climatic changes, this microrefugium apparently was continuously forested and responded to climatic instability by recruiting key species to its highly diverse stock. This evidence helps to address the joint concerns of evolutionary biologists and palaeoecologists regarding how forests can persist during periods of climatic variability by showing that some tropical regions can remain continuously forested despite reorganization during abrupt and short‐term climatic changes.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Cold impact and acclimation response of Coffea spp. plants - J. C. Ramalho; F. M. DaMatta; A. P. Rodrigues; P. Scotti-Campos; I. Pais; P. Batista-Santos; F. L. Partelli; A. Ribeiro; F. C. Lidon; A. E. Leitão (Theoretical and Experimental Plant Physiology, 2014)

Lectin of Abelmoschus esculentus (okra) promotes selective antitumor effects in human breast cancer cells - Leonardo G. Monte; Tatiane Santi-Gadelha; Larissa B. Reis; Elizandra Braganhol; Rafael F. Prietsch; Odir A. Dellagostin; Rodrigo Rodrigues e Lacerda; Carlos A. A. Gadelha; Fabricio R. Conceição; Luciano S. Pinto (Biotechnology Letters, 2014)

Effect of forced aeration on citric acid production by Aspergillus sp. mutants in SSF - Cristine Rodrigues; Luciana P. S. Vandenberghe; Wilerson Sturm; Dario E. A. Dergint; Michele Rigon Spier; Júlio Cesar de Carvalho; Carlos R. Soccol (World Journal of Microbiology and Biotechnology, 2013)

Interaction of warm acclimation, low salinity, and trophic fluoride on plasmatic constituents of the Antarctic fish Notothenia rossii Richardson, 1844 - E. Rodrigues; M. Feijó-Oliveira; G. S. Vani; C. N. K. Suda; C. S. Carvalho; L. Donatti; H. P. Lavrado; E. Rodrigues (Fish Physiology and Biochemistry, 2013)

Urban population genetics of slum‐dwelling rats ( R attus norvegicus ) in S alvador, B razil - Brittney Kajdacsi; Federico Costa; Chaz Hyseni; Fleur Porter; Julia Brown; Gorete Rodrigues; Helena Farias; Mitermayer G. Reis; James E. Childs; Albert I. Ko; Adalgisa Caccone (Molecular Ecology, 2013)
Throughout the developing world, urban centres with sprawling slum settlements are rapidly expanding and invading previously forested ecosystems. Slum communities are characterized by untended refuse, open sewers and overgrown vegetation, which promote rodent infestation. N orway rats ( R attus norvegicus ) are reservoirs for epidemic transmission of many zoonotic pathogens of public health importance. Understanding the population ecology of R . norvegicus is essential to formulate effective rodent control strategies, as this knowledge aids estimation of the temporal stability and spatial connectivity of populations. We screened for genetic variation, characterized the population genetic structure and evaluated the extent and patterns of gene flow in the urban landscape using 17 microsatellite loci in 146 rats from nine sites in the city of S alvador, B razil. These sites were divided between three neighbourhoods within the city spaced an average of 2.7 km apart. Surprisingly, we detected very little relatedness among animals trapped at the same site and found high levels of genetic diversity, as well as structuring across small geographical distances. Most F ST comparisons among sites were statistically significant, including sites R . norvegicus in S alvador, linked to the heterogeneous urban landscape. Future rodent control measures need to take into account the spatial and temporal linkage of rat populations in S alvador, as revealed by genetic data, to develop informed eradication strategies.

In vitro exploration of potential mechanisms of toxicity of the human hepatotoxic drug fenclozic acid - Alison V. M. Rodrigues; Helen E. Rollison; Scott Martin; Sunil Sarda; Timothy Schulz-Utermoehl; Simone Stahl; Frida Gustafsson; Julie Eakins; J. Gerry Kenna; Ian D. Wilson (Archives of Toxicology, 2013)

Genetic and QTL analyses of yield and a set of physiological traits in pepper - N. A. Alimi; M. C. A. M. Bink; J. A. Dieleman; M. Nicolaï; M. Wubs; E. Heuvelink; J. Magan; R. E. Voorrips; J. Jansen; P. C. Rodrigues; G. W. A. M. van der Heijden; A. Vercauteren; et al. (Euphytica, 2013)

Effect of three feeding management systems on some reproductive parameters of Scorpion mud turtles (Kinosternon scorpioides) in Brazil - Jamile da Costa Araújo; Priscila Vieira e Rosa; Maria das Dores Correia Palha; Paulo Borges Rodrigues; Rilke Tadeu Fonseca de Freitas; Alanna do Socorro Lima da Silva (Tropical Animal Health and Production, 2013)

Myrsine parvifolia (Primulaceae) in sandy coastal plains marginal to Atlantic rainforest: a case of pollination by wind or by both wind and insects? - Angela Arruda E. Albuquerque; Heloisa Alves de Lima; Vania Gonçalves-Esteves; Cristine Rodrigues Benevides; Ana Tereza Araújo Rodarte (Brazilian Journal of Botany, 2013)

Isolation and characterization of 18 microsatellites for Lycengraulis grossidens (Pisces: Clupeiformes) - Ana C. G. Mai; João P. Vieira; Alicia A. Plavan; Marcelo F. Nobrega; Leonardo E. Moraes; Fábio L. Rodrigues; Luis F. Marins (Conservation Genetics Resources, 2013)

Development of Probiotic Tablets Using Microparticles: Viability Studies and Stability Studies - J. P. Sousa e Silva; Sérgio C. Sousa; Paulo Costa; Emília Cerdeira; Maria H. Amaral; José Sousa Lobo; Ana M. Gomes; Maria M. Pintado; Dina Rodrigues; Teresa Rocha-Santos; Ana C. Freitas (AAPS PharmSciTech, 2013)

Responses in root growth, nitrogen metabolism and nutritional quality in Brachiaria with the use of thiamethoxam - Willian Rodrigues Macedo; Gisele Machado Fernandes; Rosana Aparecida Possenti; George Rodrigues Lambais; Paulo Roberto de Camargo e Castro (Acta Physiologiae Plantarum, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Effects of Pimenta pseudocaryophyllus (Gomes) L. R. Landrum, on Melanized and Non-melanized Cryptococcus neoformans - Orionalda de Fátima Lisboa Fernandes; Carolina Rodrigues Costa; Ruy de Souza Lino Junior; Marina Clare Vinaud; Lúcia Kioko Hasimoto e Souza; Joelma Abadia Marciano de Paula; Maria do Rosário Rodrigues Silva (Mycopathologia, 2012)

Changes in Liver Proteome Expression of Senegalese Sole (Solea senegalensis) in Response to Repeated Handling Stress - Odete D. Cordeiro; Tomé S. Silva; Ricardo N. Alves; Benjamin Costas; Tune Wulff; Nadège Richard; Mahaut de Vareilles; Luís E. C. Conceição; Pedro M. Rodrigues (Marine Biotechnology, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

Dietary Lysine Imbalance Affects Muscle Proteome in Zebrafish (Danio rerio): A Comparative 2D-DIGE Study - Mahaut de Vareilles; Luis E. C. Conceição; Pedro Gómez-Requeni; Katerina Kousoulaki; Nadège Richard; Pedro M. Rodrigues; Kari E. Fladmark; Ivar Rønnestad (Marine Biotechnology, 2012)

Carbon, nitrogen, organic phosphorus, microbial biomass and N mineralization in soils under cacao agroforestry systems in Bahia, Brazil - F. C. Zaia; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. K. S. Moço; A. G. Fontes; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2012)

Seasonal sea ice cover as principal driver of spatial and temporal variation in depth extension and annual production of kelp in Greenland - Dorte Krause‐Jensen; Núria Marbà; Birgit Olesen; Mikael K. Sejr; Peter Bondo Christensen; João Rodrigues; Paul E. Renaud; Thorsten J.S. Balsby; Søren Rysgaard (Global Change Biology, 2012)
We studied the depth distribution and production of kelp along the Greenland coast spanning Arctic to sub‐Arctic conditions from 78 ºN to 64 ºN . This covers a wide range of sea ice conditions and water temperatures, with those presently realized in the south likely to move northwards in a warmer future. Kelp forests occurred along the entire latitudinal range, and their depth extension and production increased southwards presumably in response to longer annual ice‐free periods and higher water temperature. The depth limit of 10% kelp cover was 9–14 m at the northernmost sites (77–78 ºN ) with only 94–133 ice‐free days per year, but extended to depths of 21–33 m further south (73 ºN –64 ºN ) where >160 days per year were ice‐free, and annual production of Saccharina longicruris and S. latissima, measured as the size of the annual blade, ranged up to sevenfold among sites. The duration of the open‐water period, which integrates light and temperature conditions on an annual basis, was the best predictor (relative to summer water temperature) of kelp production along the latitude gradient, explaining up to 92% of the variation in depth extension and 80% of the variation in kelp production. In a decadal time series from a high Arctic site (74 ºN ), inter‐annual variation in sea ice cover also explained a major part (up to 47%) of the variation in kelp production. Both spatial and temporal data sets thereby support the prediction that northern kelps will play a larger role in the coastal marine ecosystem in a warmer future as the length of the open‐water period increases. As kelps increase carbon‐flow and habitat diversity, an expansion of kelp forests may exert cascading effects on the coastal Arctic ecosystem.

Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - R. R. Lemos; S. G. de Lima; J. E. Gomes da Cunha; D. F. Oliveira; M. B. Rodrigues de Souza; C. F. J. Ayres; M. F. P. M. Albuquerque; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Assessment of Biotic Integrity of the Coastal Freshwater Tidal Zone of a Temperate Estuary of South America through Multiple Indicators - N. Gómez; M. Licursi; D. E. Bauer; E. S. Ambrosio; A. Rodrigues Capítulo (Estuaries and Coasts, 2012)

Spatial distributions of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) on coconut and their implications for development of efficient sampling plans - A. Roda; G. Nachman; F. Hosein; J. C. V. Rodrigues; J. E. Peña (Experimental and Applied Acarology, 2012)

Chemical control of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) in banana and coconut - Jose Carlos Verle Rodrigues; J. E. Peña (Experimental and Applied Acarology, 2012)

A review of the natural enemies of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) - Daniel Carrillo; J. Howard Frank; Jose Carlos V. Rodrigues; Jorge E. Peña (Experimental and Applied Acarology, 2012)

Molecular diversity of nitrogen-fixing bacteria associated with Chrysopogon zizanioides (L.) Roberty (vetiver), an essential oil producer plant - Renata E. Vollú; Arie F. Blank; Lucy Seldin; Marcia Reed Rodrigues Coelho (Plant and Soil, 2012)

An electronic study of pyrazolones drugs on agranulocytosis - J. Rodrigues Silva; A. Noronha Queiroz; E. A. Fontes Junior; M. V. Santos Silva; A. Manoel Herculano; A. M. J. Chaves Neto; R. Santos Borges (Medicinal Chemistry Research, 2012)

Combining ability of popcorn lines for seed quality and agronomic traits - Lia Mara Moterle; Alessandro de Lucca e Braccini; Carlos Alberto Scapim; Ronald José Barth Pinto; Leandro Simões Azeredo Gonçalves; Rosana Rodrigues; Antonio Teixeira do Amaral Júnior (Euphytica, 2012)

Estimation of Small Reservoir Storage Capacities with Remote Sensing in the Brazilian Savannah Region - Lineu N. Rodrigues; Edson E. Sano; Tammo S. Steenhuis; Denílson P. Passo (Water Resources Management, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

Savanna soil fertility limits growth but not survival of tropical forest tree seedlings - Ricardo A. G. Viani; Ricardo R. Rodrigues; Todd E. Dawson; Rafael S. Oliveira (Plant and Soil, 2011)

The involvement of the HO-1 pathway in the anti-inflammatory action of a sulfated polysaccharide isolated from the red seaweed Gracilaria birdiae - Edfranck de Sousa Oliveira Vanderlei; Ianna Wivianne Fernandes de Araújo; Ana Luíza Gomes Quinderé; Bruno Pedrosa Fontes; Ygor Raphael Gomes Eloy; José Ariévilo Gurgel Rodrigues; Antonio Alfredo Rodrigues e Silva; Hellíada Vasconcelos Chaves; Roberta Jeane Bezerra Jorge; Dalgimar Beserra de Menezes; Janaína Serra Azul Monteiro Evangelista; Mirna Marques Bezerra; et al. (Inflammation Research, 2011)

Seasonal abundance of the Atlantic bobtail squid Sepiola atlantica in Galician waters (NE Atlantic) - Marcelo Rodrigues; Manuel E. Garci; Jesús S. Troncoso; Ángel Guerra (Marine Biology Research, 2011)

Resistance to Meloidogyne incognita race 1 in the lettuce cultivars Grand Rapids and Salinas-88 - José Luiz Sandes de Carvalho Filho; Luiz Antonio Augusto Gomes; Wilson Roberto Maluf; Rafael Resende Oliveira; Daniela Santos Costa; Sindynara Fereira; Aline Beraldo Monteiro; Rejane Rodrigues da Costa e Carvalho (Euphytica, 2011)

Evaluation of Cu potential bioavailability changes upon coastal sediment resuspension: an example on how to improve the assessment of sediment dredging environmental risks - Wilson Machado; Ana Paula C. Rodrigues; Edison D. Bidone; Silvia M. Sella; Ricardo E. Santelli (Environmental Science and Pollution Research, 2011)

Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla) - Jaime Gongora; Rebecca E. Cuddahee; Fabrícia Ferreira do Nascimento; Christopher J. Palgrave; Stewart Lowden; Simon Y. W. Ho; Denbigh Simond; Chandramaya Siska Damayanti; Daniel James White; Wee Tek Tay; Ettore Randi; Hans Klingel; et al. (Zoologica Scripta, 2011)
Gongora, J., Cuddahee, R. E., do Nascimento, F. F., Palgrave, C. J., Lowden, S., Ho, S. Y. W., Simond, D., Damayanti, C. S., White, D. J., Tay, W. T., Randi, E., Klingel, H., Rodrigues‐Zarate, C. J., Allen, K., Moran, C. & Larson, G. (2011). Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla). — Zoologica Scripta, 40 , 327–335. Although African suids have been of scientific interest for over two centuries, their origin, evolution, phylogeography and phylogenetic relationships remain contentious. There has been a long‐running debate concerning the evolution of pigs and hogs (Suidae), particularly regarding the phylogenetic relationships among extant Eurasian and African species of the subfamily Suinae. To investigate these issues, we analysed the mitochondrial and nuclear DNA sequences of extant genera of Suidae from Eurasia and Africa. Molecular phylogenetic analyses revealed that all extant sub‐Saharan African genera form a monophyletic clade separate from Eurasian suid genera, contradicting previous attempts to resolve the Suidae phylogeny. Two major sub‐Saharan African clades were identified, with Hylochoerus and Phacochoerus grouping together as a sister clade to Potamochoerus. In addition, we find that the ancestors of extant African suids may have evolved separately from the ancestors of modern day Sus and Porcula in Eurasia before they colonised Africa. Our results provide a revision of the intergeneric relationships within the family Suidae.

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Base excision repair genes XRCC1 and APEX1 and the risk for prostate cancer - H. Kuasne; I. S. Rodrigues; R. Losi-Guembarovski; M. B. Reis; P. E. Fuganti; E. P. Gregório; F. Libos Junior; H. M. Matsuda; M. A. F. Rodrigues; M. O. Kishima; I. M. S. Cólus (Molecular Biology Reports, 2011)

A new method for the detection of Pneumocystis jirovecii using flow cytometry - J. Barbosa; C. Bragada; S. Costa-de-Oliveira; E. Ricardo; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Seroprevalence of orthopoxvirus in an Amazonian rural village, Acre, Brazil - B. E. F. Mota; G. S. Trindade; T. C. Diniz; M. da Silva-Nunes; E. M. Braga; M. Urbano-Ferreira; G. O. L. Rodrigues; C. A. Bonjardim; P. C. P. Ferreira; E. G. Kroon (Archives of Virology, 2010)

Characterization of two recessive genes controlling resistance to all races of bacterial spot in peppers - C. Eduardo Vallejos; Valerie Jones; Robert E. Stall; Jeffrey B. Jones; Gerald V. Minsavage; Diana C. Schultz; Rosana Rodrigues; Lisa E. Olsen; Michael Mazourek (Theoretical and Applied Genetics, 2010)

Effects of Antifungal Agents in Sap Activity of Candida albicans Isolates - Carolina Rodrigues Costa; Rosália Santos Amorim Jesuíno; Janine de Aquino Lemos; Orionalda de Fátima Lisboa Fernandes; Lúcia Kioko Hasimoto e Souza; Xisto Sena Passos; Maria do Rosário Rodrigues Silva (Mycopathologia, 2010)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Soil and litter fauna of cacao agroforestry systems in Bahia, Brazil - M. K. da Silva Moço; E. F. da Gama-Rodrigues; A. C. da Gama-Rodrigues; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2009)

Capturing the Many Dimensions of Threat: Comment on Salafsky et al. - ANDREW BALMFORD; PETE CAREY; VALERIE KAPOS; ANDREA MANICA; ANA S.L. RODRIGUES; JÖRN P.W. SCHARLEMANN; RHYS E. GREEN (Conservation Biology, 2009)

A role for atorvastatin and insulin combination in protecting from liver injury in a model of type 2 diabetes with hyperlipidemia - P. Matafome; E. Nunes; T. Louro; C. Amaral; J. Crisóstomo; L. Rodrigues; A. R. Moedas; P. Monteiro; A. Cipriano; R. Seiça (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Influence of the Lipophilic External Phase Composition on the Preparation and Characterization of Xylan Microcapsules—A Technical Note - Toshiyuki Nagashima; Elquio Eleamen Oliveira; Acarília Eduardo da Silva; Henrique Rodrigues Marcelino; Monique Christine Salgado Gomes; Larissa Muratori Aguiar; Ivonete Batista de Araújo; Luiz Alberto Lira Soares; Anselmo Gomes de Oliveira; E. Sócrates Tabosa do Egito (AAPS PharmSciTech, 2008)

Purification of polyhydroxybutyrate produced by Burkholderia cepacia IPT64 through a chemical and enzymatic route - Daniel V. Suzuki; José M. Carter; Maria Filomena A. Rodrigues; Elda S. da Silva; Alfredo E. Maiorano (World Journal of Microbiology and Biotechnology, 2008)

Preliminary data on microcharacters and chromosome number in Tornabenea species (Apiaceae) from Cape Verde Islands - A. C. Grosso; L. Rodrigues; I. Gomes; E. S. Martins; G. Teixeira (Plant Biosystems, 2008)

Superoxide reduction by Nanoarchaeum equitans neelaredoxin, an enzyme lacking the highly conserved glutamate iron ligand - João V. Rodrigues; Bruno L. Victor; Harald Huber; Lígia M. Saraiva; Cláudio M. Soares; Diane E. Cabelli; Miguel Teixeira (JBIC Journal of Biological Inorganic Chemistry, 2008)

Relationships among mercury, selenium, and neurochemical parameters in common loons (Gavia immer) and bald eagles (Haliaeetus leucocephalus) - A. M. Scheuhammer; N. Basu; N. M. Burgess; J. E. Elliott; G. D. Campbell; M. Wayland; L. Champoux; J. Rodrigue (Ecotoxicology, 2008)

Identification of an arsenic resistance mechanism in rhizobial strains - Paula Sá-Pereira; Mónica Rodrigues; Isabel Videira e Castro; Fernanda Simões (World Journal of Microbiology and Biotechnology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Species distribution and antifungal susceptibility patterns of Candida spp. bloodstream isolates from a Brazilian tertiary care hospital - Xisto Sena Passos; Carolina Rodrigues Costa; Crystiane Rodrigues Araújo; Elisa Sales Nascimento; Lúcia Kioko Hasimoto e Souza; Orionalda de Fátima Lisboa Fernandes; Werther Souza Sales; Maria do Rosário Rodrigues Silva (Mycopathologia, 2007)

Superoxide reduction by Archaeoglobus fulgidus desulfoferrodoxin: comparison with neelaredoxin - João V. Rodrigues; Lígia M. Saraiva; Isabel A. Abreu; Miguel Teixeira; Diane E. Cabelli (JBIC Journal of Biological Inorganic Chemistry, 2007)

The effects of fructose-1,6-bisphosphate and dexamethasone on acute inflammation and T-cell proliferation - R. Pestana Lopes; A. Lunardelli; T. Preissler; C. E. Leite; J. C. F. Alves-Filho; F. Bordignon Nunes; J. Rodrigues de Oliveira; M. E. Bauer (Inflammation Research, 2006)

Species Distribution and Antifungal Susceptibility Profile of Oral Candida Isolates from HIV-infected Patients in the Antiretroviral Therapy Era - Carolina Rodrigues Costa; Janine Aquino de Lemos; Xisto Sena Passos; Crystiane Rodrigues de Araújo; Ana Joaquina Cohen; Lúcia Kioko Hasimoto e Souza; Maria do Rosário Rodrigues Silva (Mycopathologia, 2006)

Extract of the bristles of Dirphia sp. increases nitric oxide in a rat pleurisy model - A. Lunardelli; C. E. Leite; M. Guerra Simões Pires; J. Rodrigues de Oliveira (Inflammation Research, 2006)

In situ probing of Xylella fastidiosa in honeydew of a xylem sap‐feeding insect using 16S rRNA‐targeted fluorescent oligonucleotides - Jorge L. M. Rodrigues; Maria E. Silva‐Stenico; Adriane N. De Souza; João R. S. Lopes; Siu M. Tsai (Environmental Microbiology, 2006)
Summary Xylella fastidiosa is a plant pathogen that threatens a US$ 4.6 billion worldwide wine and citrus industry. Monitoring its presence and distribution in plants and vectors is crucial for designing control strategies, as well as for understanding its ecological role and fate. We developed two fluorescent oligonucleotide probes complementary to different regions of the 16S rRNA gene of X. fastidiosa . The specificity of the newly designed probes S‐S‐X.fas‐0067‐a‐A‐18 and S‐S‐X.fas‐1439‐a‐A‐18 was demonstrated using fluorescence in situ hybridization (FISH) for 12 Xylella isolates, 15 closely related microorganisms and three plant endophytes. These probes were used to detect and quantify X. fastidiosa in plant sap (average value of 2.9 ± 0.3 × 10 6 cells ml −1 ) from three different citrus orchards. In a second experiment, cells were quantified in honeydew (2.2 ± 0.2 × 10 4 cells ml −1 ) collected from the insect vector Bucephalogonia xanthophis during the acquisition access period on an infected plant. The number of pathogen cells retained or digested by the insect is 10 000 times greater than the estimated minimum value to ensure an efficient transmission. Polymerase chain reaction (PCR) amplification using specific primers with plant sap and honeydew samples, followed by sequencing, confirmed the presence of the plant pathogen. This is the first demonstration of FISH being used for environmental samples, such as plant sap and insect honeydew, to estimate the abundance of a plant pathogen during infection.

Decreased Susceptibility to Nitroimidazoles Among Bacteroides Species in Brazil - Jessica Manya B. D. Vieira; Renata F. Boente; Karla Rodrigues Miranda; Kátia E. S. Avelar; Regina M. C. P. Domingues; Maria Candida de S. Ferreira (Current Microbiology, 2006)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Endosperm-preferred Expression of Maize Genes as Revealed by Transcriptome-wide Analysis of Expressed Sequence Tags - Natalia C. Verza; Thaís Rezende e Silva; Germano Cord Neto; Fábio T. S. Nogueira; Paulo H. Fisch; Vincente E. de Rosa; Marcelo M. Rebello; André L. Vettore; Felipe Rodrigues da Silva; Paulo Arruda (Plant Molecular Biology, 2005)

Vasopressin release during endotoxaemic shock in mice lacking inducible nitric oxide synthase - Evelin C. Carnio; Angelita M. Stabile; Marcelo E. Batalhão; João Santana Silva; José Antunes-Rodrigues; Luiz G. S. Branco; Sheldon Magder (Pflügers Archiv - European Journal of Physiology, 2005)

Meiotic instability of chicken ultra-long telomeres and mapping of a 2.8 megabase array to the W-sex chromosome - K. L. Rodrigue; B. P. May; T. R. Famula; M. E. Delany (Chromosome Research, 2005)

Anther culture and cold treatment of floral buds increased symmetrical and extra nuclei frequencies in soybean pollen grains - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E. A. Mariath; Leandro B. Irano; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Inorganic chemical composition of native trees of the Atlantic Forest - E. J. França; E. A. De Nadai Fernandes; M. A. Bacchi; R. R. Rodrigues; T. G. Verburg (Environmental Monitoring and Assessment, 2005)

Spatial and temporal variability in forest–atmosphere CO 2 exchange - D. Y. Hollinger; J. Aber; B. Dail; E. A. Davidson; S. M. Goltz; H. Hughes; M. Y. Leclerc; J. T. Lee; A. D. Richardson; C. Rodrigues; N.A. Scott; D. Achuatavarier; et al. (Global Change Biology, 2004)
Seven years of carbon dioxide flux measurements indicate that a ∼90‐year‐old spruce dominated forest in Maine, USA, has been sequestering 174±46 g C m −2 yr −1 (mean±1 standard deviation, nocturnal friction velocity ( u * ) threshold >0.25 m s −1 ). An analysis of monthly flux anomalies showed that above‐average spring and fall temperatures were significantly correlated with greater monthly C uptake while above‐average summer temperatures were correlated with decreased net C uptake. Summer months with significantly drier or wetter soils than normal were also characterized by lower rates of C uptake. Years with above‐average C storage were thus typically characterized by warmer than average spring and fall temperatures and adequate summer soil moisture. Environmental and forest–atmosphere flux data recorded from a second tower surrounded by similar forest, but sufficiently distant that flux source regions (‘footprints’), did not overlap significantly showed almost identical temperature and solar radiation conditions, but some differences in energy partitioning could be seen. Half‐hourly as well as integrated (annual) C exchange values recorded at the separate towers were very similar, with average annual net C uptake differing between the two towers by

Ring-testing and Field-validation of a Terrestrial Model Ecosystem(TME) – An Instrument for Testing Potentially Harmful Substances: Effects of Carbendazim on Organic Matter Breakdown and Soil Fauna Feeding Activity - Bernhard Förster; Cornelis A.M. Van Gestel; Josée E. Koolhaas; Gerrit Nentwig; José M.L. Rodrigues; J. Paulo Sousa; Susan E. Jones; Thomas Knacker (Ecotoxicology, 2004)

Ring-Testing and Field-Validation of a Terrestrial Model Ecosystem (TME) – An Instrument for Testing Potentially Harmful Substances: Effects of Carbendazim on Nutrient Cycling - Cornelis A.M. Van Gestel; Josée E. Koolhaas; Hans-Joachim Schallnaß; José M.L. Rodrigues; Susan E. Jones (Ecotoxicology, 2004)

Ring-Testing and Field-Validation of a Terrestrial Model Ecosystem (TME) – An Instrument for Testing Potentially Harmful Substances: Effects of Carbendazim on Earthworms - Jörg Römbke; Cornelis A.M. Van Gestel; Susan E. Jones; Josée E. Koolhaas; José M.L. Rodrigues; Thomas Moser (Ecotoxicology, 2004)

Ring-Testing and Field-Validation of a Terrestrial Model Ecosystem (TME) – An Instrument for Testing Potentially Harmful Substances: Effects of Carbendazim on Enchytraeids - Thomas Moser; Cornelis A.M. Van Gestel; Susan E. Jones; Josée E. Koolhaas; José M.L. Rodrigues; Jörg Römbke (Ecotoxicology, 2004)

Ring-testing and Field-validation of a Terrestrial Model Ecosystem (TME) – An Instrument for Testing Potentially Harmful Substances: Effects of Carbendazim on Nematodes - Thomas Moser; Hans-Joachim Schallnaß; Susan E. Jones; Cornelis A.M. Van Gestel; Josée E. Koolhaas; José M.L. Rodrigues; Jörg Römbke (Ecotoxicology, 2004)

Ring-Testing and Field-validation of a Terrestrial Model Ecosystem (TME) – An Instrument for Testing Potentially Harmful Substances: Effects of Carbendazim on Soil Microbial Parameters - J. Paulo Sousa; José M.L. Rodrigues; Susana Loureiro; Amadeu M.V.M. Soares; Susan E. Jones; Bernhard Förster; Cornelis A.M. Van Gestel (Ecotoxicology, 2004)

Ring-testing and Field-validation of a Terrestrial Model Ecosystem (TME) – An Instrument for Testing Potentially Harmful Substances: Fate of the Model Chemical Carbendazim - Susan E. Jones; Denis J. Williams; Peter J. Holliman; Nick Taylor; Joachim Baumann; Bernhard Förster; Cornelis A.M. Van Gestel; José M.L. Rodrigues (Ecotoxicology, 2004)

Trenching Behavior by Caterpillars of the Euphorbia Specialist, Pygarctia roseicapitis: A Field Study - E. A. Bernays; M. S. Singer; D. Rodrigues (Journal of Insect Behavior, 2004)

Impairment of inflammatory response in adult rats submitted to maternal undernutrition during early lactation: Role of insulin and glucocorticoid - C. Barja-Fidalgo; E. P. G. Souza; S. V. Silva; A. L. Rodrigues; E. A. Anjos-Valotta; P. Sannomyia; M. S. DeFreitas; A. S. Moura (Inflammation Research, 2003)

Chromosomal studies in Callicebus donacophilus pallescens, with classic and molecular cytogenetic approaches: Multicolour FISH using human and Saguinus oedipus painting probes - R. M. S. Barros; C. Y. Nagamachi; J. C. Pieczarka; L. R. R. Rodrigues; M. Neusser; E. H. de Oliveira; J. Wienberg; J. A. P. C. Muniz; J. D. Rissino; S. Muller (Chromosome Research, 2003)

Tissue-specific regulation of BiP genes: a cis-acting regulatory domain is required for BiP promoter activity in plant meristems - Reginaldo A.A. Buzeli; Júlio C.M. Cascardo; Leonardo A.Z. Rodrigues; Maxuel O. Andrade; Raul S. Almeida; Marcelo E. Loureiro; Wagner C. Otoni; Elizabeth P.B. Fontes (Plant Molecular Biology, 2002)

The interhepatocytic macrophages and pale‐grey cells in brown trout liver ontogenesis - A. D. Resende; E. Rocha; R. A. F. Monteiro; P. Rodrigues (Journal of Fish Biology, 2002)
Pale‐grey cells appeared in the livers of healthy and non‐stressed brown trout Salmo trutta 3 weeks post‐hatching whereas interhepatocytic macrophages appeared at 5 months. Cells with intermediate morphological characteristics between those of pale‐grey cells and macrophages were identified in all ages studies. Cell ultrastructure supported the idea that pale‐grey cells probably belonged to the macrophage lineage, being eventual precursors of the active phagocytes residing amongst hepatocytes.

Plant-soil interactions in multistrata agroforestry in the humid tropicsa - G. Schroth; J. Lehmann; M. R. L. Rodrigues; E. Barros; J. L. V. Macêdo (Agroforestry Systems, 2001)

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

Microbiology and physiology of Cachaça (Aguardente) fermentations - Rosane Freitas Schwan; Alexandre T. Mendonça; João José da Silva; Valéria Rodrigues; Alan E. Wheals (Antonie van Leeuwenhoek, 2001)

Low resistance against novel 2-benzylamino-1,3,5-triazine herbicides in atrazine-resistant Chenopodium album plants - Hitoshi Kohno; Aiko Ohki; Shinpei Ohki; Kazuya Koizumi; Maria E. Van den Noort; Gustavo C. Rodrigues; Jack J.S. Van Rensen; Ko Wakabayashi (Photosynthesis Research, 2000)

Patterns of genetic divergence in Chondrostoma lusitanicum Collares‐Pereira, in intermittent Portuguese rivers - M.M. COELHO; M.J. ALVES; E. RODRIGUES (Fisheries Management and Ecology, 1997)
Samples collected from throughout the range of Chondrostoma lusitanicum Collares‐Pereira, were examined electrophoretically for patterns of variation at 24 presumptive gene loci. Thirteen loci were found to be polymorphic (frequency of the most common allele 0.95). There was high differentiation between rivers, especially in the southern populations of the Mira and the Arade catchments. This differentiation was associated with a low level of genetic variation and was thus interpreted in the light of past and present bottlenecks. The differentiation of C. lusitanicum is congruent with that already observed for another cyprinid species of the genus Leuciscus inhabiting the same catchments. This reinforces the hypothesis that the periodic drying‐up of extensive sections of these rivers may lead to reduction in population sizes and subsequent differentiation. The level of genetic divergence of both the Mira and Arade populations of C. lusitanicum compared to all other populations sampled suggested a review of their conspecific status is necessary despite morphological similarity. The management implications in these rivers, and in the Tejo and Sado basins where C. lusitanicum is very rare, are discussed.

Sediment chemistry — Infaunal community structure in a southern European estuary related to solid-phase Microtox® toxicity testing - V. Quintino; A. M. Picado; A. M. Rodrigues; E. Mendonça; M. H. Costa; M. Bordalo Costa; P. Lindgaard-Jørgensen; T. H. Pearson (Aquatic Ecology, 1995)

Modelling infant mortality - Renan Moritz Varnier Rodrigues de Almeida; E. O. Attinger (Annals of Biomedical Engineering, 1993)